Electron-rich Pt interfaces enabled by Mn-modified Co(OH)2 for chloride-tolerant hydrogen evolution in alkaline seawater - Tianxiao Xie; Feng Chen; Zikang Zhao; Mengdi Li; Yide Luo; Zongtai Zhou; Junshuang Zhou; Faming Gao (Fuel, 2027)

Optimization of grinding media charge Based on grinding Kinetics: A Case study of copper ore - Ruitao Liu; Qingfei Xiao; Saizhen Jin; Mengtao Wang; Xianglong Li; Yanwei Zhao; Zhong Luo; Sheng Jian; Feng Xie (Minerals Engineering, 2026)

The first application of ceramic balls in a 7.32 m regrinding ball mill - Junquan Lai; Caibin Wu; Chengfang Yuan; Shuncheng Han; Yufeng Wei; Mingjun Leng; Feng Xie; Yuqing Li (Minerals Engineering, 2026)

Ultrasound-assisted selective leaching of lithium and nickel from spent lithium-ion batteries (NCM): Leaching behavior and mechanism - Shiju Li; Haibei Wang; Shengdong Wang; Feng Xie; Xudong Sun (Minerals Engineering, 2026)

Synergistic mechanism between xanthan gum and locust bean gum: a perspective from hydrogen bonding, electrostatic, and hydrophobic interactions - Yantao Liu; Conghui Feng; Diming Li; Junxian Hu; Manyi Tu; Wei Xu; Pengfei Li; Zhoujian Xie; Liang He; Katsuyoshi Nishinari; Nan Yang (Food Hydrocolloids, 2026)

Unraveling the role of IL-17 signaling pathway in breast cancer-related depression: insights from in vivo/in vitro models and transcriptomic analysis - Huimin Li; Feng Xie; Xiang Cui; Guidong Shen (Functional & Integrative Genomics, 2026)

Long-term organic fertilization fosters modular microbial networks: A global analysis of soil bacteriome responses - Shu-Le Li; Cai Chen; Xiang-Yu Dai; Hai-Song Yan; Yao-Yang Xu; Meili Feng; Jun He; Jianfeng Ren; Wan-Ying Xie; Fang-Jie Zhao (Soil Ecology Letters, 2026)

A mechanism-constrained large language model-based intelligent diagnosis framework for bridge defects - Hui Jin; Si-Ming Zhou; Han Chen; Zhi-Yu Xie; Feng Li; Yong Li; Jian-Feng Zhu; Yi-Feng Ling; Zhi-Min Wu; Xiang-Ming Zhou (Engineering Structures, 2026)

Comparative analysis of multiple health risks from different air pollution events - Feixue Zheng; Jinwen Li; Chenjie Hua; Tingyu Liu; Jiali Xie; Zemin Feng; Yusheng Zhang; Chao Yan; Men Xia; Qi Yuan; Federico Bianchi; Tuukka Petäjä; et al. (Journal of Environmental Sciences, 2026)

Thermal hardening–damage mechanism and shear instability criterion of high-temperature shale under direct shear - Chunfeng Ye; Zheng Chen; Cunbao Li; Yongrui Li; Zechen Feng; Fei Wu; Heping Xie (International Journal of Rock Mechanics and Mining Sciences, 2026)

Unveiling the cooling mechanism of strontium and copper oxalates as coolants in a 5‑Aminotetrazole Propellant: Modulating pyrolysis and combustion performance - Si-Yuan Zhou; Xuan Li; Qing Chen; Zhong-Wei Hu; Dan Zhang; Zhong-min Xiao; Li-Feng Xie; Mi Li; Andrei Rotaru (Fuel, 2026)

Biomimetic hierarchical fibrous-spherical membranes with robust superhydrophobicity for high-efficiency oil-water separation - Peike Jiang; Miaomiao Li; Peng Liu; Shitao Li; Yeqing Xu; Shiyue Cao; Chen Xie; Yucheng Yin; Peiyong Feng; Xin Jing (Desalination, 2026)

Soft residual attention-based physics-informed neural networks for acoustic phased array-based wavefield reconstruction in logging-while-drilling - Qiang Feng; Wei Zhang; Yibing Shi; Zhipeng Li; Weihong Xie (Computers & Geosciences, 2026)

Biomass-derived porous carbon supported Cu₃P/TiO₂ N-doped heterojunction for visible-light photocatalysis - Tingxuan Xie; Manting Zheng; Qingdong Deng; Weixi Zhang; Shenyi Liang; Wei Li; Yinli Dai; Jiaqi Zhang; Xu Feng; Zhanlin Wang; Junhao Li; Runjing Li; et al. (Colloids and Surfaces C: Environmental Aspects, 2026)

Sedimentological, geochronological, and palynological insights into paleoclimate and sea-level changes since the late Pleistocene in the Chaoshan Plain, SE China - Pan Zhang; Yanbo Zhang; Feng Li; Junwu Shu; Banghua Lu; Huaguo Liu; Qichao Jia; Changlong Li; Peifeng Xie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Influence of feed size distribution on energy consumption of jaw Crusher: Experimental and simulation study - Ruitao Liu; Qingfei Xiao; Saizhen Jin; Mengtao Wang; Xianglong Li; Yanwei Zhao; Sheng Jian; Feng Xie (Minerals Engineering, 2026)

Al-modified ReS2/TiO2 with enhanced adsorption and stepwise interfacial charge migration for photocatalytic PFOA removal - Ran Chen; Feng Liu; Zhenkai Liu; Jun Wan; Qidi Liu; Yixin Ma; Yan Li; Shunli Wan; Yongming Luo; Haijiao Xie (Journal of Environmental Chemical Engineering, 2026)

Progress in modification strategies of perovskite oxides for CO2 electrolysis in solid oxide electrolysis cells - Yuanxin Xie; Teng Li; Ruoping Li; Jing Ding; Nengjie Feng; Xuebin Luan; Gongde Wu; Wei Du; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2026)

Mechanisms and impacts of erythritol and tartaric acid on the quality of high moisture extruded Tartary buckwheat noodles: From gel structure to in vitro starch digestibility - Chunlei Li; Kaiwen Xie; Xiao Feng; Hongwei Wang; Hua Zhang; Xiaozhi Tang (Innovative Food Science & Emerging Technologies, 2026)

Ultrasound-initiated crosslinking between cod-rice dual-protein: Mechanisms underlying the development of dual-protein gel - Li Jiang; Feng Yang; Jing Peng; Dingyi Liu; Yisha Xie; Qingqing Liu; Yongjun Yuan (Food Research International, 2026)

Diversity of Diaporthe species associated with post-harvest decay on kiwifruit in China - Lu Feng; Yang Lin; Chao Li; Jiatao Xie; Jiasen Cheng; Bo Li; Tao Chen; Daohong Jiang; Yanping Fu (Fungal Biology, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

Trade-off between structural resilience and kinetics induced by N2-plasma activated CN− vacancies in high-entropy Prussian blue cathodes for sodium-ion storage - Qiang Liu; Yan-Jiang Liu; Miao-Yu Li; Ting-Liang Xie; Hao-Tian Tong; Bo Jin; Shuang-Feng Yin (Chemical Engineering Journal, 2026)

Toward integrated CO2 capture and photocatalytic conversion: From catalyst design to reactor engineering - Ziyi Li; Chenxi Ran; Jiao Feng; Jun Zhong; Jiaxin Xie; Yue-Fei Zhang; Xiao Luo; Yu Mao; Zhiwu Liang (Chemical Engineering Journal, 2026)

Seasonal synchrony inflates spatial dependence in water-quality Markov chains: evidence from a fine-scale agricultural wetland - Dong Xie; Yu Xue; Xin Li; Yuqing Feng (Environmental Monitoring and Assessment, 2026)

Vacancy-confinement strategy applied in electrocatalytic flow-through membrane reactors - Fangshu Xie; Ying Gao; Shuo Ji; Yuanyuan Qian; Yizhou Feng; Weihuang Zhu; Zhihua Li; Fengchang Wu (Water Research, 2026)

Decoding the honey-like aroma formation in Chinese rice-flavor baijiu via key aroma compounds and their perceptual interaction - Peiqi Li; Kaijun Xie; Yufeng Feng; Qiang Li; Long Zhang; Ruijie Wan; Zhenzhen Ning; Yuchan Wei; Hehe Li; Shuang Chen; Yan Xu (Food Research International, 2026)

Unlocking collagen-derived novel antioxidant peptides from by-product bones of silver carp: label-free peptidomic discovery, bioinformatics-aided mechanistic elucidation, and cytoprotective effects against oxidative damage - Jin Zhang; Feng Lin; Yimeng Mei; Ruoyu Xie; Jiaxin Chen; Jun Hu; Hongying Du; Guijie Hao; Shuangxi Li; Wenxuan Chen (Food Research International, 2026)

Mitigation role of edible oil and polyol sweeteners in the formation of acrylamide and 5-hydroxymethylfurfural in baked bread - You Long; Feng Li; Yuting Wang; Qiang Yu; Jianhua Xie; Yi Chen (Food Control, 2026)

Mechanistic insights into BDE-153-induced idiopathic pulmonary fibrosis through network toxicology, machine learning, and cellular validation - Haitao Cao; Shuanghua Xie; Minqian Feng; Yanyan Yao; Hemin Wu; Chuyan Zhang; Chan Ding; Jiaxin Zhang; Xinyuan Zhao; Yingjun Li; Huadong Xu (Food and Chemical Toxicology, 2026)

Spatiotemporal radical engineering via non-destructive synchrotron lithography for multimodal functionalization of inert polymers - Hao Zhang; Xincheng Xie; Shengbin Cao; Fan Zhang; Lin Da; Yang Liu; Bomin Liu; Feng Tian; Caizhen Zhu; Xiuhong Li; Jian Xu (Chemical Engineering Journal, 2026)

Tailoring a functional micro-environment via Pt single atoms on Ni4Mo to suppress OH poisoning for efficient alkaline hydrogen evolution - Feng Chen; Jing Jin; Wenfeng Peng; Kuo Wei; Tianxiao Xie; Hong Pan; Jinghui Li; Junshuang Zhou; Faming Gao (Chemical Engineering Journal, 2026)

From bacterial template to green catalyst: Bio-fabrication of nanostructured nickel hydroxycarbonate for oxygen evolution via microbial mineralization - Feng Duan; Qichang Li; Li Xu; Haifang Wu; Ercai Pan; Wei Ding; Junhui Guo; Hang Ping; Liuyi Zhao; Hao Xie; Zhengyi Fu; Zhaoyong Zou (Chemical Engineering Journal, 2026)

Genomic landscape of idiopathic male infertility and the pregnancy outcomes following assisted reproductive technology - Chen Tan; Tongyao Hu; Lanlan Meng; King Kin Lam; Qing Zhang; Xilin Xu; Shimin Yuan; Yurong Wang; Zilan Huang; Keren Zhou; Yong Li; Chunbo Xie; et al. (Science Bulletin, 2026)

Precision omic portrait deciphers the epigenetic variable during cellular identity reshaping of metastatic head and neck squamous cell carcinoma - Qiushi Feng; Xiaofeng Shan; Yangyang Xia; Lingzi Liao; Yifan Kang; Zimeng Li; Ziwei Dai; Yingyue Chai; Xinyuan Zhang; Luming Wang; Shang Xie; Zhigang Cai (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Surface charge regulation enhances photo-carrier dynamics and adsorption in WSe2 for efficient Cr(VI) photoreduction - Zimeng Li; Shiao Feng; Tuo Tao; Chunxue Zheng; Mingzheng Xie (Journal of Environmental Chemical Engineering, 2026)

Towards accurate cultivar-specific yield forecasting with a novel crop and climate fusion framework - Kunhong Li; Zhongbin Yan; Christoph Menz; Andrej Ceglar; Peng Qin; Haibo Pu; Haohui Peng; Jinyue Liao; Lei Tao; Jing Li; Li Xie; Desheng Yang; et al. (Field Crops Research, 2026)

MIL-125-NH2@Co-HHTP based solid phase microextraction for vulcanization accelerators determination in water samples by gas chromatography - Long Pang; Haiyang Feng; Xingru Hu; Shujie Tang; Xuan Wang; Li Guo; Yaxuan Xu; Meiqi Xie (Environmental Research, 2026)

Prenatal exposure to per- and polyfluoroalkyl substances, placental DNA methylation, and small vulnerable newborns: Insights from the Shanghai maternal-child pairs cohort - Yue Zhao; Liyi Zhang; Weizhao Cao; Pengpeng Wang; Yuyan Gui; Yuhan Zhou; Qiang Li; Yaqi Xu; Feng Wang; Jieming Wang; Yashuo Xie; Huijing Shi; et al. (Environmental Research, 2026)

Plastic-to-jet conversion of plastic waste: A critical review of pyrolysis oil characteristics and aviation fuel compliance - Shuhao Li; Jianhua Zhang; Lei Zhang; Feng Wang; Zongli Xie (Chemical Engineering Journal, 2026)

Formation mechanisms of a severe springtime ozone episode in the Beibu Gulf, China: The role of the marine “ozone pool” and regional transport - Runxi Pan; Fei Jiang; Shuzhuang Feng; Dewei Yang; Yuning Xie; Hang Li; Yu He; Mengwei Jia; Yanhong Xie; Bei Chen (Atmospheric Pollution Research, 2026)

Hyperspectral multi-angle driven modified photochemical reflectance index (mPRI): A novel approach for accurately estimating radiation use efficiency in winter wheat - Haiyan Zhang; Yapeng Wu; Qiwen Chen; Yangyang Wang; Jianzhao Duan; Li He; Geng Ma; Yingxin Xie; Jiandong Hu; Chenyang Wang; Wei Feng (Precision Agriculture, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Optimizing Habitat Management Strategies for Wintering Geese Using a Cross-scale Species Distribution Modelling Framework in Dongting Lake, China - Siqi Zhang; Yucheng Song; Yeai Zou; Pingyang Zhang; Qian Chen; Feng Li; Zhengmiao Deng; Yonghong Xie (Chinese Geographical Science, 2026)

A highly sensitive and simultaneous bifunctional fluorescent probe for detecting mitochondrial viscosity and nitroreductase activity in vivo - Manlin Fu; Jiarong Zhou; Qingwen Li; Qi Zhou; Zhenda Xie; Jin-Feng Hu (Analytica Chimica Acta, 2026)

BMSC-derived exosomal METTL3 synergizes with Sevoflurane to inhibit ferroptosis in pulmonary ischemia/reperfusion injury by enhancing USP7 N6-methyladenosine modification - Liang Zheng; Xiang-yu Xie; Kun Li; Xiao-feng He; Jiang Shen; Cao Gao (Apoptosis, 2026)

Yeast extract modulates the auxin biosynthesis pathway via TAR2 to enhance tanshinone accumulation in salvia miltiorrhiza - Xuhui Huang; Xiyuan Sun; Qiuyan Leng; Xiao Feng; Jinlin Xie; Xuanfeng Du; Xuexue Deng; Yuanyuan Jiang; Ruiwu Yang; Yunsong Zhang; Li Zhang (Acta Physiologiae Plantarum, 2026)

The microRNA-transcription factor-mRNA regulatory pathways involved in protein homeostasis and amino acid and lipid metabolism in the pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang (Aquaculture, 2026)

3D analytical modeling of seismic ground motion and energy partitioning in the marine site subjected to obliquely P-SV waves - Guang-rui Feng; Li-quan Xie; Chen-wei Luo (Soil Dynamics and Earthquake Engineering, 2026)

Soil crack healing, recurrence and the temporal persistence of preferential flow under wet-dry cycles revealed by deep-learning image analysis and breakthrough curves - Qinglong Zhang; Ce Wang; Meixiang Xie; Wei Qi; Genxiang Feng; Zhanyu Zhang; Yuanjie Li (Soil and Tillage Research, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Miocene evolution of source to sink in the Xihu Depression: evidence from Diaoyu island fold-uplift belt provenance in the East China Sea - Zhiyi Tang; Donghui Jiang; Kun Li; Feng Wu; Beichen Chen; Xin Dong; Xinong Xie (Journal of Asian Earth Sciences, 2026)

High-performance formaldehyde sensing of room-temperature UV-activated Mn-TiO2: Key effects of different crystal phase structures and Mn doping on carrier behavior and adsorption - Yunhong Zhao; Siyuan Guo; Xiao Feng; ZhiHan He; Tengfeng Xie; Ziheng Li; Yanhong Lin (Environmental Research, 2026)

Cross-regional assessment of heavy metal contamination and Cd exceedance risk in specialty vegetable-producing soils across China - Xiaoqin Wang; Lu Liu; Kunhao Xie; Xiaojie Feng; Lihong Gao; Mintao Sun; Jun Wang; Yan Yan; Xu Linbo; Yansu Li; Chaoxing He (Environmental Research, 2026)

Synergistic radiative and evaporative cooling in LiCl-cellulose nanofiber xerogels for temperature reduction and energy saving - Yuheng Fan; Zhengyuan Li; Kai Feng; Pengwei Xie; Hui Tian; Yang Wu; Feng Zhou (Desalination, 2026)

Regulating radical pathways in highly selective photon–phonon synergistic methane oxidation by tuning Au nanoparticle size over Au–ZrO2 - Shengrong Zhou; Zitong Bao; Yuhang Shao; Xiaolei Guo; Xinru Jiang; Yi Xie; Dong Fang; Ran Ran; Guangzhao Li; Feng Zeng; Hongwei Zhang (Chemical Engineering Journal, 2026)

Deformation and failure characteristics of tunnels in surrounding rock with weak interlayers: Insights from physical model tests and numerical investigations - Fan Ding; Xiang Fan; Yongli Xie; Wenjie Li; Wenwen Feng (Bulletin of Engineering Geology and the Environment, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

First report of scale drop disease virus (SDDV) infection in cultured silver pomfret (Pampus argenteus) in China: Isolation and pathogenic characterization - Su-Ming Zhou; Yang-Yang Bai; Deng-Feng Li; Jia-Song Xie; Ya-Jun Wang; Fei Yin (Aquaculture, 2026)

Incorporating water-energy-carbon constraints into the optimization of urban refined land use: A case study of Zhengzhou, China - Zhixiang Xie; Wei Feng; Rongqin Zhao; Liangang Xiao; Hanbing Li; Shuangsheng Yao; Yaohui Gao; Yufei Ji; Xiaowei Chuai (Sustainable Cities and Society, 2026)

Intelligent compost maturity assessment: A hybrid computer vision and physicochemical parameters - Haojun Xie; Xueru Zhu; Chao Li; Fan Jiao; Xuebin Feng; Yiyun Zhang; Hua Li (Sustainable Chemistry and Pharmacy, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Seep-related carbonates on continental shelves: Distinctive processes and morphologies revealed by the Qiongdongnan Shelf, South China Sea - Hongli Wang; Qiang Zhao; Fangqi Wang; Qingfeng Hua; Qiuhong Xie; Yangting Liu; Chenguang Liu; Yanliang Pei; Xishuang Li; Yikai Feng; Fei Cao (Marine Geology, 2026)

The conversion of organic pollutants in waste salt to carbon quantum dots and study on its fluorescence quantitative detection on DMHF - Cao Lingyun; Fei Xuening; Bai Qiu; Li Meitong; Xie Yuhong; Yuan Wenjiao; Wei Feng (Journal of Environmental Chemical Engineering, 2026)

Enhanced wastewater treatment performance in a two-stage pyrite-based denitrifying deep bed filter - Jun Ding; Feng Ling; Shu-Yang Tian; Wen-Bo Xie; Xiao-Cai Chen; Li Yu; Xu-Mei Li; Fa-Zhi Xie; Wei-Hua Li; Tong-Zhan Xue; Hou-Yun Yang; Xian-Huai Huang (Journal of Environmental Chemical Engineering, 2026)

CCFA-Net: Cross-domain collaborative and foreground-aware for UAV object detection in hazy scenes - Feng Xie; Yuanyuan Li; Zhiqin Zhu; Penglong Li; Xin Huang; Yiyao An (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Unraveling the molecular mechanism of Citrus flavor (+)-nootkatone biotransformation from (+)-valencene by Pseudomonas sp. HNGD-T31 via 4D-DIA based proteomics - Xiao Li; Mengju Zhang; Yizhuo Liu; Ke Li; Yishang Wen; Yanli Xie; Jinchu Yang; Yingjie Feng; Feng Yang; Yongming Xu; Zhenzhen Huang (Food Bioscience, 2026)

Proanthocyanidin/laccase-mediated cross-linking enhances the structural stability and rheological properties of collagen solutions - Junhong Xie; Li Feng; Fanghui Deng; Wei Yue; Wei Liang; Qiannan Zhao; Wentao Ma; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2026)

Probing the evolution and roles of reactive species in piezo-catalytic uranium extraction with petaloid MoS2 - Ying Zheng; Zhe Gao; Chao Yang; Feng Li; Jixiang Xie; Xun Li; Keng Xuan; Yadan Guo; Wei Zhuang (Chemical Engineering Journal, 2026)

Integrated end-to-end continuous-flow platform for the process intensification and kilogram-scale production of TADF emitters - Xiaoyan Li; Shoujia Zhu; Ying Wei; Yang Li; Zheng Zhang; Hao Li; Yugang Chen; Yun Deng; Xinxin Han; Quanyou Feng; Linghai Xie (Chemical Engineering Journal, 2026)

Coping with the concurrent PM2.5 and ozone pollution in Southwestern China under the impact of cross-border transport of biomass burning - Mingya Xie; Puyu Lian; Fei Qiu; Jian Wang; Feng Xiang; Yuheng Chen; Anjie Yin; Jiaqi Li; Kaihui Zhao (Atmospheric Research, 2026)

A LINE-1 retrotransposon promotes SEMA3C expression as a cis-regulatory enhancer to sustain breast cancer stem cell survival - Qidong Xia; Jingwei Feng; Jiayao Pan; Wen Deng; Xiaoqi Weng; Jianhui Jiang; Lin Wang; Wenqian Xie; Yi Chen; Aiwei Bi; Jiang Li; Yiwen Lu; et al. (Science China Life Sciences, 2026)

Improving spatial resolutions of unmanned aerial vehicle hyperspectral images to predict grain yield and protein content in rice - Zhonglin Wang; Rong Hu; Mingming Hu; Huilai Yin; Tao Liu; Yufei Xie; Yangming Ma; Feng Yang; Feijie Li; Zhiyuan Yang; Yongjian Sun; Jun Ma (Precision Agriculture, 2026)

Full-Length Transcriptome Analysis of the Pituitary of Pre-Matured and Artificially Matured Female Japanese Eel (Anguilla japonica) - Yu Gao; Jiangling Li; Zhenguang Feng; Mingxi Huang; Wen Li; Ruihan Xu; Ruoxue Chen; Yu Ban; Jingjie Liang; Yan Huang; Yangjie Xie; Jianchun Chen; et al. (Journal of Ocean University of China, 2026)

Artesunate overcomes oxaliplatin resistance in colorectal cancer by inducing ferroptosis through inhibition of the CDK5/Nrf2/GPX4 pathway - Feng Lv; Xiao-huan Li; Si-qi Li; Hao-wei Deng; Hao-tang Wei; Ke-zhi Li; Ming-zhi Xie; Li-ye Xie; Shu-fang Ning; Bang-li Hu (Apoptosis, 2026)

Stepwise Gradient in Fundamental Individualised Niche Differentiation Across Soil Microbiomes - Huaiqiang Liu; Juan Xu; Yihui Guo; Zhenyuan Lei; Na Wang; Wenya Wei; Liping Qu; Minchun Li; Yarong Feng; Wei Xie (Molecular Ecology, 2026)
Individual microbes often respond differently to the same environment, yet the magnitude of such niche variation inherent to individuals remains unresolved and is anticipated to differ substantially from community‐level average responses. We conducted metagenomic binning on monthly time‐series soil samples from three sites across seasonal cycles. By considering 440,571 genes as dimensions of the fundamental individualised niche (FIN), we traced FIN trajectories of archaea and bacteria during warming, cooling, and turning periods. We found that neither mean temperature nor temperature difference had a significant effect on FIN breadth or overlap. Instead, we discovered a temporally constant, stepwise gradient of niche differentiation across taxonomic categories. At the interdomain level (Archaea vs. Bacteria), niche overlap is approximately 25%, rising to ~40% at the interphylum level and ~60% at the interorder level. This discontinuous gradient likely marks the limit boundaries of niche variation, is closely linked to functional synergy within FINs, and provides a preliminary comparable ecological carrying capacity for each niche step, particularly regarding the interdomain balance.

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Microscopic Hydraulic–Mechanical Coupling Fracturing Behavior and Failure Mechanisms of Reservoir Rocks - Zhi Zhao; Zhi-Hong Li; Yun-Gang Duan; Liang-Fu Xie; Zheng Li; Guo-Feng Yu; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2026)

Dietary creatine supplementation promoted growth performance, muscle growth and protein deposition in red swamp crayfish (Procambarus clarkii) fed with all-plant-protein diets - Xinyuan Li; Changchun Song; Shouqi Xie; Min Wan; Yangyang Liu; Chenxi Wang; Guogen Su; Feng Huang; Juan Tian (Aquaculture, 2026)

Temporal psychological and physiological responses to 120-hour isolation in an underground rescue chamber: A preliminary study - Jie Zhang; Ligang Tan; Xueliang Xu; Cuibin Xie; Xuanhui Xu; Zhizhong Li; Feng Wang (Tunnelling and Underground Space Technology, 2026)

AI-enhanced geomechanical modeling: A dynamic mining land subsidence prediction framework with geology-triggered rebalancing - Yongjie Li; Huiyong Yin; Ning Zhuang; Fangying Dong; Daolei Xie; Longxin Feng; Liwei Gong; Biao Li (Process Safety and Environmental Protection, 2026)

Foliar boron application modulates antioxidant enzymes and gene expression to alleviate Cd toxicity in winter wheat (Triticum aestivum L.) - Mengchan XIE; Yifan FENG; Chaoming MA; Hongen LIU; Zhaojun NIE; Wei GAO; Chang LI; Fuqing SUI; Peng ZHAO; Shiyu QIN (Pedosphere, 2026)

Combining puncture testing with discrete element simulation to predict the mechanical response of Rosa roxburghii - Feng Qian; Zhiping Xie; Nan Huang; Xing Li; Yuexin Zhong; Bing Sun; Shetan Hu; Sipeng Wang; Jinping Wu (Journal of Stored Products Research, 2026)

Elucidating the pyrolytic mechanisms of clean and safe gas generator 5-amino-1H-tetrazole/SiO2: A comprehensive kinetic and theoretical investigation - Si-Yuan Zhou; Xuan Li; Yuan-Hui Liu; Hao-Tian Zhou; Peng-Cheng Xi; Dan Zhang; Mi Li; Li-Feng Xie (Fuel, 2026)

Hulled Rice or husk? Synchrotron radiation XRF and deep learning approach for the determination of the geographical origin of Chinese rice samples - Xue Li; Chaojie Wei; Hongxin Xie; Haoxuan Luan; Jinying Wang; Yunbing Gao; Yanan Zhao; Wei Wang; Yu-Feng Li; Xuefei Mao (Food Chemistry, 2026)

Synergistic coupling of micellar confinement and interfacial adsorption for fabricating high-density spherical nickel (II) tricarbohydrazide perchlorate - Jie-xin He; Dong-xu Zhang; Feng-yi Xia; Ri-lige Su; Bo-bo Lu; Jia-ni Xie; Zi-jie Bi; Qian-you Wang; Li Yang (Chemical Engineering Journal, 2026)

Overt physiological responses and atypical behavior evoked in adult zebrafish in the novel tank test by two acute ‘survival’ stressors - Yunzhe Song; Jiahao Cui; Huiling Cai; Yunqian Zhang; Yixin Qin; Zhaowen Zhou; Haoyu Feng; Shulei He; Kai He; Yucheng Liu; Jiyi Wang; Jiayou Jiang; et al. (Behavioural Processes, 2026)

Moisture-dependent effects of PBS microplastics on cadmium mobility across soil aggregate fractions - Jiayi Xie; Ming Li; Zhiwang Feng; Rongxin Xie; Akaninyene Joseph; Yimin Wang (Journal of Soils and Sediments, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Alkali-activated mechanochemical decontamination of spent SCR catalysts: phase reconstruction for selective arsenic removal and vanadium recovery - Wenbin Hu; Congcong Li; Chenye Wang; Yan Li; Huiquan Li; Xinrui Wang; Feng Xie (Resources, Conservation and Recycling, 2026)

Integrated transcriptome and proteome analyses reveal that VvMYB61 and VvNAC29 orchestrate the reprogramming of lignin and flavonoid metabolism during postharvest senescence in grape berries - Yujia Liu; Yixin Dang; Tong Cheng; Jingwen Li; Mingxin Feng; Jinna Wu; Hefang Xie; Xin Yang; Tengfei Xu; Yulin Fang; Jiangfei Meng (Postharvest Biology and Technology, 2026)

Seasonal shifts in phytoplankton community assembly mediated by hydrological connectivity in a sluice-regulated distributary estuarine network—as a case in the Pearl River Estuary - Yanzi Cai; Xia Li; Guogui Chen; Yiliang Xie; Yujia Zhai; Tian Xie; Mingyu Wang; Fang Gao; Meili Feng; Ying Man; Baoshan Cui (Journal of Hydrology, 2026)

Cr-induced electronic reconstruction in Bi@BiOx catalysts promotes CO2-to-formate conversion - Xin Xie; Ze Gao; Linglong Hu; Daming Yang; Shuo Geng; Guilian Li; Ming Feng (Journal of Environmental Chemical Engineering, 2026)

Efficient roxarsone degradation via in-situ H2O2 generation through 2e−ORR over a Pd-Fe2O3 catalyst system - Ruibin Yang; Shuang Yao; Yijun Chen; Zhiwen Jiang; Hangyu Zhang; Ke Wang; Dapeng Li; Feng Liu; Feiyue Qian; Hailiang Yang; Sanjian Ma; Zixia Lin; et al. (Journal of Environmental Management, 2026)

Reutilization of digestate (residue and liquid) in the anaerobic digestion of sole corn stover: biochar preparation, methane performance and microbial responses - Haipeng Wang; Hao Sun; Sheng-Nan Zhuo; Jianrui Li; Zetang Chai; Jingwen Jia; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Journal of Environmental Management, 2026)

Waste agricultural mulch film-derived porous carbon-based catalysts for efficient industrial wastewater purification - Yimin Zhu; Xie Li; Tengfei Shao; Mingzhu Chen; Wen Wang; Zhaoxuan Feng; Shibing Bai; Weijun Zhen; Zhiqing Liu (Journal of Environmental Chemical Engineering, 2026)

Upgrading oxygen vacancy and reducibility for enhancing synchronous abatement of Hg0 and toluene over Co-Mn-Ce trimetallic oxides fortified biochar catalysts - Jiaqing Li; Yanyan Feng; Lei Gao; Ping Fang; Yunqing Wang; Caiting Li; Jinke Xie; Yukai Quan; Siyou Li (Journal of Environmental Chemical Engineering, 2026)

Evaluation of near infrared spectroscopy for direct detection of common microplastics contamination in camel Milk powder - Chunxu WAN; Yin LIU; Jing XIE; Feng CHEN; Huijie SHEN; Rong LI (Food Chemistry, 2026)

Bioactive biphasic textile scaffold for spatiotemporal regulation of inflammation and osteogenesis in enthesis healing during anterior cruciate ligament reconstruction - Meilin Song; Yanran Du; Haohan Li; Jiankun Feng; Xianchao Li; Yakun Huang; Yu-Qing Zhao; Chengbo Li; Huanhuan Yan; Dongsheng Li; Xiumei Mo; Guige Hou; et al. (Chemical Engineering Journal, 2026)

Functionalizing 3D DNA crystals by replacing non-framework strands - Xinyu Feng; Li Xu; Yunhan Zhang; Shuheng Wei; Dongbao Yao; Huichao Chen; Yueye Wang; Yujing Wu; Hui Hou; Xiao Cui; Qian Meng; Yue Gu; et al. (Chemical Engineering Journal, 2026)

A study on the physiological responses to nanoplastics and molecular mechanisms in Chlamydomonas reinhardtii - Ruru Li; Yang Liu; Ruikai Zhang; Binliang Wang; Junping Lv; Xudong Liu; Fangru Nan; Qi Liu; Jia Feng; Shulian Xie (Algal Research, 2026)

Quantifying Pollen‐Vegetation Relationships for Improved Palaeoenvironmental Reconstruction on the Tibetan Plateau - Di Hu; Gan Xie; Yi‐Feng Yao; David K. Ferguson; Yu‐Fei Wang; Jin‐Feng Li (Journal of Biogeography, 2026)
Aim Quantitative linkage between surface pollen relative abundance (RA) and source‐plant distribution is fundamental for fossil‐based vegetation and climate reconstructions. However, how phytogeographical patterns are translated into sedimentary pollen records under the extreme high‐altitude environments of the Tibetan Plateau (TP) remains a critical yet poorly understood issue. Here we integrate 3352 unique surface pollen spectra with MaxEnt‐modelled plant distribution ranges of 36 common taxa to quantify their spatial coupling across the TP and surroundings. Location Tibetan Plateau and surroundings. Taxon 36 common plant taxa (including 16 tree taxa and 20 herbaceous/shrub taxa). Method We integrated 3352 surface pollen samples with MaxEnt‐modelled plant distribution ranges to statistically evaluate the spatial representativeness and pollen thresholds. Furthermore, we applied the newly established tree pollen thresholds to fossil pollen records from the Lunpola Basin to refine its palaeoelevation estimates for the latest Oligocene‐earliest Miocene interval. Results Quantitative correlation analysis shows that for 16 tree taxa, including Pinus (threshold of 18%), Quercus (4.2%), Abies (1.9%), and Picea (2.6%), RA inside plant distribution ranges is significantly higher than outside, enabling robust presence/absence discrimination. In contrast, 20 herbaceous or shrub taxa (e.g., Artemisia , Cyperaceae, Ephedra ) display overlapping RA distributions regardless of plant occurrence; their pollen is therefore unreliable as a local vegetation proxy. The tree thresholds are generally lower than earlier estimates derived from forest‐cover proxies, highlighting the importance of using occurrence‐based vegetation data and extra‐regional pollen dispersal control on the TP. Moreover, the relationship between plant distribution and the sedimentary record is taxon‐specific: while tree taxa exhibit robust spatial coupling, the geographic boundaries of herbs are blurred in the pollen record. We applied a tree pollen threshold to refine the fossil pollen‐based altitude reconstruction, resulting in a palaeoelevation estimate of 3690 ± 200 m for the latest Oligocene‐earliest Miocene interval in the Lunpola Basin, with this estimate being closer to the reconstructed palaeoelevation via carbonate oxygen isotopes or other evidence. Main Conclusions This study established spatial coupling relationships for 36 plant taxa on the Tibetan Plateau using plant occurrence and surface pollen data. Results show that 16 tree taxa (e.g., Pinus , Quercus ) have clear pollen relative abundance thresholds enabling reliable inference of local plant presence, while 20 herbaceous and shrub taxa lack such thresholds due to complex environmental influences, and it demonstrates that reliable reconstruction of past vegetation and associated elevation/climate changes should focus on the well‐calibrated arboreal taxa while cautiously interpreting herb/shrub signals.

Dual-functional FeMgAl-LDH/peroxydisulfate system for simultaneous carbon and phosphorus recovery from sludge anaerobic fermentation - Dan Li; Yuxin Li; Wei Xia; Weixin Zhao; Xinhui Xia; Zixuan Zhao; Likui Feng; Heng Liang; Haijiao Xie; Liangliang Wei (Water Research, 2026)

USP13 exacerbates the malignant progression of cervical cancer by inhibiting ECT2 ubiquitination and degradation - Tingting Li; Xiulan Xiong; Tingting Xie; Wei Liu; Xuqin Feng; Silin Chen; Xin Hu; Rengui Li; Kaiwen Fu (Reproductive Biology, 2026)

Numerical study on calculation methods for longitudinal ship forces in a lock chamber - Wei Feng; Xiqin Ma; Peng Wu; Chunhang Xie; Qiulin Li (Ocean Engineering, 2026)

Microplastic-derived dissolved organic matter components determine Microcystis aeruginosa-bacteria interaction network and community assembly - Zongjie Xie; Huimin Li; Jia Feng; Shulian Xie; Yang Liu (Harmful Algae, 2026)

Cobalt-free iron-based perovskite oxides with nickel substitution as air electrodes for reversible protonic ceramic electrochemical cells - Rongwei Li; Yushi Feng; Jinghui Duan; Shengyuan Xie; Jiaan Jing; Yuanping San; Peng Su; Haoyuan Yin; Youngjin Kim; Jihaeng Yu; Fang Wang; Jingwei Li; et al. (Fuel, 2026)

Procyanidin C1 from hawthorn modulates metabolic-inflammatory axis to combat vascular senescence in atherosclerosis - Min Li; Jia-Yao Si; Peng-Fei Xie; Zhen-Jie Feng; Sheng-Jie Li; Feng Zhou; Jian-Mei Li (Food Research International, 2026)

Curdlan modulates potato starch gelatinization and gelation: Mechanisms of interaction, structural enhancement, and texture improvement in hydrogel foods - Yongxin Liu; Xinyi Li; Liya Chen; Fan Feng; Chang Sun; Yingchao Xu; Xinyu Sun; Man Li; Qingjie Sun; Xingfeng Xu; Fengwei Xie; Yanfei Wang (Food Hydrocolloids, 2026)

TRPA1 mediates ozone-induced murine model of COPD through the Wnt5a/GSK-3β/β-catenin pathway - Meiqin Xie; Qing Chang; Chenfei Li; Qi Liu; Jiali Weng; Yi Feng; Hai Zhang; Mengnan Li; Kian Fan Chung; Ian M. Adcock; Xiaoyun Fan; Feng Li (Environmental Pollution, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

The Spatial Hazard Early Warning Method for Coal Burst Based on Fusion of Multi-parameter Indicators - Shifeng He; Heping Xie; Minghui Li; Feng Cui; Jingyang Zhang; Jun Lu; Farui Shi (Rock Mechanics and Rock Engineering, 2026)

Effective cost control of Haematococcus pluvialis cultivation under pilot scale conditions: sustainable utilization of waste shells and safe nitrogen sources - Shuai Guo; Feng Li; Jun Wang; Lingkun Jing; Feng Pan; Dian Xie; Hongwei Ke; Chunhui Wang; Minggang Cai (Journal of Oceanology and Limnology, 2026)

Multi-Modal Fusion with Supervised Contrastive Learning Model for Early Alzheimer’s Disease Diagnosis and Multi-Modal Biomarker Identification - Xiaofeng Xie; Peng Xue; Yihao Guo; Huijuan Chen; Li Fan; Rongnian Tang; Zhenkai Xu; Xuanqi Wang; Tao Liu; Feng Chen (Interdisciplinary Sciences: Computational Life Sciences, 2026)

A novel strategy for improving canopy nitrogen density retrieval by deciphering saturation effects and vertical heterogeneity - Hongye Yang; Bo Ming; Chenwei Nie; Dayun Feng; Kexin Gao; Shang Gao; Jun Xue; Guoqiang Zhang; Peng Hou; Ruizhi Xie; Zhenhai Li; Xiuliang Jin; et al. (Computers and Electronics in Agriculture, 2026)

Organic chemicals of Arctic concern in Russian coastal seas - Xi-Ze Min; Xianming Zhang; Zhi-Yong Xie; Anatoly Nikolaev; Katrin Vorkamp; Jian-Min Ma; Lars-Otto Reiersen; Li Li; Ming-Hong Cai; Nan-Qi Ren; Yi-Fan Li; Zi-Feng Zhang; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Corrigendum to ‘Phlecarinatones H–O: Abietane-type diterpenoids from Phlegmariurus carinatus with proliferative inhibitory effect on glioma’ [Phytochemistry 232 (2025) 114356/PHYTO_114356] - Hua Wang; Qiang Wang; Yong-Hong Chen; Xi Chen; Dong-Kun Zheng; Zhen Xie; Du-Min Feng; Lin Liu; Jing Li; Yang Liu (Phytochemistry, 2026)

A novel solution pollination in orchards - Feiran Wang; Lixing Xie; Yao Zhou; Jiangrui Dai; Likai Feng; Guoli Zhang; Zongcai Zhu; Yancun Zhao; Baolian Tian; Xiuli Shi; Donglan Lv; Muhammad Imran; et al. (Journal of Cleaner Production, 2026)

Screening of activated carbon by machine learning and its synergistic ozone catalytic oxidation for the removal of organic compounds in concentrated brine - Weixing Zhang; Dongbei Yue; Deqian Liu; Xiuchun Li; Feng Lv; Zhicheng Cao; Liying Wei; Yongjun Wang; Yang Zhang; Zhucan Xie; Wei Xie; Dingcheng Liang (Journal of Environmental Chemical Engineering, 2026)

Fe-modified CoS2/ZnIn2S4 heterojunction for dual-driven photoactivation of peroxymonosulfate: Efficient degradation of antibiotics in water - Xiao Feng; Qiqi Gan; Zhongliang Li; Yunhong Zhao; Tengfeng Xie; Dejun Wang; Yanhong Lin (Journal of Environmental Chemical Engineering, 2026)

Formation mechanism of low signal-to-noise ratio seismic data in complex Karst areas - Feng Gao; Zhangqing Sun; Xiunan Fan; Zihao Li; Fuxing Han; Jipu Lu; Wenpan Cen; Mingchen Liu; Zhenghui Gao; Jiawei Xie (Journal of Applied Geophysics, 2026)

Study on the influence mechanism of lead carbonate salt compounds on the combustion behaviors of 5AT/Sr(NO3)2 solid propellant - Yuan-Hui Liu; Jiu Chen; Zhan-Jun Yang; Guang-Ling Chen; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Li-Feng Xie; Dan Zhang (Fuel, 2026)

Identification and anti-inflammatory characterization of two triterpene glycosides from boiling waste liquid: network pharmacology, molecular docking, and in vivo evaluation - Yuying Cao; Tong Wu; Jiaqing Li; Dandan Zhang; Chenglei Qu; Yaguang Shen; Chunmei Li; Jianhui Feng; Guantong Shi; Yongtao Jiang; Zeping Xie; Xinyan Liu; et al. (Food Research International, 2026)

A prior-knowledge-integrated downscaling approach for subsurface thermal structure reconstruction in the tropical Indian Ocean - Zhongkun Feng; Jifeng Qi; Bowen Xie; Yuan Cao; Delei Li; Chuanyu Liu; Baoshu Yin (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Multiple resonance thermally activated delayed fluorescence emitters containing novel S-based acceptor with narrowed FWHM and enhanced EQE - Xiao-Xue Xia; Guo Yuan; Feng-Ming Xie; Qiang Zhang; Yan-Qing Li; Ze Hua; Jian-Xin Tang; Xin Zhao (Chemical Engineering Journal, 2026)

Ultrahigh-responsive non-contact MXene-based flexible sensor: From real-time humidity sensing to smart healthcare applications - Hao-wen Zhang; Xiang Xu; Jie Lu; Wei-jin Li; Aming Xie; Hao Chen; Yang-sheng Wang; Ying Zhi; Zhe-sheng Feng; Yan Wang (Chemical Engineering Journal, 2026)

Li3N/Li2O-rich artificial SEI formed by in-situ dielectric barrier discharge plasma for lithium metal batteries - Peng Dong; Zhipeng Xie; Fupeng Li; Shengping Hou; Da Zhang; Weiyu Gao; Yong Lei; Bin Yang; Feng Liang (Chemical Engineering Journal, 2026)

Reductive Dechlorination of Trichloroethene by Carboxymethyl Cellulose Stabilized and Sulfidated Nanoscale Zero-Valent Iron: Effect of Humic Acid - Bo Chen; Qi Li; Yuhan Hang; Si Chen; Zihan Xie; Hao Yuan; Yadong Yang; Feng He (Water, Air, & Soil Pollution, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Fucoidan induces ferroptosis in colorectal cancer cells by regulating the SLC7A11/GPX4 signaling pathway and modulating metabolic pathways - Chengyu Yang; Chunqi Feng; Naiqi Zhang; Jia Feng; Shulian Xie; Xinghua Li; Qi Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Whole-body RNA Sequencing Analysis of the Post-larval Reveals the Sex-biased Gene and MiRNA in the Prawn Macrobrachium rosenbergii - Kun Xie; Yu-Meng Shi; Jin-Xia Yang; Jia-Yan Chen; Xu Huang; Xin-Yu Liu; Li-Ping Chen; Jie Chen; Chao-Ping Lu; Gao-Feng Qiu (Marine Biotechnology, 2026)

Reducing heat vulnerability in urban regions: a human settlement optimization approach in local climate zones - Y. Feng; J. Yang; Z. Li; X. Kang; Y. Zhang; P. Xie; Y. Wang; X. Xiao (International Journal of Environmental Science and Technology, 2026)

The effects of steel fiber content and thermal curing on the mechanical and durability properties of ultra-high performance concrete with iron tailings - Qiuming Li; Xiaoxin Feng; Gang Liu; Yuantao Xie; Penghui Chen; Zhelong Li (Innovative Infrastructure Solutions, 2026)

Molecular and functional characterization of IL-17R signaling pathway-related genes in cuttlefish Sepiella japonica: Identification, expression pattern and protein interaction - Xu Zhou; Jian-Jun Xie; Shu-Fan Yu; Shuang Li; Chang-Feng Chi (Aquaculture, 2026)

Disparities in bioaccumulation of chlorinated organic pollutants in O. bartramii and seawater from the Northwest Pacific Ocean: Compound – specific mechanisms and health risks - Ci Wang; Xinran Liu; Yitong Gao; Zilan Wu; Li Zhang; Jingqian Xie; Xinyu Tian; Feng Wu; Xiaojie Dai; Bilin Liu; Tian Lin (Marine Pollution Bulletin, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Flooding enhances species-patch network stability of macroinvertebrate community in low-connectivity oxbow lakes - Yiming Hou; Baozhu Pan; Zhiyuan Feng; Gang Li; Zhenyu Huang; Hongmin Xie; Gengnan Zhao (Journal of Hydrology, 2026)

Photochemical fate of carbamazepine-10,11-epoxide mediated by triplet-state dissolved organic matter in sunlit natural waters - Yuwei Xie; Yuefei Ji; Yuan Zhang; Yuhang Li; Wenzheng Chen; Xin Yu; Mingbao Feng (Journal of Hazardous Materials, 2026)

From waste lead-acid batteries to high-value polypropylene: Sustainable recovery and enhancement via decontamination and modification strategy - Lipeng Dong; Wenwu Zhi; Juanjuan Dong; Haihua Xie; Feng Li (Journal of Environmental Management, 2026)

Reducing the detection limit of the radon monitor with less humidity influence based on electrostatic collection method and CR-39 detector - Huiying Li; Ruomei Xie; Zhongkai Fan; Shicheng Luo; Feng Xiao; Jiulin Wu; Haibo Yi; Zhipeng Liu; Jiale Sun; Xinyue Yang; Xianfa Mao; Hongbo Xu; et al. (Journal of Environmental Radioactivity, 2026)

Occurrence, distribution, and risk assessment of antibiotics in post-harvest and drained ponds of Sheyang River estuary in Jiangsu Province: Implications for sustainable aquaculture management - Wenqian Shan; Shiya Gu; Wangrong Cui; Xinyun Feng; Xin Song; Jianwei Dong; Hui Xie; Da Li (Journal of Contaminant Hydrology, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Rational design of near-infrared carbon dots activated by mitochondrial viscosity in the living Parkinson's disease mouse - Jintao Zhang; Ying Ma; Linyu Feng; Minjie Xie; Yao Wang; Linjiao Yang; Yuying Cai; Xu Yu; Li Xu (Chemical Engineering Journal, 2026)

Facile synthesis of a high-efficiency phosphorus-based flame retardant enabling epoxy resin with superior flame retardancy, mechanical robustness, and transparency - Gonghao Chen; Feng He; Ruoxi Ye; Dan Xie; Fengqing Chen; Shi-Neng Li; Shiya Wu; Yintian Guo; Li Peng; Jinfeng Dai; Baiyu Jiang (Chemical Engineering Journal, 2026)

Salt stress estimation in pumpkin germplasm based on maximum likelihood statistical modeling of the leaf color space distribution - Zhang Xinyan; Liu Quan; Li Shuai; Feng Huaxiong; Luo Liang; Tan Zuojun; Shen Huan; Bie Zhilong; Xie Jing (Computers and Electronics in Agriculture, 2025)

Trans-2-decenal inhibits Phytophthora capsici by inducing ROS accumulation and mitochondrial dysfunction - Siyuan Xie; Lanning Wang; Jingkun Lv; Xiang Feng; Siyu Li; Haojie Tan; Chao Wang; Gang Wang; Hongjun Ge; Chun Xiao; Danyu Shen; Daolong Dou (Pesticide Biochemistry and Physiology, 2025)

Arrangement optimization of wingsails subject to complex mutual aerodynamic interference: A numerical study - Ranqi Ma; Daize Li; Rui Zhang; Feng Tian; Zhiqiang Tang; Jianlin Cao; Yuhao Xie; Zihan Jing; Jijun Chen; Xiaowu Li; Lianzhong Huang (Ocean Engineering, 2025)

Geochemical constraints on origin of high-silica granite and volcanic-plutonic connection: An example from Ningwu volcanic basin, Eastern China - Jiancheng Xie; Sujuan Zhou; Lin Qian; Qian Feng; Liu Yang; Shan Huang; Quanzhong Li; Jianmin Liu; Jun Yan (Lithos, 2025)

Biogeochemical processes play a decisive role in determining the fate of marine PAHs: A case validation with field measuring and modelling in the Beibu Gulf, South China Sea - Jingwen Shi; Mengyang Liu; Lingxin Chen; Jiandong Ye; Wupeng Xiao; Jinyan Xie; Fajin Chen; Yi-Fan Li; Xuke Chen; Yan Lin; Lin Zhang; Mingjun Feng; et al. (Journal of Hazardous Materials, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Rutile geochemistry records the evolution of ore-forming fluid in the Sizhuang gold deposit, Jiaodong Peninsula, Eastern China - Dong Xie; Xue Gao; Sirui Wang; Xiangdong Liu; Ligong Wang; Wei Yang; Kexin Li; Zhenjun Liu; Tao Feng; Kehui Wu (Journal of Asian Earth Sciences, 2025)

Effect of edible ethanol-induced redistribution of gluten proteins on fresh noodle quality and starch digestibility - Xianyu Cao; Kun Feng; Yishu Wang; Yanfei Wang; Chuanwu Han; Meng Ma; Qingjie Sun; Fengwei Xie; Man Li (Food Chemistry, 2025)

Differentiating volatile compounds in soy sauce that regulate the attractiveness of flesh flies (Parasarcophaga dux) - Shuxing Zhou; Chunlin Li; Li Li; Feng Xie; Karyne M. Rogers; Yuwei Yuan; Jun Huang (Food Chemistry, 2025)

The key role of Cytochrome P450 and ALDH in citrus flavor (+)-valencene biotransformation to (+)-nootkatone with Yarrowia lipolytica D21173 - Xiao Li; Gang Fan; Yanli Xie; Jinchu Yang; Yingjie Feng; Siyi Pan; Linhua Huang; Guijie Li; Yujiao Cheng (Food and Bioproducts Processing, 2025)

Top-down inversion of urban-scale sectoral methane (CH4) emissions and their response to environmental drivers - Wenxin Zhao; Zhiye Xia; Yanqing Xu; Kenan Li; Ziheng Huang; Feng Xie; Yuchen Li; Chao Li (Atmospheric Environment, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Selenite versus selenium nanoparticles in foliar application: enhancing alfalfa (Medicago sativa L.) and Bacillus subtilis PSL-1 mediated remediation of pyrene-contaminated soil - Hongguan Xie; Lian Gong; Shiwei Lei; Shida Li; Yuxin Feng; Lin Liao; Yue Wang; Kongxi Wang (Environmental Geochemistry and Health, 2025)

Provenance and geogenic modes of high-fluoride groundwater occurred in various sedimentary environments: constraints of hydrogeology and hydrogeochemstry - Guojie Feng; Zhiqin Li; Chunli Su; Xianjun Xie; Weili Ge; Yiqun Gan; Zhaohui Luo; Kunfu Pi; Hongjie Pan; Yanhui Gao; Yanmei Yang (Applied Geochemistry, 2025)

CPT1A facilitated ferroptosis by forming feedback loop with Nrf2 via PI3K/AKT pathway in colorectal cancer - Xiao-huan Li; Feng Lv; Si-qi Li; Hao-wei Deng; Li-ping Tang; Ke-zhi Li; Li-ye Xie; Bang-li Hu; Shu-fang Ning (Apoptosis, 2025)

Analysis of hydraulic response characteristics of reservoir bank slope under the action of reservoir water level rise and fall - Shu-Jun Ju; Ming-Li Xie; Neng-Pan Ju; Liang Duan; Ming-Cheng Jiang; Yu-Feng He (Applied Geophysics, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Implications of Flume Simulation for the Architectural Analysis of Shallow-Water Deltas: A Case Study from the S Oilfield, Offshore China - Lixin Wang; Ge Xiong; Yanshu Yin; Wenjie Feng; Jie Li; Pengfei Xie; Xun Hu; Xixin Wang (Journal of Marine Science and Engineering, 2025)
The shallow-water delta-front reservoir in Member II of the Oligocene Dongying Formation (Ed2), located in an oilfield within the Bohai Bay Basin, is a large-scale composite sedimentary system dominated by subaqueous distributary channels and mouth bars. Within this system, reservoir sand bodies exhibit significant thickness, complex internal architecture, poor injection–production correspondence during development, and an ambiguous understanding of remaining oil distribution. To enhance late-stage development efficiency, it is imperative to deepen the understanding of the genesis and evolution of the subaqueous distributary channel–mouth bar system, analyze the internal reservoir architecture, and clarify sand body connectivity relationships. Based on sedimentary physical modeling experiments, integrated with core, well logging, and seismic data, this study systematically reveals the architectural characteristics and spatial stacking patterns of the mouth bar reservoirs using Miall’s architectural element analysis method. The results indicate that the study area is dominated by sand-rich, shallow-water delta front deposits, which display a predominantly coarsening-upward character. The main reservoir units are mouth bar sand bodies (accounting for 30%), with a vertical stacking thickness ranging from 3 to 20 m, and they exhibit lobate distribution patterns in plan view. Sedimentary physical modeling reveals the formation mechanism and stacking patterns of these sand-rich, thick sand bodies. Upon entering the lake, the main distributary channel unloads its sediment, forming accretionary bodies. The main channel then bifurcates, and a new main channel forms in the subsequent unit, which transports sediment away and initiates a new phase of deposition. Multi-phase deposition ultimately builds large-scale lobate complexes composed of channel–mouth bar assemblages. These complexes exhibit internal architectural styles, including channel–channel splicing, channel–bar splicing, and bar–bar splicing. Reservoir architecture analysis demonstrates that an individual distributary channel governs the formation of an individual lobe, whereas multiple distributary channels control the development of composite lobes. These lobes are laterally spliced and vertically superimposed, exhibiting a multi-phase progradational stacking pattern. Dynamic production data analysis validates the reliability of this reservoir architecture classification. This research elucidates the genetic mechanisms of thick sand bodies in delta fronts and establishes a region-specific reservoir architecture model. This study clarifies the spatial distribution of mudstone interlayers and preferential flow pathways within the composite sand bodies. It provides a geological basis for optimizing injection–production strategies and targeting residual oil during the ultra-high water-cut stage. The findings offer critical guidance for the efficient development of shallow-water delta front reservoirs.

Versatile platforms based on HPTLC: Multimodal and green solutions for food and herbal quality assurance - NaNa Feng; YuYing Song; YuanYuan Li; XinYi Cheng; QingYa Yu; JingQiu Shi; HuiMing Gao; JiHang Xie; Qian Zhang; YiSheng Chen; Ce Tang; Yi Zhang (Trends in Food Science & Technology, 2025)

Synchronized lake-vegetation dynamics under climate change in arid central Asia - Yanan Su; Shengqian Chen; Xin Li; Tingting Xie; Min Feng; Fahu Chen (Science Bulletin, 2025)

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

Rational design of an ultra-high-gain MoS2 phototransistor enabling room-temperature detection of few-photon signals and attomolar-level immunosensing - Zhengdao Xie; Yun Hui; Wenhua Zhou; Shengxuan Xia; Yawei Lv; Liwei Ouyang; Yang Chai; Xingqiang Liu; Bei Jiang; Chang Liu; Sen Zhang; Chenchen Chu; et al. (Science Bulletin, 2025)

Nonlinear trajectory tracking control of UVMS with compositing fuzzy disturbance observer and robust state-dependent Riccati equation - Qirong Tang; Yuanjie Di; Tong Li; Yuanzhe Cui; Zongwu Xie; Linlin Feng; Min Yu (Ocean Engineering, 2025)

Latest Pleistocene to mid-Holocene vegetation changes revealed by multi-proxy analyses at Lop Nur in the eastern Central Asia - Yi-Feng Yao; Kai-Qing Lu; Feng Qin; Guo-An Wang; Qin-Min Yang; Xin-Ying Zhou; David K. Ferguson; Gan Xie; Jin-Feng Li; Bin Sun; Stephen Blackmore; Yu-Fei Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Zircon records water-fluxed melting in origin of W-rich magma: Insights from the Yangchuling porphyry W Mo deposit, South China - Qingqing Yin; Juxing Tang; Jingjing Dai; Inna Safonova; Faqiao Li; Hao Sun; Yumin Xu; Xinkui Xiang; Jinling Xie; Baoping Gan; Bohao Yin; Zhongchao Zheng; et al. (Lithos, 2025)

Experimental investigation and numerical simulation on Multiphysics coupling of shale under laser irradiation - Mingxin Liu; Jing Xie; Yuze Du; Zeyu Zhu; Li Ren; Bengao Yang; Gan Feng; Yanan Gao; Mingzhong Gao (International Journal of Rock Mechanics and Mining Sciences, 2025)

Altitude weakens the drought resistance-resilience tradeoff across northern ecosystems - Yuting Yang; Xie He; Yunfei Feng; Ben Niu; Jianshuang Wu; Meng Li (Global and Planetary Change, 2025)

Coulomb repulsion strategy synergizes electronic effects to facilitate efficient H2 production from alkaline seawater - Kuo Wei; Mengdi Li; Feng Chen; Lu Zhou; Ruijia Xie; Congyi Zhao; Liyuan Chen; Yuanzhe Wang; Faming Gao (Fuel, 2025)

Transformation of landfill leachate into in-situ iron-carbon galvanic stabilizer for effective remediation of mercury-contaminated soils: a sustainable solution - Dongping Song; Tao Huang; Chenglong Wang; Yun Xia; Xiaolong Sun; Chong Luo; Weihua Liu; Shihong Xie; Yuxuan Feng; Kai Chen; Jialin Cui; Shouze Li (Environmental Research, 2025)

Multi-source apportionment of soil heavy metals and spatial heterogeneity of associated risks in overlapping zones with high geological background and mining-smelting activities - Chaobo Wang; Yuezhong Chen; Yixi Xie; Xingyu Feng; Kangkang Wu; Xuexian Li; Pan Wu (Environmental Pollution, 2025)

Microplastic exposure drives divergent assembly mechanisms in riverine microorganisms: Poly(butylene adipate-co-terephthalate) triggers metabolic shifts vs polyethylene-enhanced network complexity - Huimin Li; Zongjie Xie; Xiding Wang; Ziyan Zhao; Shulian Xie; Jia Feng; Yang Liu (Environmental Pollution, 2025)

Synergistic NH3 and N2O mitigation in rice paddies via subcritical thermochemical conversion of livestock manure: Unraveling subcritical fecal fertilizer-mediated biochemical pathways - Yuanyuan Feng; Lisha Wang; Yuanhao Liu; Huifang Xie; Jing Li; Yahui Ji; Shiying He; Xi Zhang; Haibin Fu; Yanfang Feng; Gerrard Eddy Jai Poinern; Lihong Xue (Chemical Engineering Journal, 2025)

Modulating the redox states in a 3D conductive MOF for sweat ascorbic acid monitoring - Wei-Qi Wang; Han Xie; Feng Cheng; Ting Zou; Ke-Qiang Xu; Amare Aregahegn Dubale; Wen-Hui Zhang; Ning Xu; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2025)

Enhanced oxidative stability of EGDE/PEI@MX560 adsorbent for CO2 capture: Anti-oxidation mechanism of double epoxide crosslinking - Fangzheng Zou; Hanjun Liu; Zhijian Xie; Jiguang Li; Heijin Chen; Xuehua Shen; Zuotai Zhang; Feng Yan (Chemical Engineering Journal, 2025)

“d-f electron ladder” accelerates dynamic reconstruction of bimetallic sulfides for efficient oxygen evolution in seawater electrolysis - Kuo Wei; Ruijia Xie; Mengdi Li; Feng Chen; Lu Zhou; Yaxu Zhao; Guiqing Xu; Yuanzhe Wang; Ying Meng; Faming Gao (Chemical Engineering Journal, 2025)

Signal molecule-mediated algae-bacteria interactions and membrane-enabled separation synergize wastewater bioremediation - Kai-Yuan Li; Jin-Long Zhou; Ashiwin Vadiveloo; Jia-Nan Li; Dan Zhou; Jia-Ming Wang; Ci Zhang; Yi-Lin Xie; Dong-Zhi Chen; Feng Gao (Chemical Engineering Journal, 2025)

Enhancing E. coli removal in mesophilic anaerobic digestion: New insights from inoculum comparison and metagenomic analysis - Haipeng Wang; Zetang Chai; Jianrui Li; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Bioresource Technology, 2025)

Comprehensive analysis of prevailing weather patterns and high-impact typhoon tracks to reveal where and how tropical cyclone affects regional ozone pollution in the Yangtze River Delta region, China - Mengzhu Xi; Yi Luo; Yichen Li; Danyang Ma; Lingyun Feng; Shuxian Zhang; Shitong Chen; Min Xie (Atmospheric Environment, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

LW-MS-LFTFNet: A Lightweight Multi-Scale Network Integrating Low-Frequency Temporal Features for Ship-Radiated Noise Recognition - Yu Feng; Zhangxin Chen; Yixuan Chen; Ziqin Xie; Jiale He; Jiachang Li; Houqian Ding; Tao Guo; Kai Chen (Journal of Marine Science and Engineering, 2025)
Ship-radiated noise (SRN) recognition is vital for underwater acoustics, with applications in both military and civilian fields. Traditional manual recognition by sonar operators is inefficient and error-prone, motivating the development of automated recognition systems. However, most existing deep learning approaches demand high computational resources, limiting their deployment on resource-constrained edge devices. To overcome this challenge, we propose LW-MS-LFTFNet, a lightweight model informed by time-frequency analysis of SRN that highlights the critical role of low-frequency components. The network integrates a multi-scale depthwise separable convolutional backbone with CBAM attention for efficient spectral representation, along with two LSTM-based modules to capture temporal dependencies in low-frequency bands. Experiments on the DeepShip dataset show that LW-MS-LFTFNet achieves 75.04% accuracy with only 0.85 M parameters, 0.38 GMACs, and 3.27 MB of storage, outperforming representative lightweight architectures. Ablation studies further confirm that low-frequency temporal modules contribute complementary gains, improving accuracy by 2.64% with minimal overhead. Guided by domain-specific priors derived from time-frequency pattern analysis, LW-MS-LFTFNet achieves efficient and accurate SRN recognition with strong potential for edge deployment.

Chiral switching of many-body steady states in a dissipative Rydberg gas - Chongwu Xie; Konghao Sun; Kang-Da Wu; Chuan-Feng Li; Guang-Can Guo; Wei Yi; Guo-Yong Xiang (Science Bulletin, 2025)

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

Biodegradable microplastics amplify antibiotic resistance in aquaculture: A potential One Health crisis from environment to seafood - Shiyu Xie; Licheng Peng; Zhenchao Zhou; Nuohan Xu; Siqi Li; Yujie Feng (Journal of Hazardous Materials, 2025)

Ferrocene-based metal-organic frameworks for electrochemically synergistic conversion and capture of arsenic from water - Xueting Feng; Junfeng Li; Lijuan Yi; Dongbao Song; Junyang Xiao; Jiankang Wang; Xi Xie; Quanli Zong (Journal of Environmental Chemical Engineering, 2025)

Impacts of synoptic weather patterns on Hefei's ozone in warm season and analysis of transport pathways during extreme pollution events - Feng Hu; Pinhua Xie; Jin Xu; Ang Li; Yinsheng Lv; Zhidong Zhang; Jiangyi Zheng; Xin Tian (Journal of Environmental Sciences, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

Recyclable, photothermal dual responsive shape memory epoxy vitrimers containing dynamic oxime-carbamate bonds, dynamic ester bonds and hydrogen bonds based on vegetable oil - Xiaoqi Xie; Shouhai Li; Mei Li; Haiyang Ding; Mingtao Lin; Lina Xu; Na Yao; Qingyuan Feng; Xiaohua Yang; Xiao Feng; Yan Zhang; Yi Xing (Chemical Engineering Journal, 2025)

Dipole-unit mediated Co-solute engineering to construct nanodomain electrolytes for highly reversible and shuttle-free ZnI2 batteries - Renwu Feng; Qingying Li; Haozhen Dou; Yihan Xie; Jinliang Yan; Mi Xu; Dan Luo; Zhile Yang; Yuanjun Guo; Xinru Wu; Xin Wang; Zhongwei Chen (Chemical Engineering Journal, 2025)

Biochar alleviates adverse effects of polystyrene microplastics on anaerobic digestion performance of food waste and antibiotic resistance gene propagation - Feng Wang; Ye Li; Linjie Zhang; Yinglong Su; Yan Zhang; Seungkwan Hong; Min Zhan; Bing Xie (Bioresource Technology, 2025)

Global burden and characterization of hypertriglyceridemia-induced acute pancreatitis: results from a systematic review and a multi-center cohort study - Zhengyang Fan; Yuelun Zhang; Jianing Li; Wenhua He; Xiaoyin Bai; Yanna Cai; Naishi Li; Feng Xie; Li Wen; Venkata Sandeep Akshintala; Yin Zhu; Dong Wu (Science China Life Sciences, 2025)
To compare and characterize hypertriglyceridemia-induced acute pancreatitis (HTG-AP) across the geographical regions, we conducted a systematic review and a multi-center cohort study. We conducted a systematic review and random effects meta-analysis of studies reporting HTG-AP. Also, we separately characterized HTG-AP in a multi-center retrospective cohort study involving eight centers in China. The key outcomes of interest included the pooled proportion of HTG-AP and its severity parameters after adjusting for the effect of confounding factors through logistic regression. Our systematic review identified 110 studies from 15 countries accounting for 3,057,428 participants (35% female, median age 50 years). The pooled proportion of HTG-AP was 11.6% globally while the Eastern and Western countries reported the proportions as 16.3% and 5.4%, respectively ( P <0.01). The pooled mortality rate was remarkably higher in Eastern countries (4.1%) than in Western countries (1.0%) ( P <0.01). 3,224 participants (37% female, median age 48 years) were included in our multi-center cohort study, and the proportion of HTG-AP was much higher at 35.9% with a nearly three-fold higher mortality rate compared with acute pancreatitis (AP) due to other etiologies (odds ratio (OR): 2.77, 95% confidence interval (CI): 1.60 to 4.81). The proportion of patients with HTG-AP is remarkably higher in Eastern countries, particularly China, than in Western countries. Furthermore, compared with other causes of AP, HTG-AP has a poorer prognosis and may warrant aggressive management.

Integrin α6 Targeted Tumor Theranostics - Xinling Li; Kaili Xie; Qiaoli Wang; Jiacong Ye; Wenbiao Zhang; Jie Yang; Musheng Zeng; Guokai Feng (Phenomics, 2025)

Unveiling Moxibustion's Impact on AD Mice Learning and Memory: Role of Mitochondrial Respiratory Chain Complex I Subunit in the Hippocampus - Yuan Shen; Hong-Ying Li; Qing-Qing Yang; Ke Zhang; Shu-Qing Liu; Ning Zhang; Chen-Yu Li; Shu-Guang Yu; Lu-Shuang Xie; Qiao-Feng Wu (Molecular Neurobiology, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Host Egg Preference and Density-Dependent Parasitism of Telenomus remus in Spodoptera litura and Spodoptera frugiperda Eggs - Ibrahim Osman; Zhimin Wang; Ertao Li; Honglin Feng; Jiao Yin; Gemei Liang; Zhengling Liu; Dekai Ning; Kebin Li; Yonghui Xie (Neotropical Entomology, 2025)

Chronic low-level exposure to Pb, Hg, and Cd mixture triggers brain premature aging in rat - Jie Xie; Lu Ouyang; Jiajun Li; Shuo Yang; Qi Li; Yue Li; Lingyu Yan; Yihong Fu; Qijun Li; Yuting Xia; Xinling Chen; Ziyang Fu; et al. (Toxicology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Tracing mercury sources and transfer pathways in Pacific and Atlantic Ocean tuna and billfish using mercury stable isotopes - Ruo Lan; Feng Wu; Jingqian Xie; Shaochen Yang; Xingyu Liang; Zhiyang You; Ping Li; Runsheng Yin; Xinbin Feng (Journal of Hazardous Materials, 2025)

Irradiation-dependent properties, photodegradation dynamics, and molecular evolution mechanism of biochar-derived dissolved black carbon - Tingting Li; Fanhao Song; Mingqi Ruan; Yuhan Cao; Yao Zhao; Weiying Feng; Nuo Chen; Jin Hur; Fazhi Xie; Fengchang Wu (Journal of Hazardous Materials, 2025)

Dynamic changes in metabolic compounds and their effects on flavor quality of Fuliang black tea and green tea during processing - Fang Dong; Hongkun Lai; Qifang Sun; Wenjie Yu; Gaowei Zhang; Shijuan Du; Shuai Zhuang; Tao Liu; Yan Li; Xiaoqing Fan; Feng Xie; Liping Luo (Food Bioscience, 2025)

Synergistic alloy interface and Zn(002) texture for stable Zn anodes in aqueous zinc ion batteries - Wenwen Ma; Jiahui Zhou; Chen Xie; Yang Mei; Feng Wu; Renjie Chen; Li Li (Chemical Engineering Journal, 2025)

Lanthanum-based hydrogels for simultaneous removal of trace phosphorus and algae - Yan Zhang; Qian Xie; Cheng Fu; Zhen Qiu; Zechao Zhuang; Ting Wang; Yunying Fang; Yongfu Li; Yanjiang Cai; Huajun Feng; Bing Yu (Chemical Engineering Journal, 2025)

Exploring the masking of berberine bitterness by natural polysaccharides based on a “net-hook” dual-effect mechanism - Min Qiu; Jiaxin Li; Huijuan Xie; Jiamin Feng; Qi Huang; Yin Tian; Haozhou Huang; Li Han; Dingkun Zhang (Carbohydrate Polymers, 2025)

Decomposition of Nelumbo nucifera Litters with Three Initial Biomasses Significantly Affected the Microbial Community and Assembly in Sediment - Fan Wu; Deyou Feng; Yanan Li; Xin Liu; Xiaohong Zhou; Sisi Xiao; Qingjie Xie (Current Microbiology, 2025)

Responses of multi-trophic microbial communities to altered precipitation affected soil respiration in coastal wetlands - Yuqi Zhou; Xinge Li; Shuzhen Li; Xiongfeng Du; Zheng Zhang; Zhaojing Zhang; Kai Feng; Xi Peng; Wen Song; Song Gu; Pengpeng Duan; Baohua Xie; et al. (Applied Soil Ecology, 2025)

Procyanidin B2 mitigate asthmatic airway remodeling by inhibiting TGF-β1-induced airway smooth muscle proliferation through ROS signaling - Wenyan Liang; Mingzhen Zhang; Hongyu Wang; Ling Feng; Dengke Li; Ruizhi Hao; Weiping Xie; Xiaoning Zeng; Yuan Ma (Tissue and Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Longitudinal transport of net suspended sediment in the river-dominated Modaomen Estuary of the Pearl River: Effects of river, tide, and mouth bar - Xinran Li; Feng Liu; Hao Zou; Chao Tan; Jie Huang; Sihao Mo; Haiwei Li; Rongyao Xie; Heng Wang (Marine Geology, 2025)

Life-long impacts of nanoplastics to rice plant (Oryza sativa L.): Decreased grain yield with perturbed metallome and soil microbiome - Hongxin Xie; Xuejia Wang; Liwei Cui; Rui Chen; Rui Zhao; Yang Yu; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2025)

The potential electrical transmission mechanism of strengthening petroleum hydrocarbon biodegradation by KOH-modified biochar - Wen Li; Quanwei Song; Jufeng Li; Xianyuan Du; Jiacai Xie; Zhongyuan Li; Xing Chen; Nan Zhao; Feng Ju; Hao Ling (Journal of Environmental Chemical Engineering, 2025)

A scalable and robust MOF@PAN nanofibers with acid−base dual surface sites as an excellent catalyst for the cycloaddition of epoxides with CO2 - Weiqin Xu; Xiangwen Li; Huahua Tang; Weixi Zhang; Jiao Li; Xu Feng; Dien Huang; Shenyi Liang; Yinli Dai; Haoyuan Xie; Wenting Liu; Shengrun Zheng (Journal of Environmental Chemical Engineering, 2025)

Influence of the ratio of fresh cream to anhydrous milk fat on the quality and flavor of recombined protein-based emulsions - Wenhui Feng; Yunna Wang; Ning Ju; Yali Chen; Xiaolu Geng; Yonglong Yang; Zhiwei Li; Wentao Qian; Jiaping Lv; Ning Xie; Xiaoyang Pang; Shuwen Zhang (International Dairy Journal, 2025)

Selective indium extraction from zinc oxide dust leachate by microwave-assisted solvent extraction with P507 and stripping with HCl: Thermodynamics and kinetics - Shiju Li; Haibei Wang; Shengdong Wang; Feng Xie; Xudong Sun (Hydrometallurgy, 2025)

Tracking the gastrointestinal fate and prebiotic effect of ellagic acid-rich fruit byproducts: A comprehensive evaluation - Zhike Xie; Feng Chen; Pei Li; Yawen Xiao; Zheng Ruan (Food Chemistry, 2025)

Mechanistic insights into the combustion behaviors of 5AT/Sr(NO3)2 solid propellant induced by additives (Cu2(OH)2CO3 and Cu(OH)2)) - Jiu Chen; Guang-Ling Chen; Yuan-Hui Liu; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Guang-Cheng Yang; Li-Feng Xie; Dan Zhang (Chemical Engineering Journal, 2025)

Bisulfite-free whole-genome mapping of 5-methylcytosine at single-base resolution by NTD-seq - Min Wang; Neng-Bin Xie; Fang-Yin Gang; Shan Zhang; Li Zeng; Tong-Tong Ji; Jun Xiong; Xia Guo; Ying Hao; Yu Liu; Bi-Feng Yuan (Science China Life Sciences, 2025)

Key Controlling Factors of Hydrocarbon Accumulation of Fine-Grained Mixed Sequence in a Saline Lacustrine Basin: An Integrated Research of Petroleum System in the Northwestern Qaidam Basin, Qinghai–Tibet Plateau - Dehao Feng; Chenglin Liu; Jixian Tian; Minjunshi Xie; Hongliang Huo; Taozheng Yang; Guoxiong Li; Yubo He (Natural Resources Research, 2025)

Efficient Sulfamethoxazole Removal by an Isolated Strain Microbacterium esteraromaticum S13 - Guihua Leng; Yanlan Wen; Feng Zhang; Leli Wang; Hangtian Yan; Meng Zhang; Jun Li; Xingchen Li; Lei Zhao; Bingxing Xie; Jinhua Kang; Jingbai Wen (Current Microbiology, 2025)

Calcium-O-Sr-Nd isotope evidence for the origin of REE-bearing carbonatite from metasomatized lithospheric mantle without recycled carbonate - Xing-Hui Li; Ming-Cai Xie; Kui-Feng Yang; Kan Li; Chun-Ming Han; Hai-Dong She; Gai-Zhong Liang; Xiao-Chun Li; Hong-Rui Fan (Contributions to Mineralogy and Petrology, 2025)

Heterogeneity in the seroprevalence of hepatitis E virus among hospital attendees: a retrospective study in Shanghai, China - Jie Lu; Qing Li; Chenxi Zhang; Ziqiang Li; Qing Guo; Zhujun Cao; Yu-Feng Yao; Qing Xie (Infectious Diseases, 2025)

Encephalomyocarditis virus non-structural protein 2C induces the degradation of NDP52 autophagy protein to promote its own survival - Rongqian Mo; Rongrong Cheng; Pingan Dong; Tingting Ma; Yaxin Zhang; Jingying Xie; Shasha Li; Huixia Li; Adi Idris; Xiangrong Li; Ruofei Feng (Veterinary Microbiology, 2025)

Gaining water bodies by climate change benefits water crisis mitigation in central Asia - Yanan Su; Shengqian Chen; Yijie Sui; Xin Li; Jinhao Xu; Xianghong Che; Tingting Xie; Jianhui Chen; Yongwei Sheng; Min Feng; Fahu Chen (Science Bulletin, 2025)

Transcriptome sequence reveal the roles of MaGME777 and MabHLH770 in drought tolerance in Musa acuminata - Yuchen Wei; Jingfang Shi; Xueyi Xie; Feng Zhang; Huizhen Dong; Yaoyao Li; Fangcheng Bi; Xiaosan Huang; Tongxin Dou (Plant Science, 2025)

Attention-enhanced deep learning model for reconstruction and downscaling of thermocline depth in the tropical Indian Ocean - Zhongkun Feng; Jifeng Qi; Delei Li; Bowen Xie; Guimin Sun; Baoshu Yin; Shuguo Yang (Ocean Modelling, 2025)

Health risks of ambient polycyclic aromatic hydrocarbons based on the prediction of their gas-phase concentrations in the central Yangtze River Delta, China: Regional and time-resolved variability - Wanqing Qi; Wei Feng; Xiangyu Zhang; Guihong Dong; Guofeng Shen; Zhijuan Shao; Ke Li; Hong Liao; Yuhang Wang; Mingjie Xie (Journal of Hazardous Materials, 2025)

Characterization of differences in physicochemical properties, volatile organic compounds, and vitro digestion properties of turnips by inoculation of lactic acid bacteria - Miao Cui; Yun Xie; Junbo Zhang; Jie Feng; Yiwen Chen; Yongkang Li; Yue Hu; Jianming Niu; Weidong Cheng; Feifei Gao (Food Bioscience, 2025)

Preparation of ultramicroporous carbon for gas adsorption through oxygen-rich precursor-enhanced chemical activation - Jingyu Li; Xiaoxiao Meng; Wei Zhou; Yulin Feng; Junfeng Li; Naiyuan Xue; Liang Xie; Zheyu Liu; Jihui Gao; Fei Sun; Guangbo Zhao (Environmental Research, 2025)

Corrosion fatigue degradation of FRP tendon after acidic corrosion coupling with sustaining/fatigue loading - Xia Liu; Xin Wang; Jingyang Zhou; Feng Li; Jiazhan Xie; Zhishen Wu (Engineering Structures, 2025)

Fabrication of graphene-PEI composite membrane by supercritical CO2 exfoliation for efficient nanofiltration performance - Lin Li; Kunpeng Yu; Jing Xie; Haixin Sun; Tong Feng; Qinqin Xu; Jianzhong Yin (Chemical Engineering Journal, 2025)

Sediment hardening changes the physicochemical characteristics and microbial diversity of sediment and has potential effects on submerged macrophytes - Chuanxin Chao; Xiaorong Chen; Shen Gong; Feng Li; Zhengmiao Deng; Yeai Zou; Yonghong Xie (Plant and Soil, 2025)

Rakicidin J and K, two cytotoxic and antibacterial cyclic depsipeptides from the marine bacterium Micromonospora chalcea - Li Chen; Lijun Xie; Jian Zhou; Dongsheng Fang; Honglei Jiang; Wei Liu; Yuqiu Ye; Wei Zhao; Hong Jiang; Feng Lin (Natural Product Research, 2025)

Corrigendum to “Hippocampal MEF2C phosphorylation mediates synaptic plasticity in lead-induced learning and memory impairments” [Toxicology 512 (2025) 154082] - Shuo Yang; Yanhui Zhu; Jinmei Xiao; Lingyu Yan; Xuebing Zhuang; Qi Li; Yue Li; Jie Xie; Guihua Du; Fankun Zhou; Guangqin Fan; Chang Feng (Toxicology, 2025)

Partially oxidized cobalt-based metal-organic frameworks for peroxymonosulfate activation: An unusual strategy for naphthalene degradation with mechanistic and DFT insights - Ze Li; Qiyan Feng; Andy Baker; Haijiao Xie (Process Safety and Environmental Protection, 2025)

Enrichment and characterization of anaerobic ammonium oxidation coupled with iron reduction (Feammox) by anaerobic digestion and conventional activated sludges - Danyang Zhu; Hui Gong; Siyuan Diao; Xiankai Wang; Xiang Chen; Peng Li; Bin Dong; Li Xie; Jacek Makinia; Xueyuan Qiao; Feng Liu; Xiaohu Dai (Journal of Environmental Chemical Engineering, 2025)

Triaxial unloading effects on pre-holed sandstone energy characteristics and damage evolution mechanism: Comparative analysis of diffrent borehole bottom locations - Wenpu Li; Yaoguang Chen; Guorui Feng; Xingxing Xie; Minda Zhang; Zhiyuan Tian; Huan Zhang; Tao Wang; Ruiqing Hao; Yun Bai (Geomechanics for Energy and the Environment, 2025)

Experimental study on the reliability of Pt/C-SSWM catalysts applied to hydrogen mitigation: Temperature development mechanism, hydrogen mitigation effect and reaction lower limit - Xuan Li; Si-Yuan Zhou; Tao-Tao Ye; Jing Zhang; Bin Li; Dan Zhang; Yong-Xu Wang; Li-Feng Xie; Xian-Zhao Song (Fuel, 2025)

Study on the mechanism of 1-(4-bromophenyl)5-phenyl-1h-1, 2, 3-triazole against Colletotrichum gloeosporioides in mango by chemical proteomics - Shuai Wang; Jiayang Li; Cong Xie; Wanhui Chen; Huajie Feng; Wenying He (Food Bioscience, 2025)

Association of ambient ozone with time to pregnancy and the modifying effect of ambient temperature: a population-based cohort study - Bingxue Wu; Tao Wang; Yan Zhang; Yuyan Li; Cai Kong; Yishi Jiang; Xiangjing Song; Xing Chen; Zhengyuan Xie; Hanfeng Ye; Lin Feng; Zigao Zhao; et al. (Environmental Pollution, 2025)

Microbial hydrolysis of Camellia seed cake with Bacillus subtilis: Fermentation process optimization and bioactivity assessment of the hydrolysates - Lingyun Yao; Qingru Huang; Huatian Wang; Tao Feng; Chuang Yu; Kun Xie; Hao Liu; Shiqing Song; Li Shao; Min Sun (Biocatalysis and Agricultural Biotechnology, 2025)

Global Research and Emerging Trend of Superabsorbent Hydrogel Applied to Agriculture Based on Visual Analysis - Zhiwen Li; Yuankai Zhou; Tian Qin; Wei Liu; Xiaohao Guo; Yalan Zhang; Sunlin Chi; Jinying Xu; Zanxu Chen; Yongdong Zhang; Jiyi Kang; Xianchuan Xie; et al. (Water, Air, & Soil Pollution, 2025)

Association of grapevine geminivirus a isolate QN with upward leaf curling, necrosis, chlorosis, and malformation symptoms in two grapevine cultivars - Can Liu; Jinying Wang; Shangzhen Yu; Yinshuai Xie; Hanwei Li; Chenlu Feng; Mengqi Ma; Yixuan Wang; Yuqin Cheng (Archives of Virology, 2025)

Extracellular vesicles engineered to directly target encephalomyocarditis virus ameliorates multi-organ viremia in a lethal infection model - Jiayu Yue; Yanmei Yang; Adi Idris; Wenjing Jin; Yaxin Zhang; Yongfang Chen; Xiangrong Li; Huixia Li; Shasha Li; Yanqiao Wen; Ruofei Feng; Jingying Xie (Veterinary Microbiology, 2025)

Proline betaine facilitates angiogenesis in bronchopulmonary dysplasia - Wangdui Cili; Zhiye Qi; Qinghua Zhong; Yin Li; Xia Huang; Ruoting Yang; Si Tang; Qingyuan Li; Li Yang; Yue Ning; Yunbo Xie; Yanli Feng; et al. (Toxicology and Applied Pharmacology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Comprehensive study of flusulfinam in paddy water–sediment microcosms: Enantioselective fate, degradation pathways, and toxicity assessment - Shiling Liu; Xiaoli Li; Siying Qin; Heng Zhang; Tengfei Zhang; Junqi Zhu; Lu Lin; Lei Lian; Fayang Xie; Huihua Tan; Feng Zhao (Journal of Hazardous Materials, 2025)

Apatite as a proxy for imaging the link between multistage hydrothermal alteration and anomalous gold enrichment in orogenic gold deposits: Evidence from the Jiaodong Peninsula, Eastern China - Dong Xie; Liqiang Yang; Xue Gao; Gary O'Sullivan; M. Santosh; Wei Yang; Zengsheng Li; Tao Feng; Jun Deng (Journal of Geochemical Exploration, 2025)

Spatial-temporal distribution and emission of urban scale air pollutants in Hefei based on Mobile-DOAS - Zhidong Zhang; Pinhua Xie; Ang Li; Min Qin; Jin Xu; Zhaokun Hu; Xin Tian; Feng Hu; Yinsheng Lv; Jiangyi Zheng; Youtao Li (Journal of Environmental Sciences, 2025)

Influence of effective decay constant uncertainty on radon exhalation rate measurement from medium surfaces using CR-39 - Xinyue Yang; Zhongkai Fan; Huiying Li; Ruomei Xie; Shuaibin Liu; Shuai Yuan; Haibo Yi; Jiale Sun; Zhipeng Liu; Jiulin Wu; Shicheng Luo; Xianfa Mao; et al. (Journal of Environmental Radioactivity, 2025)

Metabolomic profiles of the infection pathways of Calcarisporium cordycipiticola on the cultivated and medicinal mushroom, Cordyceps militaris - Li Lu; Mahesh C.A. Galappaththi; Nimesha M. Patabendige; Yu-Zhe Feng; Tian Yang; Samantha C. Karunarathna; Jiang-Tao Xie; Eleni Gentekaki; Sylvie Rapior; Esteban Charria-Girón; Marc Stadler; Wei-Feng Ding; et al. (Fungal Biology, 2025)

Enhanced activation of peroxymonosulfate by nickel sulfide with sulfur vacancies for ultrafast organic pollutants degradation: Roles of active sites and mechanism - Cai-Wu Luo; Liang Jiang; Xian-Feng Li; Qiang-Mao Wan; Tian-Jiao Jiang; Sen-Ping Mao; Jing-Qian Guo; Run-Ze Zhao; Chao Xie (Environmental Pollution, 2025)

Toxicokinetic and liver proteomic study of the Chinese rare minnow (Gobiocypris rarus) exposed to F-53B - Hongbo Yang; Chan Xu; Jieyu Song; Jin Li; Chan Zhang; Chunli Teng; Kai Ma; Feng Xie (Aquatic Toxicology, 2025)

Outstanding Formaldehyde Abatement Performance and Preferable Resistance to SO2 and H2O over CrOx-CeOx Facilitated Hierarchical Porous Biochars Catalysts - Huiyu Xiong; Xiaoxin Feng; Lei Gao; Liping Xiang; Dong Xie; Caiting Li; Weizhi Peng; Zhixiu Huang; Xuan Liu (Water, Air, & Soil Pollution, 2025)

Biomedical data and AI - Hao Xu; Shibo Zhou; Zefeng Zhu; Vincenzo Vitelli; Liangyi Chen; Ziwei Dai; Ning Yang; Luhua Lai; Shengyong Yang; Sergey Ovchinnikov; Zhuoran Qiao; Sirui Liu; et al. (Science China Life Sciences, 2025)

The effects of simulated Martian regolith on Arabidopsis growth, circadian rhythms and rhizosphere microbiota - Yuanyuan Zhao; Rujia Luo; Haoran Zhang; Li Yuan; Xiaoting Fang; Xinjie Tong; Yongyu Qian; Zengxuan Zhou; Yilin Yang; Xiaojia Zeng; Jian-Feng Li; Xiaodong Xu; et al. (Plant and Soil, 2025)

RGVPSeg: multimodal information fusion network for retinogeniculate visual pathway segmentation - Qingrun Zeng; Lin Yang; Yongqiang Li; Lei Xie; Yuanjing Feng (Medical & Biological Engineering & Computing, 2025)

Association between multiple metals mixture and diabetic retinopathy in older adults with diabetes mellitus: a cross-sectional study in China - Shuren Ding; Yirong Xie; Feng Wang; Jieyi Liu; Hongya Li; Heng Su; Zhiqiang Zhao; Qing Wei; Shurong Pi; Fubin Chen; Qian Gu; Baixiang Xiao; et al. (Environmental Geochemistry and Health, 2025)

Monthly variations of the spring greenness response across boreal Eurasia to the preceding wintertime northern annular mode during 1982–2022 - Jing Li; Weiming Zeng; Ruichen Lin; Zhiqing Xu; Xilin Xie; Feng Su; Rui Zhao; Anmin Duan (Climate Dynamics, 2025)

Soil micro-structure drives trophic interactions within micro-food webs via bottom-up regulation under different planting patterns - Qiwen Xu; Mengdie Feng; Binghui He; Tianyang Li; Peng Tang; Dengyu Zhang; Yonghong Xie (Agriculture, Ecosystems & Environment, 2025)

Baicalin alleviates lipid accumulation in adipocytes via inducing metabolic reprogramming and targeting Adenosine A1 receptor - Zaikuan Zhang; Runzhi Wang; Jin Cai; Xinyi Li; Xiaosong Feng; Shengming Xu; Zhihong Jiang; Peiyi Lin; Zengyi Huang; Yajun Xie (Toxicon, 2025)

Investigations of spatial-temporal distribution and regional transport in typical section of NO2 in eastern China using Mobile-DOAS - Zhidong Zhang; Pinhua Xie; Ang Li; Jin Xu; Xin Tian; Feng Hu; Zhaokun Hu; Yinsheng Lv; Youtao Li; Qiang Zhang; Wenqing Liu (Science of The Total Environment, 2025)

Phlecarinatones H–N: Abietane-type diterpenoids from Phlegmariurus carinatus with proliferative inhibitory effect on U251 glioblastoma cells - Hua Wang; Qiang Wang; Yong-Hong Chen; Xi Chen; Dong-Kun Zheng; Zhen Xie; Du-Min Feng; Lin Liu; Jing Li; Yang Liu (Phytochemistry, 2025)

Short-term water quality prediction of reclaimed water plant effluent and key measurement sections based on a surrogate prediction model - Jing Feng; Yu Tian; Peng Li; Zhaolong Xie; Hao Wang (Journal of Environmental Management, 2025)

Enhanced ammonia synthesis using surface microdischarge with metal-loaded nickel foam electrodes - Yue Feng; Yuzhuo Cai; Yaolin Wang; Tianyu Li; Santu Luo; Wenpeng Liang; Sutao Zheng; Tao Xie; Qing-Yuan Yang; Xue Yong; Renwu Zhou; Dingxin Liu; et al. (Chemical Engineering Journal, 2025)

Understanding equilibrium climate sensitivity changes from CMIP5 to CMIP6: Feedback, AMOC, and precipitation responses - Xinqi Wang; Lijuan Li; He Wang; Ling Zuo; Bin Wang; Feng Xie (Atmospheric Research, 2025)

PpSPL1 and PpSPL15 inhibit peach branching by increasing strigolactone synthesis - Wan Pei; Jie Zhang; Ruixian Shen; Hefang Xie; Yajia Zhang; Junjie Zhang; Xiaodong Lian; Haipeng Zhang; Nan Hou; Lei Wang; Xianbo Zheng; Jun Cheng; et al. (Planta, 2025)

Correction to: Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2025)

Changes in the spectroscopic response of soil organic matters by PBAT microplastics regulated the Cd adsorption behaviors in different soils - Rongxin Xie; Ming Li; Zhiwang Feng; Jiayi Xie; Akaninyene Joseph; Minori Uchimiya; Yimin Wang (Environmental Geochemistry and Health, 2025)

Adsorption Behaviors of Cadmium Regulated by Microplastics Properties in a Forest Soil - Akaninyene Joseph; Rongxin Xie; Zhiwang Feng; Hanzhou Wu; Jizhou Li; Xuyin Yuan; Ningyuan Zhu; Yimin Wang (Bulletin of Environmental Contamination and Toxicology, 2025)

Transcriptome Profiling of Mutant iew-1 with Epicuticular wax Increase in Common Wheat (Triticum aestivum L.) - Tong Gou; Qiqi Ha; Jun Xing; Xiaoting Xie; Aixia Ren; Pengcheng Ding; Ying You; Zhiqiang Gao; Feng Liu; Linghong Li; Min Sun (Journal of Plant Biology, 2025)

Efficient conversion and highly sensitive detection of PAEs in milk based on hydrazinolysis reaction and hydrogen bonding using SERS technique - Lili Hua; Hongmei Li; Jing-Wen Zhou; Xiao-Feng Liu; Xian-Ming Guo; Zhao-Bing Zhang; Yichuan Kou; Tang-Tang Xie; Cuihong Sheng; Lin Zhang; Sheng-Hong Liu; Fan-Li Zhang; et al. (Analytica Chimica Acta, 2025)

Role of Glucose Metabolism in the Effects of Serum Metals on Telomere Length: Findings in Chinese Diabetic Population - Shuren Ding; Qian Gu; Zhiqiang Zhao; Yirong Xie; Feng Wang; Jieyi Liu; Hongya Li; Heng Su; Qing Wei; Shurong Pi; Fubin Chen; Baixiang Xiao; et al. (Biological Trace Element Research, 2025)

Hippocampal MEF2C phosphorylation mediates synaptic plasticity in lead-induced learning and memory impairments - Shuo Yang; Yanhui Zhu; Jinmei Xiao; Lingyu Yan; Xuebing Zhuang; Qi Li; Yue Li; Jie Xie; Guihua Du; Fankun Zhou; Guangqin Fan; Chang Feng (Toxicology, 2025)

Theoretical study on the characteristics of P1 wave seismic scattering induced by seabed slope with local interlayers - Feng Guang-rui; Xie Li-quan (Soil Dynamics and Earthquake Engineering, 2025)

Cavity as radio telescope for galactic dark photon - Yanjie Zeng; Yuxin Liu; Chunlong Li; Yuxiang Liu; Bo Wang; Zhenxing Tang; Yuting Yang; Liwen Feng; Peng Sha; Zhenghui Mi; Weimin Pan; Tianzong Zhang; et al. (Science Bulletin, 2025)

Modified bauxite enhanced electrocoagulation for groundwater fluoride pollution: Insights into the efficacy and mechanism - Zhiheng Cao; Junfeng Li; Xueting Feng; Qiong Feng; Dongbao Song; Wenhuai Wang; Junyang Xiao; Xi Xie (Journal of Water Process Engineering, 2025)

Efficient fluconazole degradation by activating peroxymonosulfate with LDH-coated nickel foam: Synergism of radical and non-radical pathways - Xiang-Yang Li; Ling-Xi Zhao; Meng Xie; Ning Liu; Xiang-Feng Chen; Ru-Song Zhao (Journal of Water Process Engineering, 2025)

LPA reduces the apoptosis of cryopreserved porcine skin-derived stem cells by inhibiting the regulatory factor TNF-α - Xin-Xiang Xie; Jia-Dong Sun; Ming-Xin Zang; Geng Zhang; Chun-Xiao Li; Xiang-Wei Zhai; Wei Shen; Wei Ge; Shun-Feng Cheng (Cryobiology, 2025)

Structural design and biomechanical analysis of a combined titanium and polyetheretherketone cage based on PE-PLIF fusion - Lei Ma; Yutang Xie; Kai Zhang; Jing Chen; Yanqin Wang; Liming He; Haoyu Feng; Weiyi Chen; Meng Zhang; Yanru Xue; Xiaogang Wu; Qiang Li (Medical & Biological Engineering & Computing, 2025)

Temporal dynamics of bacterial biofilms and their relationship with heavy metals on expanded polystyrene microplastics - Qun Xie; Yan Feng; Xiangrong Xu; Hengxiang Li; Lang Lin; Weiqiong Yu; Guanghui Zhu; Nenghao Zhong; Minhua Wu; Kai Zhang (Journal of Oceanology and Limnology, 2025)

Corrigendum to “Effects of fasting on golden pompano Trachinotus ovatus: Physiological and biochemical responses” [Aquaculture, Volume 595, Part 1, 30 January 2025, 741637] - Xing Ren; Xiaojie Lu; Yubo Wu; Li Zhang; Huawei Ma; Yueyuan Tan; Yao Guan; Renming Jia; Enge Xie; Aiping Feng; Ning Zhang (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Impact of the 1994–1997 temporary decrease in Northern Hemisphere stratospheric methane on the 1990s methane trend - Yuanyuan Han; Shentao Li; Xinlong Tan; Wenyan Guo; Wuhu Feng; Xin Li; Feiyang Wang; Fei Xie (Global and Planetary Change, 2025)

Halloysite nanotube@N-doped carbon electrocatalysts for highly efficient hydrogen peroxide cathode fuel electrosynthesis - Yongrong Sun; Fayong Li; Yue Feng; Mingxian Liu; Dong Xie (Fuel, 2025)

Understanding the anti-browning mechanism and physicochemical properties in potato pulp during the magnetic field processing - Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Xin Zhang; Chuangshuo Yan; Yujian Xie; Dongliang Zhang; Hongjun Li (Food Chemistry, 2025)

Involvement of PRQFVamide-related peptide in immune response of Sepiella japonica through suppressing nitric oxide production - Xu Zhou; Shu-fan Yu; Jia-yin Qiu; Jian-jun Xie; Shuang Li; Li-bing Zheng; Chang-feng Chi (Aquaculture International, 2025)

The PhoBR two-component system upregulates virulence in Aeromonas dhakensis C4–1 - Wei Feng; Xuesong Li; Nuo Yang; Lixia Fan; Guiying Guo; Jun Xie; Xiuqing Cai; Yuqi Meng; Jifeng Zeng; Yu Han; Jiping Zheng (Aquaculture, 2025)

Effects of fasting on golden pompano Trachinotus ovatus: Physiological and biochemical responses - Xing Ren; Xiaojie Lu; Yubo Wu; Li Zhang; Huawei Ma; Yueyuan Tan; Yao Guan; Renming Jia; Enge Xie; Aiping Feng; Ning Zhang (Aquaculture, 2025)

Lignite degraded by Trichoderma citrinoviride: Products, processes and mechanisms - Xingyu Mu; Meitong Li; Jianhua Tian; Wenjiao Yuan; Hui Shen; Ruijie Zhang; Shuwei Li; Xin Feng; Xuening Fei; Yuhong Xie (International Biodeterioration & Biodegradation, 2025)

Electrospinning of emulsions stabilized by octenylsuccinylated starch and pullulan - Xuerong Huang; Feng Zhao; Zifan Teng; Yingkai Li; Chuang Zhang; Xingxun Liu; Songnan Li; Fengwei Xie (Food Hydrocolloids, 2025)

Blocking the PD-1 signal transduction by occupying the phosphorylated ITSM recognition site of SHP-2 - Wenjie Li; Wenyi Mei; Hewei Jiang; Jie Wang; Xiaoli Li; Lina Quan; Yanyan Diao; Yanni Ma; Sisi Fan; Zhuwei Xie; Mengdie Gong; Huan Zhu; et al. (Science China Life Sciences, 2025)

The Association Between Functional Variants in Long Non-coding RNAs and the Risk of Autism Spectrum Disorder Was Not Mediated by Gut Microbiota - Kaiheng Zhu; Xinyan Xie; Fang Hou; Yanlin Chen; Haoxue Wang; Qi Jiang; Yanan Feng; Pei Xiao; Quan Zhang; Zhen Xiang; Yixi Fan; Xufang Wu; et al. (Molecular Neurobiology, 2025)

Linkage detection between climate oscillations and water and sediment discharge of 10 rivers in Eastern China - Feng Zhang; Li Zhang; Yaozhao Zhong; Huangjie Zou; Xiaohe Lai; Yanshuang Xie (Frontiers in Marine Science, 2024)
Water discharge and sediment load are often controlled by a combination of factors. However, the relationship between water and sediment load changes and meteorological oscillations has rarely been explored for different river sizes. Explanations for the various responses of water-sediment changes to meteorological factors in different rivers is important for understanding global hydrology. In this study, we analyzed data from 2002-2022 using cross-wavelet and wavelet coherence in an attempt to characterize the effects of large-scale climatic oscillations on 10 rivers in eastern China. Comparing the results shows that water releases lag three months or more behind SST variations. It also oscillates interannually (mostly every 8-16 months). Most rivers runoff lags changes in PDO by three months or more. The impact of ENSO (El Niño-Southern Oscillation) on each river basin gradually decreases from south to north. The impacts on northern rivers such as the Yellow River, Huai Riverand Liao River are weaker. At the same time, the water discharge changes in the Pearl River and Minjiang River basins in southeastern China are extremely rapid and sensitive to ENSO events. Meanwhile, the impacts of ENSO on large rivers lasted throughout the study period, while the impacts of ENSO on smaller rivers had intermittent periods, and the response rates of geographically similar mountain and stream-type rivers were not the same. The effect of the PDO (Pacific Decadal Oscillation) warm and cold phases was different for each region. Our research contributes to understanding the relationship between rivers and climate oscillations, advancing Water-Sediment Balance and Global Sustainability—key goals of the United Nations 2030 Agenda for Sustainable Development.

A Method for Aliasing Metal Particle Recognition Based on Three-Coil Sensor Using Frequency Conversion - Di Wu; Yucai Xie; Chenyong Wang; Xian’an Gu; Feng Gu; Guoqing Li; Hongpeng Zhang; Yunsheng An; Rui Li; Changzhi Gu (Journal of Marine Science and Engineering, 2024)
The diesel engine on a ship is crucial as it serves as the primary power source, significantly influencing both the vessel’s efficiency and safety. Monitoring metal wear particles found in lubricating oil is essential for assessing the lubrication condition of mechanical equipment onboard and anticipating potential failures. Analyzing these metal wear particles allows us to gauge the wear status of bearing pairs within the machinery, thereby providing a technical foundation for routine maintenance activities. However, under real operating conditions, it can be challenging to prevent multiple metal particles from simultaneously passing through sensors. To address this issue, this research introduces an innovative three-coil induction sensor that employs a variable-frequency excitation technique to explore how induction and eddy currents interact. The findings indicate that when the excitation frequency changes, the peak value of the signal from 337 μm iron particles only increases by 3.35 times, while the peak value of the signal from 340 μm copper particles increases by 22.69 times. Consequently, this study recommends using changes in excitation frequency to differentiate between mixed metal particles made of various materials.

Fecal microbiota transplantation as an effective way in treating methylmercury-poisoned rats - Yanfei Zhang; Qingxuan Liu; Hongxin Xie; Wei Zhang; Xiaoying Lin; Huifeng Zhang; Huan Yu; Yinghui Ma; Chuang Zhang; Hao Geng; Nianqiu Shi; Liwei Cui; et al. (Science of The Total Environment, 2024)

The Keap1-Nrf2/ARE signaling pathway regulates redox balance and apoptosis in the small yellow croaker (Larimichthys polyactis) under hypoxic stress - Jingqian Wang; Li Wang; Yang Liu; Congcong Hou; Qingping Xie; Daojun Tang; Feng Liu; Bao Lou; Junquan Zhu (Science of The Total Environment, 2024)

Evaluating the role of recalcitrant dissolved organic matter in bacterial community dynamics in urbanized freshwater ecosystems - Yang Liu; Xiding Wang; Huimin Li; Ruikai Zhang; Xudong Liu; Fangru Nan; Qi Liu; Junping Lv; Jia Feng; Chao Ma; Shulian Xie (Science of The Total Environment, 2024)

Dust event identification and characterization with one-year online observations in Beijing - Feixue Zheng; Jinwen Li; Chenjie Hua; Jiali Xie; Yusheng Zhang; Liye Li; Sunan Shen; Simo Hakala; Chao Yan; Zemin Feng; Xiaolong Fan; Federico Bianchi; et al. (Science of The Total Environment, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Effect of isomeric polysaccharides on heteroaggregation of nanoplastics in high ionic strength conditions: Synergies of morphology and molecular conformation - Yong Liu; Jie Ma; Bingcong Feng; Xiaoyu Zhang; Yujie Zhao; Liping Weng; Yali Chen; Haijiao Xie; Yongtao Li (Journal of Hazardous Materials, 2024)

Mechanism of membrane fouling mitigation by microalgae biofilm formation for low C/N mariculture wastewater treatment: EPS characteristics, composition and interfacial interaction energy - Yanbo Liu; Jing Zhu; Weirun Li; Binghan Xie; Guoyu Zhang; Yi Ding; Feng Liu; Haili Tan; Yuhong Jia; Hong You; Zhipeng Li (Journal of Environmental Chemical Engineering, 2024)

Targeted construction of porous biochar with well-developed pore structure for high-performance CO2 adsorption - Zhipei Tang; Jianmin Gao; Heming Dong; Qian Du; Dongdong Feng; Jian Cheng; Junfeng Li; Yirui Peng; Tianhang Zhang; Min Xie; Huanlong Chen (Journal of Environmental Chemical Engineering, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Bacterial community and dissolved organic matter networks in urban river: The role of human influence - Xiding Wang; Huimin Li; Ruikai Zhang; Xudong Liu; Fangru Nan; Qi Liu; Junping Lv; Jia Feng; Shulian Xie; Yang Liu (Environmental Research, 2024)

Spatiotemporal variations of PM2.5 organic molecular markers in five central cities of the Yangtze River Delta, East China in autumn and winter: Implications for regional and local sources of organic aerosols - Wei Feng; Guihong Dong; Wanqing Qi; Yizhen Wang; Xiangyu Zhang; Ke Li; Hong Liao; Yuhang Wang; Zhijuan Shao; Mingjie Xie (Environmental Pollution, 2024)

High-homogeneous recyclable self-cured epoxy resins based on imine - Changbo Zhao; Guohua Huang; Hao Zhang; Hui Xie; Feixiang Sha; Lukun Feng; Jinze Cui; Xiyan Li; Mingliang Wang; Feng Bao; Zhiyong Xue; Caizhen Zhu; et al. (Chemical Engineering Journal, 2024)

Nanoscale Biochar for Fertilizer Quality Optimization in Waste Composting: Microbial Community Regulation - Ran Tao; Menghan Cui; Yuqing Li; Jixiang Wang; Weijiang He; Yingjie Zhao; Wenping Xie; Yu Shen; Yanfang Feng; Jason C. White (Bioresource Technology, 2024)

Triclosan facilitates the dissemination of antibiotic resistance genes during anaerobic digestion: Focusing on horizontal transfer and microbial response - Panliang Wang; Liuying Li; Yufei Zhang; Dayang Ren; Yiyi Feng; Xiaoyu Li; Dong Wu; Bing Xie; Junguo Ma (Bioresource Technology, 2024)

Microbial transformation of lignite into methane: Insights from anaerobic-activated sludge systems - Ruijie Zhang; Meitong Li; Wenjiao Yuan; Xin Feng; Xuening Fei; Xingcheng Zhao; Gangzhen Jiao; Hui Shen; Xingyu Mu; Yuhong Xie (Bioresource Technology Reports, 2024)

Chemical characteristics, sources, and formation mechanisms of PM2.5 before, during, and after the Spring Festival in a plateau city of Southwest China - Jianwu Shi; Li Deng; Wei Du; Xinyu Han; Yaoqian Zhong; Wenjun Rao; Haitao Xie; Feng Xiang; Ping Ning; Senlin Tian (Atmospheric Environment, 2024)

Microphysical characteristics of torrential predecessor rain events over the Yangtze River Delta Area and the related tropical cyclones - Huiyan Xu; Bin Xie; Xiaofan Li; Ben Wang; Lingyun Lou; Zhifeng Yu; Jiaxi Wu; Dengrong Zhang; Feng Zhang (Atmospheric Research, 2024)

Short-term regulation of TSFM level does not alter amyloidogenesis and mitochondrial function in type-specific cells - Xiao-Yun Li; Gui-Feng Zhou; Xiong-Yong Xie; Ya-Lan Pu; Xue -Chen; Chen-Lu Li; Jie Yang; Lu Wang; Guo-Jun Chen (Molecular Biology Reports, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

The development characteristics and exploration significance of the Changxing Formation reefs in the eastern Sichuan Basin under the sequence framework - Xin Chen; Lei Chen; Shengxian Zhao; Xiucheng Tan; Fei Liu; Liang Feng; Bo Li; Gaoxiang Wang; Shengyang Xie (Carbonates and Evaporites, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Effects of 2,4,6-Trichloroanisole on the morphological development and motility of zebrafish - Yanxia Zuo; Fang Zhou; Rong Huang; Zhihui Jia; Juhong Xie; Guangxin Wang; Shuzhao Jia; Yongming Li; Manyi Wang; Lanjie Liao; Feng Ge; Yaping Wang (Science of The Total Environment, 2024)

The impact of evolving synoptic weather patterns on multi-scale transport and sources of persistent high-concentration ozone pollution event in the Yangtze River Delta, China - Feng Hu; Pinhua Xie; Yu Zhu; Fuhai Zhang; Jin Xu; YinSheng Lv; ZhiDong Zhang; Jiangyi Zheng; Qiang Zhang; Youtao Li; Xin Tian (Science of The Total Environment, 2024)

Fetal weight growth trajectories and childhood development: A population-based cohort study - Xinmei Chen; Hongxiu Liu; Aifen Zhou; Feng Jin; Chufeng Jing; Yuanyuan Li; Wei Xia; Linda G. Kahn; Ya Xie; Xingliang Xiang; Shuting Cao; Wenxin Zhang; et al. (Science Bulletin, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Improved identification and monitoring of meteorological, agricultural, and hydrological droughts using the modified nonstationary drought indices in the Yellow River Basin of China - Ben Niu; Yi Li; De Li Liu; Lulu Xie; Lei Wang; Xiaohui Jiang; Hao Feng; Qiang Yu; Jianqiang He; Haixia Lin (Journal of Hydrology, 2024)

Optimal agronomic measures combined with biochar increased rice yield through enhancing nitrogen use efficiency in soda saline-alkali fields - Shihao Miao; Xudong Wang; Yang Song; Yue Zhang; Xuebin Li; Weikang Che; Junlong Piao; Liming Xie; Feng Jin (European Journal of Agronomy, 2024)

Outside-in enhancement of phosphate solubilizing bacteria by sludge biochar for phenol remediation in soil: Pollution stress reduction, electron transfer gain and secretion regulation - Nazhafati Muhanmaitijiang; Yang Feng; Yuyan Xie; Xianfeng Du; Jiansheng Li; Haoming Chen (Chemical Engineering Journal, 2024)

Enhanced sensitivity and broadband response in porous triple periodic minimal surface piezoresistive sensors for telemedicine applications - Jiahong Han; Zhongming Li; Shuoshuo Kong; Bin Li; Tao Chen; Haili Zhao; Delong Xie; Dong Feng (Chemical Engineering Journal, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

Recyclable VOCs-free eutectic adhesive based on hydrogen bond fusion strategy with robust adhesion, flame retardancy, transparency, high durability, and low-temperature resistance - Chenyang Xie; Shiru Wang; Feng Li; Liang Meng; Jingtian Chen; Lei Wang; Jingyue Yang (Chemical Engineering Journal, 2024)

Sequence-Unconstrained DNA Computing: DSN cycling and PER circuitry for dynamic miRNAs analysis and multifunctional logic operations - Dan Bai; Yaoyi Zhang; Jiu Pu; Li Zhang; Hongyan Yu; Xiaole Han; Ke Lv; Li Wang; Junjie Li; Ao Tang; Wang Luo; You Wu; et al. (Chemical Engineering Journal, 2024)

Allosteric stem-loop multicomponent DNAzyme: A versatile stimuli-responsive switch for nanotweezer operations and multifunctional biosensing - Yaoyi Zhang; Dan Bai; Jiu Pu; Li Zhang; Weitao Wang; Tong Feng; Jianhong Zhang; Hongyan Yu; Xiaole Han; Ke Lv; Li Wang; Yongcan Guo; et al. (Chemical Engineering Journal, 2024)

Enhancing medium-chain fatty acids production via alkyl polyglucose modulation of electron acceptor generation, microbial community and metabolic traits in anaerobic fermentation of waste activated sludge - Chun-shuang Zhou; Guang-li Cao; Bing-feng Liu; Guo-jun Xie; Wan-li Ma; Sheng-qiang Fan; Nan-qi Ren (Chemical Engineering Journal, 2024)

Salinomycin, a potent inhibitor of XOD and URAT1, ameliorates hyperuricemic nephropathy by activating NRF2, modulating the gut microbiota, and promoting SCFA production - Yong-jun Chen; Zi-tao Guo; Hai-qiao Chen; Shi-fan Zhang; Ying-xia Bao; Zhoufan Xie; Jia-le Ke; Wen-jie Ye; Jia-cheng Liang; Jia-chen Chen; Ning Li; Feng-xin Zheng; et al. (Chemico-Biological Interactions, 2024)

Effects of varied inundation characteristics on early life stages of a salt marsh plant - Qing Wang; Meng Luo; Baoshan Cui; Cong Chen; Tian Xie; Xia Li; Feng Lu (Frontiers in Marine Science, 2024)
Tidal inundation is a major stress in salt marshes that regulates the patterns of plant distribution and the associated functions provided by vegetation communities. Usually, frequency is used to represent inundation intensity and can be estimated using elevation. However, frequency is only a statistical indicator of tidal inundation conditions during a given period, which ignores many details of tidal inundation characteristics based on a single tidal event. On the scale of a single tidal event, duration and water depth are important characteristics for describing inundation conditions, which vary along the elevation gradient. The frequency of tidal events of a specific duration and water depth also varied. To unravel the impact of varied inundation characteristics on the key life stages of a foundation plant, we designed an experiment with varied inundation treatments of different frequencies, durations, and depths. Our results showed that the frequency, duration, and depth of inundation events significantly influenced seed emergence, seedling survival, and growth. Stress can be strengthened by a higher frequency with a longer duration and larger depth. Among these factors, frequency had a dominant impact, followed by duration and water depth. Specifically, there is a trade-off between frequency, duration, and depth, suggesting that an inundation event with shallower depth and/or shorter duration would reduce the stress from higher frequency. The findings fill a gap in the loss of details of varied inundation characteristics on plant establishment on a fine scale. Further, it will help explicit inundation stress more accurately and clearly and provide important implications for stress relief solutions in coastal ecological restoration.

Otolith Microchemistry Reveals the Diversity of Migration Patterns and Spawning Ground Distribution of Coilia nasus from the Yangtze River Estuary - Chao Song; Wenjie Yu; Ruohui Liu; Jilin Xie; Feipeng Li; Feng Zhao; Ping Zhuang (Fishes, 2024)
Coilia nasus are an important fish resource in the Yangtze River, and the Yangtze River Estuary is a crucial migration pathway for them. In this study, we used otolith microchemistry to analyze the strontium/calcium (Sr/Ca) ratios and Sr contents in the sagitta otolith of C. nasus from the south branch (SB) and north branch (NB) of the Yangtze River Estuary and obtained the diversity of migration patterns and spawning ground distribution for C. nasus. The results indicate that C. nasus from both branches include two types of habitat history: freshwater (F)–brackish water (B) (Type I) and F-B seawater (S) (Type II), with Type I being dominant at 62.50% in both branches. The C. nasus from the SB comprise six migration patterns, while that from the NB has seven migration patterns. The C. nasus from both branches hatch in F habitats. At the time of capture, the C. nasus from the SB predominantly remain in F, accounting for 62.5%, while C. nasus from the NB primarily stay in B, accounting for 87.5%. Throughout the migration process, C. nasus from both branches switch between different habitats, with C. nasus from the NB exhibiting more frequent transitions between F and B, showing a greater reliance on the estuarine brackish habitat. The radius of the first blue region near the core (Lf) and freshwater coefficient (Fc) of the otolith for C. nasus from both branches are divided into three groups: long-distance freshwater dependence (LD), medium-distance freshwater dependence (MD), and short-distance freshwater dependence (SD), with the LD only appearing in the SB, while the NB is primarily represented by MD. There is a correlation between the differences in Lf among different groups of C. nasus and the differences in the distance from the spawning grounds of C. nasus in different sections of the Yangtze River to the estuary (DYRE), reflecting the distribution pattern of C. nasus spawning grounds in different sections of the Yangtze River. This study provides theoretical guidance for the protection of migration pathways and maintenance of spawning grounds for C. nasus, which have significant practical value in the precise management of C. nasus resources in the Yangtze River Estuary.

New challenge: Mitigation and control of antibiotic resistant genes in aquatic environments by biochar - Yimeng Feng; Tong Xie; Fengxiang Li (Science of The Total Environment, 2024)

Improving key gene expression and di-n-butyl phthalate (DBP) degrading ability in a novel Pseudochrobactrum sp. XF203 by ribosome engineering - Yunchang Xie; Nai-Xian Feng; Li Huang; Miaoer Wu; Cheng-Xuan Li; Fantao Zhang; Yunhong Huang; Quan-Ying Cai; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Reasonably adjusting the oxygen vacancies and Mn valence of nanocomposite microspheres Mn-Ni catalysts to boost toluene catalytic oxidation - Pijun Gong; Mingyang Ma; Xin Zhou; Ruhan Zhang; Feng He; Junlin Xie; Xiaoqiang Li (Journal of Environmental Chemical Engineering, 2024)

Effect of two-stage low-temperature tempering process assisted by electrostatic field application on physicochemical and structural properties of myofibrillar protein in frozen longissimus dorsi of tan mutton - Yuanlv Zhang; Yang Li; Jiajun Guo; Yuqin Feng; Qiwen Xie; Mei Guo; Junjie Yin; Guishan Liu (Food Chemistry, 2024)

Game analysis of future rice yield changes in China based on explainable machine-learning and planting date optimization - Ziya Zhang; Yi Li; Lulu Xie; Shiqiong Li; Hao Feng; Kadambot H.M. Siddique; Guozhen Lin (Field Crops Research, 2024)

Controlling of irreversible fouling and mechanism in a hybrid ceramic membrane bioreactor (CMBR)-reverse osmosis (RO) process for textile wastewater reclamation - Feng Zhou; Wenyue Wang; Kaiyi Li; Weilong Yang; Jaewon Lee; Bing Xie; Bing Wu; Hongqiang Ren; Seungkwan Hong; Min Zhan (Desalination, 2024)

Design of enhanced entropy-driven non-covalent DNA catalytic reactions via the paired junction structure - Weitao Wang; Hongyan Yu; Xiaole Han; Li Zhang; Zhi Weng; Chen Zuo; Na Yin; Yaoyi Zhang; Tong Feng; Dan Bai; Ao Tang; Yongcan Guo; et al. (Chemical Engineering Journal, 2024)

Anchored Ru nanoclusters strategy enhances hydrogen spillover effect for high-efficiency hydrogen storage - Xiao-Qi Zhang; Yi-Qiang Qi; He Liu; Jun-Yu Wang; Li-Ying Xie; Jun-Lian Shi; Feng Wang; Yue-Liang Liu; Zong-Xian Wang; Ai-Jun Guo (Chemical Engineering Journal, 2024)

Accelerated cartilage regeneration through immunomodulation and enhanced chondrogenesis by an extracellular matrix hydrogel encapsulating Kartogenin - Kai Huang; Qing-Yi Zhang; Jie Tan; Rong Nie; Zi-Yuan Feng; Yuan Liu; Ning Sheng; He-Xi Li; Yue-Qi Zhang; Bin Shen; Hui-Qi Xie (Chemical Engineering Journal, 2024)

High resistance towards electrochemical dissolution of cubic Rh@Ir core shell in acidic water splitting - Yuhua Xie; Yumei Feng; Chen Li; Fang Luo; Qing Li; Shiao Zhu; Mingxing Gong; Zehui Yang (Chemical Engineering Journal, 2024)

Ultrasmall Cu2I2 nanoclusters trigger metabolic-epigenetic reprogramming and endogenous antioxidant systems for alleviating osteoarthritis - Yexin Wang; Xuyang Ding; Feng Zhang; Xinru Xie; Chen Yang; Zhiming Wang; Xiaodong Cai; Qilin Li; Lingjie Li; Xuzhuo Chen; Fengrong Dai; Shanyong Zhang (Chemical Engineering Journal, 2024)

Three-way junction-mediated three-letter coded SDA cascade CRISPR/Cas12a system for circRNA detection - Di Wu; Xin Liu; Lujia Tang; Baiying Li; Rong Zhao; Tong Feng; Xiangyang Xiao; Guoming Xie; Wenli Feng (Chemical Engineering Journal, 2024)

Use of Tirofiban to Prevent Ischemic Events in Patients with CYP2C19 Loss-of-Function Alleles during Flow Diversion of Intracranial Aneurysm: A Multicenter Cohort Study - Yangyang Zhou; Huibin Kang; Wenqiang Li; Bin Luo; Chao Wang; Ruhang Xie; Yongnan Zhu; Qichen Peng; Yisen Zhang; Jian Liu; Ying Zhang; Shiqing Mu; et al. (Translational Stroke Research, 2024)

Understanding the genesis of ore-bearing and ore-barren adakitic rocks: insights from geochronology and geochemical analysis of the Tuncang intrusion and enclaves along the South Tan-Lu Fault - Feng Zi; Wenzhou Xiao; Mabrouk Sami; Chenguang Zhang; Fenquan Xie; Ye Liu; Shuanglian Li (International Journal of Earth Sciences, 2024)

Concurrent drought threatens wheat and maize production and will widen crop yield gaps in the future - Miaolei Hou; Yi Li; Asim Biswas; Xinguo Chen; Lulu Xie; Deli Liu; Linchao Li; Hao Feng; Shufang Wu; Yusuke Satoh; Alim Pulatov; Kadambot H.M. Siddique (Agricultural Systems, 2024)

Bioinformatics Analysis and Identification of Ferroptosis-Related Hub Genes in Intervertebral Disc Degeneration - Feng Jiang; Xinxin Li; Zhiyang Xie; Lei Liu; Xiaotao Wu; Yuntao Wang (Biochemical Genetics, 2024)

The effects of polypropylene microplastics on the removal of nitrogen and phosphorus from water by Acorus calamus, Iris tectorum and functional microorganisms - Yilin Zhao; Zuoming Xie; Baoming Hu; Yuanle Li; Aiting Teng; Feng Zhong (Chemosphere, 2024)

Multi-constraint improved RS path planning method for unmanned rice direct seeding machine - Lian Hu; Kang Hou; Jie He; Zhongxian Man; Jiasheng Xie; Pei Wang; Tuanpeng Tu; Ruitao Gao; Le Zi; Yufeng Huang; Mingjin Li; Shuaiqi Ding; et al. (Computers and Electronics in Agriculture, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

First report on liquid crystal monomers in tree barks surrounding a display manufacturer: Insights for atmospheric transport and establishment of priority list - Jiong-Feng Xie; Jia-Yi Gu; Liang-Zhong Li; Ying Guo; Liang-Ying Liu (Journal of Hazardous Materials, 2024)

Revealing the comprehensive effect of mechanization on sauce-flavor Daqu through high-throughput sequencing and multi-dimensional metabolite profiling - Yu Mu; Ying Huang; Dong Li; Zhiyu Zhu; Shirui Yu; Feng Xie (Food Research International, 2024)

Efficient uranium sequestration ability and mechanism of live and inactivated strain of Streptomyces sp. HX-1 isolated from uranium wastewater - Gen Xie; Guangwen Feng; Qin Li; Keyong Zhang; Chao Tang; Henglei Chen; Changlong Cai; Peihong Mao (Environmental Pollution, 2024)

The entropy effect on the structure and microwave dielectric properties of high-entropy Lix(MgZnCoNi)(1-x)/4Al2O4-δ ceramics - Mingjun Xie; Yuanming Lai; Pingwen Xiang; Feng Liu; Linqiao Zhang; Xingyue Liao; Huan Huang; Qian Liu; Chongsheng Wu; Yuanxun Li (Chemical Engineering Journal, 2024)

Bulky neutral group incorporation in Through-Space charge transfer delayed fluorescence emitters for efficient Non-Doped organic Light-Emitting diodes - Han-Yang Wang; Feng-Ming Xie; Hao-Ze Li; Kai Zhang; Jianhua Zou; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Hydrochemical characteristics and the ecological effect of algal carbonic anhydrase in carbon cycle in the Taiyuan section of Fenhe River - Jing Yang; Xin Li; Shulian Xie; Jia Feng (Journal of Oceanology and Limnology, 2024)

Revealing mechanisms of NH3 and N2O emissions reduction in the rapid bio-drying of food waste: Insights from organic nitrogen composition and microbial activity - Kaiyi Li; Liangmao Zhang; Feng Zhou; Kai Yang; Min Zhan; Yinglong Su; Dong Wu; Bing Xie (Science of The Total Environment, 2024)

Transparent and open-source aluminum life cycle inventory dataset for China - Jinliang Xie; Yuzhen Feng; Huimin Chang; Changqing Xu; Ruoxi Xiong; Zimeng Cai; Chenling Fu; Ziqian Xia; Jing Guo; Nan Li (Resources, Conservation and Recycling, 2024)

Mechanical properties and electromagnetic wave absorption characteristics of solid waste low-carbon cementitious materials - Hongzhang Xie; Wenjing Sun; Mingyu Li; Xiating Feng (Journal of Cleaner Production, 2024)

Deciphering the formation of granules by n-DAMO and Anammox microorganisms - Zhi-Cheng Zhao; Ruo-Lin Li; Sheng-Qiang Fan; Yang Lu; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Environmental Research, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Application of spatial filtering high order FDTD method in the multi-physics field coupled equations - Guoda Xie; Pan Pan; Naixing Feng; Ke Xu; Ming Fang; Xianliang Wu; Yingsong Li; Zhixiang Huang (Computer Physics Communications, 2024)

Effect of oxy-fuel combustion with different O2/CO2 fractions on the pulverized coal combustion mechanism and heat transfer characteristics in rotary kilns: A numerical simulation study - Quanliang Li; Feng He; Shuxia Mei; Junlin Xie; Chao Zhang; Yuhua Deng (Chemical Engineering Journal, 2024)

An ink-free integrated dual electrode assembly for economical proton electrolyzer membrane water electrolysis at ultrahigh current densities - Weitian Wang; Lei Ding; Jun Li; Zhiqiang Xie; Matthew M. Mench; Feng-Yuan Zhang (Chemical Engineering Journal, 2024)

Synergistically promoting the catalytic conversion of polysulfides via in-situ construction of Ni-MnO2 heterostructure on N-doped hollow carbon spheres towards high-performance sodium-sulfur batteries - Haoyu Zhao; Zuze Li; Mingzhe Liu; Suyu Ge; Kaixuan Ma; Qingze Jiao; Hansheng Li; Haijiao Xie; Yun Zhao; Caihong Feng (Chemical Engineering Journal, 2024)

Pyrolysis-free coupling strategy to synthesize two-dimensional oxygen reaction electrocatalysts for rechargeable Zn-air batteries - Peng-Fei Xie; Hao Hu; Lingzhe Fang; Xiaohua Yu; Ju Rong; Xiaoyi Qiu; Feng Wu; Tao Li; Minhua Shao; Jin-Cheng Li (Chemical Engineering Journal, 2024)

Novel tri-solvent amines absorption for flue gas CO2 capture: Efficient absorption and regeneration with low energy consumption - Guanghuan Li; Xuehua Shen; Xianfeng Jiao; Feng Xie; Jiali Hua; Han Lin; Feng Yan; Hao Wu; Zuotai Zhang (Chemical Engineering Journal, 2024)

Association Between Multiple Metal(loid)s Exposure and Blood Lipid Levels: Evidence from a Cross-Sectional Study of Southeastern China - Guihua Du; Xiaoguang Song; Fankun Zhou; Lu Ouyang; Qi Li; Shiying Ruan; Rui Su; Shaoqi Rao; Yanhui Zhu; Jie Xie; Chang Feng; Guangqin Fan (Biological Trace Element Research, 2024)

Effect of abamectin on osmoregulation in red swamp crayfish (Procambarus clarkii) - Guan Tianyu; Zhu QianQian; Zhu Jingyuan; Wang Long; Chang Guoliang; Xie Peng; Feng Jianbin; Wang Hui; Li Jiale (Environmental Science and Pollution Research, 2024)

Microstructure evolution of coarse-grained soil fillers during subgrade compaction-operation period based on CT technology - Kang Xie; Tai-feng Li; You-ming Zhao; Xiao-bin Chen; Qian-li Zhang (Transportation Geotechnics, 2024)

Overexpression of the grape β-galactosidase gene VvBGAL3 delays the softening and extends the shelf life of tomato fruits - Shanshan He; Hongli Wei; Zhirui Xue; Meng Li; Jiannan Xie; Jiakang Qian; Xing Chen; Zhiqian Li; Chang He; Bin Tan; Xianbo Zheng; Jun Cheng; et al. (Postharvest Biology and Technology, 2024)

Experimental investigation on compressive dwell fatigue behavior of titanium alloy pressure hull for deep-sea manned submersibles - Lei Wang; Cong Ye; Chengqi Sun; Shichao Feng; Xiaozhong Xie; Yuan Gao; Kun Zhao; Yanqing Li; Zhengquan Wan (Ocean Engineering, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

A CNN-SVR model for NO2 profile prediction based on MAX-DOAS observations: The influence of Chinese New Year overlapping the 2020 COVID-19 lockdown on vertical distributions of tropospheric NO2 in Nanjing, China - Xin Tian; Zijie Wang; Pinhua Xie; Jin Xu; Ang Li; Yifeng Pan; Feng Hu; Zhaokun Hu; Mingsheng Chen; Jiangyi Zheng (Journal of Environmental Sciences, 2024)

Indole-3-acetic acid regulating the initial adhesion of microalgae in biofilm formation - Zhihuai Xie; Zixuan Ou; Meili Zhang; Guotao Tang; Xiaoshi Cheng; Wangbei Cao; Jingyang Luo; Fang Fang; Yingqiang Sun; Ming Li; Juan Cai; Qian Feng (Environmental Research, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

“Edge in-situ heterogeneous” BiOI based on defect engineering and non-noble metal deposition: Boosting visible-light photocatalytic sterilization - Bangfeng Fu; Yifan Pan; Peng Zhao; Liang Zhang; Junchen Zhuo; Jianxing Feng; Bingzhi Li; Lenan Yao; Jiafeng Xi; Xi Lan; Linpin Luo; Ting Du; et al. (Chemical Engineering Journal, 2024)

A rapid and efficient Agrobacterium-mediated transient transformation system in grape berries - Jiannan Xie; Chang He; Zhiqian Li; Meng Li; Shanshan He; Jiakang Qian; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Jidong Li; Jiancan Feng; et al. (Protoplasma, 2024)

Sample data selection based on the feature subspace for photometric correction of the Chang'E-4 in situ observations - Jia Li; Chao Wang; Huan Xie; Xiaohua Tong; Yongjiu Feng; Xiong Xu; Sicong Liu (Advances in Space Research, 2024)

Presence of humic acid in the environment holds promise as a potential mitigating factor for the joint toxicity of polystyrene nanoplastics and herbicide atrazine to Chlorella vulgaris: 96-H acute toxicity - Mehdi Khoshnamvand; Dongmei You; Yafang Xie; Yixiao Feng; Marriya Sultan; Xingyi Wei; Jingli Li; Ailing Fu; De-Sheng Pei (Chemosphere, 2024)

Parent material influences soil properties to shape bacterial community assembly processes, diversity, and enzyme-related functions - Yu-Zhu Li; Xue-Lian Bao; Xue-Feng Zhu; Fang-Bo Deng; Ya-Li Yang; Yue Zhao; Hong-Tu Xie; Shi-Xin Tang; Cheng-Jun Ge; Chao Liang (Science of The Total Environment, 2024)

Removal of pesticide acetamiprid using KOH activated biochar derived from crayfish shell: Behavior and mechanism - Xiao-Wen Yao; Xie Chen; Man-Li Chen; Neng-Jia Feng; Lin-Yin Tong; Yun-Qiang Yi; Wei Qian; Zeng-Hui Diao (Process Safety and Environmental Protection, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

In-depth impact evaluation of binders on the mechanical properties and CO2 capture performance of CaO-based particles - Xuehua Shen; Ruiheng Zhang; Yiping Su; Han Lin; Feng Xie; Yingying Cai; Guanghuan Li; Jiali Hua; Feng Yan; Zewei Quan; Zuotai Zhang (Journal of Environmental Chemical Engineering, 2024)

Phase development in steelmaking slags during a gas quenching granulation process - Wen-Feng Gu; Jiang Diao; Li-Yuan Jiang; Hua-Fang Yu; Wen-Feng Tan; Lian Chen; Hong-Yi Li; Bing Xie; Shigeru Ueda (Journal of Environmental Chemical Engineering, 2024)

Investigation of the in vitro toxic effects induced by real-time aerosol of electronic cigarette solvents using microfluidic chips - Zezhi Li; Xiang Li; Boyang Feng; Junwei Zhao; Kejian Liu; Fuwei Xie; Jianping Xie (Food and Chemical Toxicology, 2024)

Highly elastic, fatigue-resistant, antibacterial, conductive, and nanocellulose-enhanced hydrogels with selenium nanoparticles loading as strain sensors - Xinling Nie; Yitong Xie; Xiaofeng Ding; Lili Dai; Feng Gao; Wancheng Song; Xun Li; Pei Liu; Zhongbiao Tan; Hao Shi; Chenhuan Lai; Daihui Zhang; et al. (Carbohydrate Polymers, 2024)

Residual networks without pooling layers improve the accuracy of genomic predictions - Zhengchao Xie; Xiaogang Xu; Ling Li; Cuiling Wu; Yinxing Ma; Jingjing He; Sidi Wei; Jun Wang; Xianzhong Feng (Theoretical and Applied Genetics, 2024)

Identification of individual plants carrying viruses or a viroid in Pyrus betulifolia seedlings and virus-tested pear mother plants by group testing - Feng Jiang; Hanwei Li; Yinshuai Xie; Jinying Wang; Hai Chi; Qing Kan; Shangzhen Yu; Tianzhong Li; Yuqin Cheng (Journal of Plant Diseases and Protection, 2024)

Recognition of autism spectrum disorder in children based on electroencephalogram network topology - Fali Li; Shu Zhang; Lin Jiang; Keyi Duan; Rui Feng; Yingli Zhang; Gao Zhang; Yangsong Zhang; Peiyang Li; Dezhong Yao; Jiang Xie; Wenming Xu; et al. (Cognitive Neurodynamics, 2024)

SNHG4-mediated PTEN destabilization confers oxaliplatin resistance in colorectal cancer cells by inhibiting ferroptosis - Si-qi Li; Wen-ting Xu; Yi-xin Yin; Hao-tang Wei; Ke-zhi Li; Ming-zhi Xie; Feng Lv; Li-ye Xie; Bang-li Hu (Apoptosis, 2024)

Autonomous prediction of rock deformation in fault zones of coal roadways using supervised machine learning - Feng Guo; Nong Zhang; Xiaowei Feng; Zhengzheng Xie; Yongle Li (Tunnelling and Underground Space Technology, 2024)

Spatiotemporal characteristics and drivers of ecosystem service interactions in the Dongting Lake Basin - Lige Yuan; Mingming Geng; Feng Li; Yonghong Xie; Tian Tian; Qian Chen (Science of The Total Environment, 2024)

Emergent energy dissipation in quantum limit - Hailong Li; Hua Jiang; Qing-Feng Sun; X.C. Xie (Science Bulletin, 2024)

Experimental study on removal of hydrogen sulfide gas by spray and bubble blowing: A comparative study - Hua Yang; Xiao Xiao Shi; Ji Feng Li; Jun Xie; Xuan Chen Liu; Lian Sheng Liu; Zi Yue Wang (Process Safety and Environmental Protection, 2024)

Early Cretaceous intrusive rocks in the Gangdese arc of southern Tibet do not support shallow subduction of the Neo-Tethyan oceanic lithosphere - Feng Wang; Qing Wang; Di-Cheng Zhu; Shi-Min Li; Peter A. Cawood; Rui-Qiang Wang; Jian-Kang Yi; Liang-Liang Zhang; Jin-Cheng Xie (Lithos, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Unraveling the photochemical behavior of dissolved organic matter derived from hydrothermal carbonization process water: Insights from molecular transformation and photoactive species - Huifang Xie; Qiaoqiao Li; Minli Wang; Yanfang Feng; Bingyu Wang (Journal of Hazardous Materials, 2024)

Study on window-opening behavior of suburban sustainable life-pattern in residential buildings at Donglu town of Hezhou, China - Jie Han; Nan Mo; Jingyi Cai; Xinyue Li; Fuhao Xie; You Peng; Tao Feng (Journal of Cleaner Production, 2024)

Correlation of Immune-Inflammatory Response System (IRS)/Compensatory Immune-Regulatory Reflex System (CIRS) with White Matter Integrity in First-Episode Patients with Schizophrenia - Mengzhuang Gou; Wei Li; Jinghui Tong; Yanfang Zhou; Ting Xie; Ting Yu; Wei Feng; Yanli Li; Song Chen; Baopeng Tian; Shuping Tan; Zhiren Wang; et al. (Molecular Neurobiology, 2024)

Methylated derivatives of polycyclic aromatic hydrocarbons in road dust, green belt soil and parking lot dust: occurrence, spatial distribution and emission sources - Jin-Nong Li; Ye Zhang; Jian-Xin Wang; Jie Hu; Xi-Mei Lu; Wen-Xi Xie; Zi-Feng Zhang; Zhong-Hua Tang (Environmental Geochemistry and Health, 2024)

Two new rakicidin derivatives from marine Micromonospora chalcea FIM-R160609 - Li Chen; Lijun Xie; Wei Zhao; Jian Zhou; Honglei Jiang; Wei Liu; Hong Jiang; Feng Lin (Natural Product Research, 2024)

Multimedia distribution, dynamics, and seasonal variation of PAHs in Songhua wetland: Implications for ice-influenced conditions - Bo Meng; Xi-Ze Min; Meng-Yuan Xiao; Wen-Xi Xie; Wen-Long Li; Ming-Gang Cai; Hang Xiao; Zi-Feng Zhang (Chemosphere, 2024)

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Vitamin E alleviates pyraclostrobin-induced toxicity in zebrafish (Danio rerio) and its potential mechanisms - Mengna Zhang; Hui Li; Mengyu Guo; Feng Zhao; Yao Xie; Zhongyu Zhang; Jingshu Lv; Lihong Qiu (Science of The Total Environment, 2024)

Vegetation types and flood water level are dominant factors controlling the carbon sequestration potential in Dongting Lake floodplain, China - Tao Wang; Zhengmiao Deng; Chengyi Zhang; Yeai Zou; Yonghong Xie; Feng Li; Fengjin Xiao; Changhui Peng (Science of The Total Environment, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Virtual-network-reconstruction-based underwater acoustic localization framework: Theory and experiment validation - Feng Liu; Huifang Chen; Yida Li; Lei Xie (Ocean Engineering, 2024)

Investigation of the cyclic separation of dioxins from municipal solid waste incineration fly ash by using fat - Jun Liu; Zhengdong Wang; Zhenlin Li; Guangming Xie; Weizhuo Zhang; Hesong Jin; Feng Xing (Journal of Cleaner Production, 2024)

The enhanced performance of Chlorococcum sphacosum in rich carbon wastewater treatment under the influence of calcium ion - Yi Zhang; Huifen Li; Xudong Liu; Jia Feng; Shulian Xie; Junping Lv (Journal of Cleaner Production, 2024)

The removal mechanisms of HF and HCl gases using Mg-Al adsorbent prepared by sol-gel synthesis method - Peng Gao; Jiayu Feng; Yuxuan Xie; Xinyu Yang; Ping Ning; Xin Sun; Fei Wang; Lei Shi; Jie Zhao; Kai Li (Journal of Environmental Chemical Engineering, 2024)

Exploring correlations between soy sauce components and the formation of thermal contaminants during low-salt solid-state fermentation - Feng Li; Yuting Wang; Hongxia Liao; You Long; Qiang Yu; Jianhua Xie; Yi Chen (Food Research International, 2024)

Degradation of Aflatoxin B1 by the Armillariella tabescens-derived aldo-keto reductase AtAKR - Tianyang Jiang; Feifei Li; Feng Li; Chunfang Xie; Daling Liu; Dongsheng Yao (Food Bioscience, 2024)

Inulin alleviates perinatal 2-ethylhexyl diphenyl phosphate (EHDPHP) exposure-induced intestinal toxicity by reshaping the gut microbiota and suppressing the enteric-origin LPS/TLR4/NF-κb pathway in dams and pups - Xiu-Wen Li; Feng Qiu; Yi Liu; Jian-Zheng Yang; Li-Jian Chen; Jia-Hao Li; Jia-Li Liu; Clare Hsu; Long Chen; Jia-Hao Zeng; Xiao-Li Xie; Qi Wang (Environmental Pollution, 2024)

N, P codoped hollow carbon prisms for efficient oxidative dehydrogenation reaction with both enhanced activity and selectivity - Xuefei Zhang; Aoxue Hu; Shuchun Li; Ruiping Feng; Shuping Huang; Zailai Xie (Chemical Engineering Journal, 2024)

Development of targeted chloride-responsive Ag/Ca-MoO4-LDH for synergistic corrosion resistance - Mengzhu Chen; Haibing Zheng; Linwen Yu; Yuxin Cai; Qing-feng Liu; Zhijun Wang; Hui Xie; Weihua Li (Chemical Engineering Journal, 2024)

Research on the Control Technology and Key Parameters of External Anchor-Internal Unloading of Surrounding Rock During Gob-Side Entry Driving Under Severe Mining of 1000-m-Deep Mine - Shengrong Xie; Hui Li; Dongdong Chen; Shaohua Feng; Junhui Yang; Xiang Ma; Zaisheng Jiang; Shikun Xing (Rock Mechanics and Rock Engineering, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Analysis of the response to cigarette smoke exposure in cell coculture and monoculture based on bionic-lung microfluidic chips - Zezhi Li; Boyang Feng; Xiang Li; Junwei Zhao; Kejian Liu; Fuwei Xie; Jianping Xie (Analytica Chimica Acta, 2024)

Clinical epidemiology of adenovirus pneumonia among Chinese hospitalized children - Jiao Tian; Xinyu Wang; Qi Li; Linlin Zhang; Junhong Ai; Guoshuang Feng; Yueping Zeng; Ran Wang; Zhengde Xie (Archives of Microbiology, 2024)

The relationships between vertical variations of shallow gas and pore water geochemical characteristics in boreholes from the inner shelf of the East China Sea - Xue Li; Xiaoyong Duan; Xingliang He; Yongqing Xie; Lei Yang; Ping Yin; Ke Cao; Bin Chen; Fei Gao; Feng Li (Frontiers in Marine Science, 2024)
Shallow gas was widely recognized in the coastal region, especially in the estuarine delta areas with high organic matter (OM) burial flux. In this study, the vertical variations of shallow gas and the related geochemical indicators from two boreholes in the coastal region of the East China Sea (ECS) were investigated. Two gas-bearing layers were identified in the sediments from the Holocene and late Pleistocene series. Both boreholes exhibit a “typical” and an “inverse” Sulfate Methane Transition Zone (SMTZ). The “typical” SMTZs (SMTZ1 and SMTZ3) were in the upper part of the gas-bearing layers, where sulfate levels decrease and methane levels increase with depth. Conversely, the “inverse” SMTZs (SMTZ2 and SMTZ4) were in the lower part of the gas-bearing layers, exhibiting an increase in sulfate levels and a decrease in methane levels with depth, a phenomenon rarely documented in previous research. The downward variations of pore water geochemical characteristics indicates that these ions were related to Anaerobic Oxidation of Methane (AOM) processes. The increase in Ca 2+ and Ba 2+ concentrations and the gradual decrease in sulfate at the SMTZ reflect a series of biogeochemical processes resulting from the dissolution of carbonate and other minerals by AOM. The research indicates that sulfate in AOM may originate from multiple sources. Through analyzing the vertical distribution of shallow gas and the geochemical properties of pore water, this study elucidates the shallow gas formation mechanism and the features of the SMTZ, laying the groundwork for further investigations.

TRPA1-PI3K/Akt-OPA1-ferroptosis axis in ozone-induced bronchial epithelial cell and lung injury - Jiali Weng; Qi Liu; Chenfei Li; Yi Feng; Qing Chang; Meiqin Xie; Xiaohui Wang; Mengnan Li; Hai Zhang; Ruolin Mao; Na Zhang; Xiaohua Yang; et al. (Science of The Total Environment, 2024)

Manure derived hydrochar reduced phosphorus loss risk via an alteration of phosphorus fractions and diversified microbial community in rice paddy soil - Shudong Ding; Jing Li; Yu Wang; Shiying He; Huifang Xie; Haibin Fu; Yanfang Feng; Sabry M. Shaheen; Jörg Rinklebe; Lihong Xue (Science of The Total Environment, 2024)

High-temperature stress response: Insights into the molecular regulation of American shad (Alosa sapidissima) using a multi-omics approach - Mingkun Luo; Wenbin Zhu; Zhengyuan Liang; Bingbing Feng; Xudong Xie; Yulin Li; Ying Liu; Xiulan Shi; Jianjun Fu; Linghong Miao; Zaijie Dong (Science of The Total Environment, 2024)

Pd-CeO2 catalyst facilely derived from one-pot generated Pd@Ce-BTC for low temperature CO oxidation - Shaohua Xie; Wei Tan; Yuhan Xu; Chunying Wang; Yuan Feng; Kailong Ye; Lu Ma; Steven N. Ehrlich; Yaobin Li; Yan Zhang; Lin Dong; Jiguang Deng; et al. (Journal of Hazardous Materials, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

Effect of EDDS on the rhizosphere ecology and microbial regulation of the Cd-Cr contaminated soil remediation using king grass combined with Piriformospora indica - Haixiang Zhang; Kailu Zhang; Yali Duan; Xiaoyan Sun; Li Lin; Qianli An; Muhammad Mohsin Altaf; Zhiqiang Zhu; Fan Liu; Yangqiu Jiao; Jing Yin; Can Xie; et al. (Journal of Hazardous Materials, 2024)

S-scheme heterojunction and heterovalent ion doping synergistically promote the visible light photocatalytic performance of hierarchical nanoflowers - Hongwei Wu; Jie Li; Yuanli Li; Wei Feng; Xiaoyan Zhong; Sili Liu; Haifeng Liu; Na Li; Ruishi Xie (Journal of Cleaner Production, 2024)

Potential source and health risks of black carbon based on MERRA-2 reanalysis data in a typical industrial city of North China Plain - Hao Yu; Menghui Li; Xueqing Zheng; Mingyue Zhu; Zhensen Zheng; Tianyi Xie; Guangxuan Yan; Pengtuan Hu; Zhiguo Cao; Jinglan Feng; Jianhui Sun (Journal of Environmental Management, 2024)

Biocontrol potential of volatile organic compounds produced by Streptomyces corchorusii CG-G2 to strawberry anthracnose caused by Colletotrichum gloeosporioides - Xiaojuan Li; Lu Zhang; Yankun Zhao; Junting Feng; Yufeng Chen; Kai Li; Miaoyi Zhang; Dengfeng Qi; Dengbo Zhou; Yongzan Wei; Wei Wang; Jianghui Xie (Food Chemistry, 2024)

Variations of entries and bolting technologies, a case study based on a field monitoring of a longwall face - Feng Guo; Nong Zhang; Xiaowei Feng; Zhengzheng Xie; Changliang Han; Yongle Li; Qinghua Chen; Guoli Ding (Engineering Geology, 2024)

Chemical engineering solution for carbon neutrality in cement industry: Tailor a pathway from inevitable CO2 emission into syngas - Bin Shao; Yuanming Zhu; Jun Hu; Yuan Zong; Zhicheng Xie; Su Li; Wenli Du; Meihong Wang; Honglai Liu; Feng Qian (Chemical Engineering Journal, 2024)

Biochar loaded with ferrihydrite and Bacillus pseudomycoides enhances remediation of co-existed Cd(II) and As(III) in solution - Rui Cao; Guodong Kang; Weiwen Zhang; Jihai Zhou; Wangliang Xie; Zhenzhen Liu; Li Xu; Feng Hu; Zhen Li; Huixin Li (Bioresource Technology, 2024)

Effects of chronic abamectin stress on growth performance, digestive capacity, and defense systems in red swamp crayfish (Procambarus clarkii) - Tianyu Guan; Long Wang; Meng Hu; Qianqian Zhu; Lin Cai; Yurui Wang; Peng Xie; Jianbin Feng; Hui Wang; Jiale Li (Aquatic Toxicology, 2024)

Distribution and characteristics of microplastics in 16 benthic organisms in Haizhou Bay, China: Influence of habitat, feeding habits and trophic level - Siqi Xie; Kexin Song; Shiwei Liu; You Li; Jiaxuan Wang; Wei Huang; Zhihua Feng (Marine Pollution Bulletin, 2024)

Assessing the impact of water-sediment factors on water quality to guide river-connected lake water environment improvement - Mingming Geng; Zhan Qian; Heng Jiang; Bing Huang; Shuchun Huang; Bo Deng; Yi Peng; Yonghong Xie; Feng Li; Yeai Zou; Zhengmiao Deng; Jing Zeng (Science of The Total Environment, 2024)

Screening the phytotoxicity of micro/nanoplastics through non-targeted metallomics with synchrotron radiation X-ray fluorescence and deep learning: Taking micro/nano polyethylene terephthalate as an example - Hongxin Xie; Chaojie Wei; Wei Wang; Rui Chen; Liwei Cui; Liming Wang; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2024)

The occurrence of pollutants in organisms and water of inland mariculture systems: Shrimp aquaculture is a procession of Microplastics accumulation - Kexin Song; Siqi Xie; Changwen Li; Jincheng He; Wei Jin; Rui Wang; Wei Huang; Pingjing Li; Zhihua Feng (Environmental Pollution, 2024)

Unraveling fluorescent mechanism of biomass-sourced carbon dots based on three major components: Cellulose, lignin, and protein - Tian-xiang Li; De-fang Zhao; Lin Li; Yang Meng; Yu-hui Xie; Dong Feng; Feng Wu; Delong Xie; Yuxin Liu; Yi Mei (Bioresource Technology, 2024)

Bufogarlides A-C, three new bufadienolides with Δ 14,15 double bond from the skins of Bufo bufo gargarizans - Lingjie Meng; Qinghong Kong; Jianxun Xie; Feng Pan; Keyu Lu; Sanhua Li; Yiling Li; Di Zhang; Yun Liu (Natural Product Research, 2024)

TET1 Regulates Proliferation of Mouse Skin-Derived Stem Cells In Vitro - Tian Qiao; Li Li; Ming-Xin Zang; Yi-Nuo Jiang; Sha-Sha Wang; Chun-Xiao Li; Xin-Xiang Xie; Geng Zhang; Ying Zhang; Wei Ge; Wei Shen; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2024)

Protecting China’s major urban bird diversity hotspots - Li Li; Mingxiao Yan; Yixuan Hong; Weijia Feng; Dong Xie; Emilio Pagani-Núñez (Ambio, 2024)
The Kunming-Montreal Global Biodiversity Framework puts forward a new conservation target to enhance urban biodiversity. Cities have a great potential for sustaining biodiversity and nurturing a healthy relationship between people and our nearest nature. It is especially important in developing countries such as China, which has a rich biodiversity and a rapidly growing urban population. Using citizen science data, we show that 48% of the national bird diversity and 42% of its threatened species have been recorded in the top-20 most avian-diverse cities of China. Urban bird diversity hotspots clustered along the eastern coast, indicating the importance of establishing an inter-city conservation network along the East Asian-Australasian Flyway. This urban conservation network would be a starting point to promote social recognition of biodiversity’s relational value in a country with a vast population and an increasingly important role in meeting UN’s Sustainable Development Goals.

Optimizing biochar application rates for improved soil chemical environments in cotton and sugarbeet fields under trickle irrigation with plastic mulch - Xingyun Qi; Guang Yang; Yi Li; Zhenan Hou; Penghui Shi; Shibin Wang; Xiaofang Wang; Jiaping Liang; Benhua Sun; Kadambot H.M. Siddique; Shufang Wu; Hao Feng; et al. (Soil and Tillage Research, 2024)

Liquid crystal monomers in soils near the e-waste recycling site and liquid crystal display manufacturer: Exponential decrease with distance - Jiong-Feng Xie; Gao-Ling Wei; Li-Xi Zeng; Liang-Ying Liu (Science of The Total Environment, 2024)

Integrated analysis of the transport process and source attribution of an extreme ozone pollution event in Hefei at different vertical heights: A case of study - Feng Hu; Pinhua Xie; Xin Tian; Jin Xu; Ang Li; Aurelia Lupaşcu; Tim Butler; Zhaokun Hu; YinSheng Lv; ZhiDong Zhang; Jiangyi Zheng (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Promoted micropollutant degradation and structural evolution of natural organic matter by a novel S(IV)-based water treatment strategy - Yuwei Xie; Wenzheng Chen; Haoran Li; Qi Zeng; Xin Yu; Mingbao Feng (Journal of Hazardous Materials, 2024)

Pressure–temperature–time path of ultrahigh-pressure metamorphic terranes constrained by zircon petrochronology: A case study of orthogneisses from the northern Sulu belt, China - Peng Feng; Hao Deng; Yang Zhang; Qing-Lin Sui; Hai-Yang He; Yan-Shi Xie; Liang Chen; Xian-Zhe Duan; Wen-Zhou Xiao; Xia-Wen Li; Nan Li (Journal of Asian Earth Sciences, 2024)

Co-pyrolysis of biomass with Red Mud: An efficient approach to improving bio-oil quality and resourceful utilization of the iron in Red Mud - Yuan Zhang; Yongshuai Wang; Hongyou Cui; Fang Wang; Zhihe Li; Changhua Sun; Yun Jia; Yujiao Xie; Feng Song; Jiangang Wang; Weiming Yi (Fuel, 2024)

Imbibition behavior of water on coal surface and the impact of surfactant - Qiming Huang; Yuting Yan; Gang Wang; Jingna Xie; Yifeng Huang; Mingyang Li; Bo Yu; Xu Feng (Fuel, 2024)

Impairment of Autophagic Flux After Hypobaric Hypoxia Potentiates Oxidative Stress and Cognitive Function Disturbances in Mice - Shuhui Dai; Yuan Feng; Chuanhao Lu; Hongchen Zhang; Wenke Ma; Wenyu Xie; Xiuquan Wu; Peng Luo; Lei Zhang; Fei Fei; Zhou Fei; Xia Li (Neuroscience Bulletin, 2024)
Acute hypobaric hypoxic brain damage is a potentially fatal high-altitude sickness. Autophagy plays a critical role in ischemic brain injury, but its role in hypobaric hypoxia (HH) remains unknown. Here we used an HH chamber to demonstrate that acute HH exposure impairs autophagic activity in both the early and late stages of the mouse brain, and is partially responsible for HH-induced oxidative stress, neuronal loss, and brain damage. The autophagic agonist rapamycin only promotes the initiation of autophagy. By proteome analysis, a screen showed that protein dynamin2 (DNM2) potentially regulates autophagic flux. Overexpression of DNM2 significantly increased the formation of autolysosomes, thus maintaining autophagic flux in combination with rapamycin. Furthermore, the enhancement of autophagic activity attenuated oxidative stress and neurological deficits after HH exposure. These results contribute to evidence supporting the conclusion that DNM2-mediated autophagic flux represents a new therapeutic target in HH-induced brain damage.

Isolation, identification, and induced differentiation of satellite cells from skeletal muscle of adult tree shrews - Shenghui Ke; Yiwei Feng; Liying Luo; Wanzhao Qin; Huayu Liu; Jingchong Nie; Beijiang Liang; Hongjie Ma; Mao Xie; Jingyu Li; Zhijie Niu; Guojian Li; et al. (In Vitro Cellular & Developmental Biology - Animal, 2024)

Combining a lung microfluidic chip exposure model with transcriptomic analysis to evaluate the inflammation in BEAS-2B cells exposed to cigarette smoke - Zezhi Li; Xiang Li; Boyang Feng; Jingxian Xue; Junwei Zhao; Qingqing Zhu; Kejian Liu; Fuwei Xie; Jianping Xie (Analytica Chimica Acta, 2024)

Stronger control of surface conductance by soil water content than vapor pressure deficit regulates evapotranspiration in an urban forest in Beijing, 2012–2022 - Xinhao Li; Tianshan Zha; T. Andrew Black; Xin Jia; Rachhpal S. Jassal; Peng Liu; Yun Tian; Chuan Jin; Ruizhi Yang; Feng Zhang; Haiqun Yu; Jing Xie (Agricultural and Forest Meteorology, 2024)

Numerical investigation of the electrostatic dust transport around a lunar lander - Lianghai Xie; Lei Li; Yiteng Zhang; Bin Zhou; Jindong Wang; Xiaoping Zhang; Yongyong Feng (Advances in Space Research, 2024)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Corrigendum to “Cardamine violifolia as a potential Hg hyperaccumulator and the cellular responses” [Sci. Total Environ., Volume 863(2023), 160940] - Liwei Cui; Xue Tian; Hongxin Xie; Xin Cong; Lihong Cui; Han Wu; Jianxu Wang; Bai Li; Jiating Zhao; Yanshan Cui; Xinbin Feng; Yu-Feng Li (Science of The Total Environment, 2023)

Carbonation of steel slag at low CO2 concentrations: Novel biochar cold-bonded steel slag artificial aggregates - Jun Liu; Canrong Zeng; Zhenlin Li; Guang Liu; Weizhuo Zhang; Guangming Xie; Feng Xing (Science of The Total Environment, 2023)

Hydrate formation significantly decreases the uplifting rate of methane bubble from the seafloor to the upper water column - Jingchun Feng; Yan Xie; Li Tang; Pian Li; Zhenwu Zhou; Si Zhang; Zhifeng Yang; Yi Wang (Science Bulletin, 2023)

Detection of Atlantic salmon residues based on computer vision - Yu Feng; Xinxing Li; Yinggang Zhang; Tianhua Xie (Journal of Food Engineering, 2023)

Green recycling of valuable metals from spent cathode materials by water electrolysis - Neng Wei; Yaqun He; Guangwen Zhang; Yi Feng; Jinlong Li; Zimeng Liu; Lixin Ding; Weining Xie (Journal of Environmental Chemical Engineering, 2023)

Adipocyte-derived exosomes promote the progression of triple-negative breast cancer through circCRIM1-dependent OGA activation - Yuehua Li; Baohong Jiang; Lijun Zeng; Yuanbin Tang; Xiaowen Qi; Zhixing Wan; Wenjie Feng; Liming Xie; Rongfang He; Hongbo Zhu; Yimou Wu (Environmental Research, 2023)

Is water resources management at the expense of deteriorating water quality in a large river-connected lake after the construction of a lake sluice? - Mingming Geng; Kelin Wang; Zhan Qian; Heng Jiang; Yunliang Li; Yonghong Xie; Feng Li; Youzhi Li; Yeai Zou; Zhengmiao Deng; Jing Zeng (Ecological Engineering, 2023)

Elucidation of the neutralizing antibody evasion of emergent SARS-CoV-2 Omicron sub-lineages using structural analysis - Cong Sun; Yuan-Tao Liu; Yin-Feng Kang; Chu Xie; Shu-Xin Li; Yu-Tong Lu; Mu-Sheng Zeng (Science China Life Sciences, 2023)

Microstructure Characteristics of Tectonic Coal and Primary Coal: A Case Study of Guizhou, China - Cong Feng; Xijian Li; Enyu Xu; Hao Sui; Feng Xue; Honggao Xie (Natural Resources Research, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Phylogeny and Geographical Derivation of Genus Hildenbrandia Based on Morphological and Molecular Evidence - Fangru Nan; Huiying Zhao; Juan Li; Xudong Liu; Qi Liu; Junping Lv; Jia Feng; Shulian Xie (Journal of Ocean University of China, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Influence of Air Pollution Exposures on Cardiometabolic Risk Factors: a Review - Li-Hao Guo; Mohammed Zeeshan; Guo-Feng Huang; Duo-Hong Chen; Min Xie; Jun Liu; Guang-Hui Dong (Current Environmental Health Reports, 2023)

Essential and non-essential elements in tuna and billfish around the world: Distribution patterns and influencing factors - Jingqian Xie; Qiang Wu; Ling Tao; Feng Wu; Shuyi Tu; Duofu Chen; Tian Lin; Tiejun Li (Marine Pollution Bulletin, 2023)

Change to the transcriptomic profile, oxidative stress, apoptotic and immunity in the liver of small yellow croaker (Larimichthys polyactis) under hypoxic stress - Jingqian Wang; Li Wang; Yang Liu; Chen Du; Congcong Hou; Qingping Xie; Daojun Tang; Feng Liu; Bao Lou; Junquan Zhu (Aquaculture, 2023)

How weather impacts the citizens' activity patterns in southern China? Enlightenment from large-scale mobile phone signaling data of Guangzhou - Yukai Zou; Weien Xie; Siwei Lou; Lei Zhang; Yu Huang; Dawei Xia; Xiaolin Yang; Chao Feng; Yilin Li (Urban Climate, 2023)

Occurrence, fate and potential health risks of antibiotic resistomes in a constructed wetlands-reservoir ecosystem for drinking water source improvement - Xuan Li; Jiahao Xie; Cheng Ding; Hongqiu Du; Shuhong Gao; Weixing Ma; Feng Liang; Haihan Zhang; Aijie Wang (Science of The Total Environment, 2023)

McPrA - A new gas profile inversion algorithm for MAX-DOAS and apply to 50 m vertical resolution - Jiangyi Zheng; Pinhua Xie; Xin Tian; Jin Xu; Ang Li; Bo Ren; Feng Hu; Zhaokun Hu; Yinsheng Lv; Zhidong Zhang; Wenqing Liu (Science of The Total Environment, 2023)

Field study on variation characteristics of PCDD/Fs and flue gas particles along MSW incinerator - Pengju Wang; Feng Yan; Feng Xie; Xuehua Shen; Xuankun Wei; Fan Qu; Yiping Su; Guodong Yang; Rigang Zhong; Zhongzheng Li; Lan Song; Zuotai Zhang (Process Safety and Environmental Protection, 2023)

Integrating suitable habitat dynamics under typical hydrological regimes as guides for the conservation and restoration of different waterbird groups - Pingyang Zhang; Siqi Zhang; Yeai Zou; Ting Wu; Feng Li; Zhengmiao Deng; Hong Zhang; Yucheng Song; Yonghong Xie (Journal of Environmental Management, 2023)

Urea-based magnetic porous organic frameworks as novel adsorbent for the enrichment of phenylurea herbicides in foods - Jinhua Li; Xiuli Xu; Feng Zhang; Wei Guo; Xiujuan Wang; Yun Xie; Feifang Zhang (Food Chemistry, 2023)

Effects of abamectin on nonspecific immunity, antioxidation, and apoptosis in red swamp crayfish (Procambarus clarkii) - Tianyu Guan; Jianbin Feng; Qianqian Zhu; Long Wang; Peng Xie; Hui Wang; Jiale Li (Fish & Shellfish Immunology, 2023)

Aeration intensity drives dissolved organic matter transformation and humification during composting by regulating the organics metabolic functions of microbiome - Ting Xie; Zhaohan Zhang; Yanling Yu; Yan Tian; Fei Wang; Dongyi Li; Jun Nan; Yujie Feng (Chemical Engineering Journal, 2023)

3D hierarchical fireproof gel polymer electrolyte towards high-performance and comprehensive safety lithium-ion batteries - Yirou Du; Xianshuai Liu; Lin Chen; Sihao Yin; Yuhui Xie; Ao Li; Xiaodong Liang; Yong Luo; Feng Wu; Yi Mei; Delong Xie (Chemical Engineering Journal, 2023)

Piezoelectric self-power supply driven by ferroelastic host–guest supramolecule with considerable electromechanical conversion capability - Meng-Meng Lun; Jia-Qi Luo; Zhi-Xu Zhang; Jie Li; Li-Yan Xie; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2023)

Improved sequential production of hydrogen and caproate by addition of biochar prepared from cornstalk residues - Jian Du; Pian-Pian Xu; Hong-Yu Ren; Guang-Li Cao; Guo-Jun Xie; Nan-Qi Ren; Bing-Feng Liu (Bioresource Technology, 2023)

Comparison and phylogeny on mitochondrial genome of marine and freshwater taxa of genus Hildenbrandia (Florideophyceae, Rhodophyta) - Fangru Nan; Juan Li; Jia Feng; Junping Lü; Qi Liu; Xudong Liu; Shulian Xie (Journal of Oceanology and Limnology, 2023)

Multifunctional dumbbell probes-based logic circuits: microRNAs logic detection and tumor cells identification - Xin Liu; Baiying Li; Qian Liu; Li Zhang; Rong Zhao; Di Wu; Luojia Wang; Zhongzhong Wang; Guoming Xie; Wenli Feng (Analytica Chimica Acta, 2023)

Positive relationships between species diversity and genetic diversity on a local scale at Mt. Wu Yi, China - Lei Xie; YueYao Feng; Rong Zhao; Ting Lv; NingJie Wang; Yao Li; Xiao Zheng; ShuiFei Chen; Hui Ding; YanMing Fang (Biodiversity and Conservation, 2023)

The role of high humidity on extreme-temperature-related mortality in central China - Peizhi Deng; Yan Li; Shenxin Li; Yuxin Feng; Donghui Jin; Yiping Yang; Yang Xie; Yao Lu; Qiuping Zhao; Hong Yuan (Air Quality, Atmosphere & Health, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Three new compounds from Anoectochilus roxburghii (Wall.) Lindl - Yan-Lin Bin; Shun-Zhi Liu; Ting-Ting Xie; Wen-Zheng Feng; Hao-Yang Li; Zi-Jia Ye; Zhi-Hao Dong; Ying-Kun Qiu (Natural Product Research, 2023)

Insight into the effect of a heavy metal mixture on neurological damage in rats through combined serum metabolomic and brain proteomic analyses - Jie Xie; Fankun Zhou; Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Shuo Yang; Jiajun Li; Xin Wan; Lingyu Yan; Peishan Liu; Hui Cheng; et al. (Science of The Total Environment, 2023)

The sulfate assimilation and reduction of marine microalgae and the regulation of illumination - Wen-Ying Dai; Lu Han; Pei-Feng Li; Qin-Dao Li; Li-Jun Xie; Chun-Ying Liu; Jun-Ru Kong; Ru Jia; Dan-Yang Li; Gui-Peng Yang (Marine Environmental Research, 2023)

Photo-assisted “co-movement catalysis”: CoFe2O4/CNS heterojunction based portable electrochemical sensor for simultaneous detection of Pb2+ and Cd2+ in natural water - Fengqian Xie; Feng Tang; Xinli Li; Xiaoran Wu; Shujun Wang; Hongqiang Xie; Ping Wang; Yueyun Li; Qing Liu (Journal of Hazardous Materials, 2023)

Remediation potential of magnetic biochar in lead smelting sites: Insight from the complexation of dissolved organic matter with potentially toxic elements - Wenshun Ke; Zheng Liu; Feng Zhu; Yi Xie; William Hartley; Xue Li; huan Wu; Shengguo Xue (Journal of Environmental Management, 2023)

Performance and mechanism of sulfite mediated oxidation of organic contaminants using iron(III) titanium oxide as catalyst - Juntao Guo; Wenyu Wang; Shenhao Xie; Yihui Zhang; Jinjun Li; Jing Xu; Feng Wu (Journal of Environmental Chemical Engineering, 2023)

Neoproterozoic tectonic transition from subduction to back-arc extension along the western Yangtze Block, South China: Petrological evidence of Nb-enriched basalts and arc-type intrusive rocks - Yu Zhu; Shao-cong Lai; Wan-li Xie; Jiang-feng Qin; Ren-zhi Zhu; Shao-wei Zhao; Min Liu; Fang-yi Zhang; Ze-zhong Zhang; Hang Yang (Gondwana Research, 2023)

Kinetics study on the catalytic recombination of non-premixed hydrogen–oxygen system: Effects of initial temperature, oxygen flow rate, and hydrogen diffusion time - Xuan Li; Si-Yuan Zhou; Jing Zhang; Zhuo-Wei Guo; Man-Qi Guan; Bin Li; Dan Zhang; Yong-Xu Wang; Li-Feng Xie (Fuel, 2023)

Spatial and temporal distribution of environmental microbiota in Chinese rice wine (Huangjiu) natural fermentation wineries - Qi Peng; Xueping Chen; Huajun Zheng; Kai Meng; Jianjiang Wu; Guangfa Xie; Lili Zhang; Xinxin Feng; Linyuan Li; Shunan Fang; Yuhao Zhang; Hefeng Yu (Food Bioscience, 2023)

Effects of environmental disinfection on microbial population and resistance genes: A case study of the microecology within a panda enclosure - Min Yan; Chunzhong Xu; Caiwu Li; Yongqi Feng; Juntang Duan; Ke Zhao; Daifu Wu; Guo Li; Shengzhi Yang; Xinfeng Han; Yue Xie; Yan Huang; et al. (Environmental Research, 2023)

Energy analysis of wind-induced wave and current during typhoon kalmaegi - Feng Zhang; Lei Wang; Chongwei Zheng; Kenny Thiam Choy Lim Kam Sian; Shaoping Shang; Hengyou Lan; Zhijie Jiang; Yundong Li; Han Zhang; Zhigang He; Guomei Wei; Yanshuang Xie; et al. (Estuarine, Coastal and Shelf Science, 2023)

Synergistic activation of anionic redox through substitution strategy to design low-cost Co/Ni-free layered oxide cathode materials for high-performance Na-ion batteries - Ting-Ting Wei; Ying Li; Yu-Hao Chen; Peng-Fei Wang; Ying Xie; Ting-Feng Yi (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

The effect of pore structure in ethane-selective metal-organic frameworks for ethylene purification - Feng Xie; Jiaqi Liu; Wells Graham; Saif Ullah; Eder Moisés Cedeño Morales; Kui Tan; Timo Thonhauser; Hao Wang; Jing Li (Chemical Engineering Journal, 2023)

Hippocampal LIMK1-mediated Structural Synaptic Plasticity in Neurobehavioral Deficits Induced by a Low-dose Heavy Metal Mixture - Fankun Zhou; Lu Ouyang; Qi Li; Shuo Yang; Sisi Liu; Han Yu; Qiyue Jia; Shaoqi Rao; Jie Xie; Guihua Du; Chang Feng; Guangqin Fan (Molecular Neurobiology, 2023)

Time-lag effects of flood stimulation on methane emissions in the Dongting Lake floodplain, China - Tao Wang; Zhengmiao Deng; Yonghong Xie; Buqing Wang; Shaoan Wu; Feng Li; Wei Wang; Yeai Zou; Xu Li; Zhiyong Hou; Jing Zeng; Mei Wang; et al. (Agricultural and Forest Meteorology, 2023)

Description of a natural infection with decapod iridescent virus 1 in farmed swimming crab - Liang Qiu; Xiao-Meng Guo; Guo-Si Xie; Yong-Hui Feng; Jing-Yi Xing; Chen Li; Bing Yang; Jie Huang (Aquaculture, 2023)

Proteomic profiling of purified avian leukosis virus subgroup J particles - Sheng Chen; Yiming Yan; Liguo Gao; Shuang Gao; Keyu Feng; Hongxin Li; Xinheng Zhang; Weiguo Chen; Feng Chen; Qingmei Xie (Veterinary Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Diverse diterpenoids from Callicarpa rubella Lindl. as natural inhibitors of macrophage foam cell formation - Xue-Wen Wu; Qian-Lang Feng; Yi-Fan Xie; Si-Chen Song; Bin Cheng; Yan Ma; Qing Li; Xu Ji; Xiao-Li Li; Guang Cao; Wei-Lie Xiao (Phytochemistry, 2023)

Concrete improvement incorporating recycled powder and aggregates treated via a combination of calcination and carbonation: The impact behaviors - Yuan Feng; Jianglin Li; Baifa Zhang; Huanchang Fu; Wei Chen; Zixin Xue; Zhongyu Lu; Jian Yang; Jianhe Xie (Journal of Cleaner Production, 2023)

Synthesis of geopolymer using municipal solid waste incineration fly ash and steel slag: Hydration properties and immobilization of heavy metals - Jun Liu; Guangming Xie; Zhengdong Wang; Zhenlin Li; Xu Fan; Hesong Jin; Weizhuo Zhang; Feng Xing; Luping Tang (Journal of Environmental Management, 2023)

Molecular characterization and expression of twenty interleukin-17 transcripts in the common Chinese cuttlefish (Sepiella japonica) in response to Vibrio harveyi infection - Xu Zhou; Pei-Xuan Fang; Hui-Min Cao; Jian-Jun Xie; Shuang Li; Chang-Feng Chi (Fish & Shellfish Immunology, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

The induction of ferroptosis by KLF11/NCOA4 axis: the inhibitory role in clear cell renal cell carcinoma - Zi-Qi Zhou; Xi Lv; Shi-Bo Liu; Hong-Chen Qu; Qing-Peng Xie; Long-Feng Sun; Gang Li (Human Cell, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Association between multiple metal(loid)s exposure and renal function: a cross-sectional study from southeastern China - Guihua Du; Xiaoguang Song; Fankun Zhou; Lu Ouyang; Qi Li; Shiying Ruan; Shuo Yang; Shaoqi Rao; Xin Wan; Jie Xie; Chang Feng; Guangqin Fan (Environmental Science and Pollution Research, 2023)

A multi-arm robot system for efficient apple harvesting: Perception, task plan and control - Tao Li; Feng Xie; Zhuoqun Zhao; Hui Zhao; Xin Guo; Qingchun Feng (Computers and Electronics in Agriculture, 2023)

MaizeNetome: A multi-omics network database for functional genomics in maize - Jia-Wu Feng; Linqian Han; Hao Liu; Wen-Zhao Xie; Hanmingzi Liu; Lin Li; Ling-Ling Chen (Molecular Plant, 2023)

Environmentally-friendly foam-coating synthetic strategy for fabrics with robust superhydrophobicity, self-cleaning capability and flame retardance properties - Wei Li; Libing Yang; Xiaowen Xie; Kim Hoong Ng; Feng Xu; Chan Zheng; Zhiqi Zhang; Shuhui Li; Jianying Huang; Weilong Cai; Yuekun Lai (Chemical Engineering Journal, 2023)

Characteristics comparison of gaseous and particle-phase VOCs released by smoldering mosquito coils and their health risks - Shuhao Li; Zerong Hao; Hongling Shen; Feng Wang; Zongli Xie; Boxiong Shen; Fengju Lu (Atmospheric Pollution Research, 2023)

Effects of elevated temperature and acidification on sulfate assimilation and reduction of microalgae - Qin-Dao Li; Pei-Feng Li; Shan-Shan Duan; Chun-Ying Liu; Li-Jun Xie; Gui-Peng Yang (Journal of Applied Phycology, 2023)

Competition between Potamogeton malaianus and Hydrilla verticillata in response to different water level conditions - Xiangdong Liu; Zhiyong Hou; Feng Li; Yonghong Xie; Yang Li; Xiaoying Yu (Hydrobiologia, 2023)

Contrasting global patterns and trait controls of major mineral elements in leaf - Yajun Xie; Feng Li; Yonghong Xie (Global Ecology and Biogeography, 2023)
Aim Multiple mineral elements in leaf are the foundation of plant life and regulate many ecosystem functions. However, whether a common mechanism governs the variations of all leaf mineral elements is still unknown. Location Global. Time period 1970–2020. 10. Major taxa studied: Plants. Methods Here, we demonstrate the global‐scale biogeographic patterns of 12 major mineral elements (nitrogen, phosphorus, potassium, calcium, magnesium, sulphur, aluminium, iron, manganese, sodium, zinc and copper) by compiling a global data set including 2710 records of leaf mineral elements for 1073 species and of associated climate and soil indices. Results In general, like nitrogen and phosphorus, elements including potassium, calcium, magnesium, sodium and copper in leaf declined towards the equator, which supported both plant physiological hypothesis and soil substrate age hypotheses developed on the basis of nitrogen and phosphorus. By contrast, other elements responded to latitude in a contrary manner as nitrogen and phosphorus, in line with a competing mechanism, temperature–biogeochemistry hypothesis . Besides, plant functional types intrinsically differed in mineral concentrations, and to a certain extent, shifts of their composition in turn exacerbated the latitudinal patterns of respective elements as predicted by the species composition hypothesis . Main conclusions The fundamentally different dynamics and control mechanisms of patterns of some elements compared with those of nitrogen and phosphorus challenge the idea that common hypotheses can predict biogeographic patterns across all mineral elements; thus, current paradigms of element biogeochemical models and ecological plant nutrition require revision.

Gene-specific silencing of SlPL16, a pectate lyase coding gene, extends the shelf life of tomato fruit - Haozhan Ren; Qing Zhao; Youwei Feng; Peipei Tang; Yong Wang; Jun Jiang; Chunhua Hu; Yunxing Wang; Baolu Cui; Xiaodong Xie; Yan Li; Xuejie Zhao; et al. (Postharvest Biology and Technology, 2023)

Bisbenzylisoquinoline alkaloids from Plumula Nelumbinis inhibit vascular smooth muscle cells migration and proliferation by regulating the ORAI2/Akt pathway - Xiao Feng; Baoping Xie; Yuantao Han; Zhiying Li; Yuanyuan Cheng; Li-Wen Tian (Phytochemistry, 2023)

Light-driven micromotor swarm induced in-situ polymerization and synergistic photothermal therapy - Zeqi Li; Shaoming Fu; Huaan Li; Bin Chen; Dazhi Xie; Dongmei Fu; Ye Feng; Chao Gao; Suyi Liu; Daniela A. Wilson; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2023)

Carbon emissions from accumulated stock of building materials in China - Tianhao Liu; Rongqin Zhao; Zhixiang Xie; Liangang Xiao; Aijiu Chen; Wei Feng; Zengtao You; Mengyu Feng; Ruishi Li (Building and Environment, 2023)

Steroidal saponins from Allium chinense and their inhibitory effects on pancreatic lipase - Huili Xie; Xiaolei Shi; Bingzi Wang; Dexin Zhao; Zhiheng Sun; Yifu Chen; Yuezhu Feng; Yongri Jin; Xuwen Li (Phytochemistry Letters, 2023)

Two semi flexible nonplanar double Schiff bases as corrosion inhibitors for mild steel in HCl solution: Experimental and theoretical investigations - Xiaolong Li; Luo Chen; Bin Xie; Chuan Lai; Jiayu He; Jianshen Feng; Yugeng Yang; Runwu Ji; Mengnan Liu (Journal of Environmental Chemical Engineering, 2023)

A Review of Mercury Uptake, Transport and Bioaccumulation in Rice - Aiai Yang; Jingyun Feng; Hao Wang; Lingwei Cui; Guojing Xie; Hai Li; Xianwan Luo; Yingnan Xian (Water, Air, & Soil Pollution, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Microbial degradation of petroleum characteristic pollutants in hypersaline environment, emphasizing n-hexadecane and 2,4 di-tert-butylphenol - Shiling Liu; Wenjiao Yuan; Xiaolin Yang; Chengbin Li; Yishan Ji; Xin Feng; Meitong Li; Yuhong Xie (Environmental Monitoring and Assessment, 2023)

Carp stocking and climate change are potentially more important factors than nutrient enrichment driving water quality deterioration in subtropical freshwater lakes in China - Haojie Su; Jianfeng Chen; Yun Li; Qingyang Rao; Congqiang Luo; Xuwei Deng; Hong Shen; Renhui Li; Jun Chen; Yuanfeng Sun; Jiamin Pan; Suhui Ma; et al. (Limnology and Oceanography, 2023)
Freshwater lakes across the world have undergone dramatic changes in biological components and water quality over the past several decades. Previous studies focused on potential drivers mainly on nutrient enrichment in the catchment. However, the relative importance of climate change and the top‐down cascade effects of fish stocking on water quality is not fully understood. Here, by compiling 155 lakes data with four periods of field investigation in subtropical lakes in China, we found no significant changes in water total nitrogen and total phosphorus in the past two decades. However, the phytoplankton abundance increased significantly, and the water clarity declined by 44.1%. We further found that carp stocking and climate change are potentially more important than nutrients driving water quality change, which is also evidenced in two lakes (Lake Donghu and Qiandao) with long‐term monitoring histories. Specifically, carp stocking can decrease the water clarity directly by stirring up sediment and indirectly by trophic cascade along the food web. For climatic factors, mean annual temperature (MAT) has a positive effect on phytoplankton abundance, while mean annual precipitation has a negative one, with climates overall having little effect on water clarity. In addition, nutrient enrichment and climate change also have strong interactions with carp stocking, which may enhance the top‐down effects on water quality. Our findings highlight that either MAT or carp stocking may become an overwhelming driver of water clarity decline, which provides new insights into the conservation strategy for water quality management in the subtropical lakes in China.

Systematic characterisation of the effective components of five Callicarpa species with UPLC-Q-TOF-MS and evaluation of their anti-hyperuricaemic activity - Shixiu Feng; Luolin Wang; Li Deng; Min Zhang; Wenyu Ma; Xiangping Liang; Huichun Xie; Bo Yi (Natural Product Research, 2023)

Reduced cadmium toxicity in rapeseed via alteration of root properties and accelerated plant growth by a nitrogen-fixing bacterium - Shili Shen; Yinghan Li; Mingbiao Chen; Juan Huang; Feng Liu; Shijie Xie; Liping Kong; Ying Pan (Journal of Hazardous Materials, 2023)

Temperature uniformity of frozen pork with various combinations of fat and lean portions tempered in radio frequency - Xiangqing Chen; Feng Li; Juming Tang; Hu Shi; Jing Xie; Yang Jiao (Journal of Food Engineering, 2023)

Preparation of high-quality alkylated gasoline with low alkane-to-alkene ratio catalyzed by polyether-based Brønsted-Lewis acidic deep eutectic solvent - Ying-Bin Jiang; Feng-Li Yu; Bing Yuan; Cong-Xia Xie; Shi-Tao Yu (Fuel, 2023)

Cognitive outcomes caused by low-level lead, cadmium, and mercury mixture exposure at distinct phases of brain development - Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Yanhui Zhu; Guihua Du; Jie Xie; Fankun Zhou; Chang Feng; Guangqin Fan (Food and Chemical Toxicology, 2023)

MTA-YOLACT: Multitask-aware network on fruit bunch identification for cherry tomato robotic harvesting - Yajun Li; Qingchun Feng; Cheng Liu; Zicong Xiong; Yuhuan Sun; Feng Xie; Tao Li; Chunjiang Zhao (European Journal of Agronomy, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Identification of Heterophilic Epitopes of H1N1 Influenza Virus Hemagglutinin - Jing-ying Sun; Chun-yan Guo; Guo-rong Wang; Li-ting Yan; Qing Feng; Yan Li; Xue-ping Huo; Xin Xie; Jun Hu; Li-jun Sun (Current Microbiology, 2023)

Livestock manure-derived hydrochar is more inclined to mitigate soil Global Warming Potential than raw materials based on soil stoichiometry analysis - Yuanyuan Feng; Ning Wang; Huifang Xie; Jing Li; Guanlin Li; Lihong Xue; Haibin Fu; Yanfang Feng; Gerrard Eddy Jai Poinern; Deli Chen (Biology and Fertility of Soils, 2023)

A new insight into the low membrane fouling tendency of liquid-liquid hollow fiber membrane contactor capturing ammonia from human urine - Junhui Zhang; Kuiling Li; Mengfei Xie; Qi Han; Li Feng; Dan Qu; Liqiu Zhang; Ke Wang (Water Research, 2023)

NAC1 regulates root ground tissue maturation by coordinating with the SCR/SHR–CYCD6;1 module in Arabidopsis - Chuantian Xie; Cuiling Li; Fengxia Wang; Feng Zhang; Jiajia Liu; Junxia Wang; Xiansheng Zhang; Xiangpei Kong; Zhaojun Ding (Molecular Plant, 2023)

Conductive carrier promotes synchronous biofilm formation and granulation of anammox bacteria - Kun Feng; Yu Lou; Yitian Li; Baiyun Lu; Anran Fang; Guojun Xie; Chuan Chen; Defeng Xing (Journal of Hazardous Materials, 2023)

Process water from hydrothermal carbonization: The impacts on the aquatic dissolved organic matter feature and microbial network at the soil-water interface - Qiuyue Zhang; Bingyu Wang; Yanfang Feng; Yuanyuan Feng; Jing Li; Shudong Ding; Huayong He; Huifang Xie (Journal of Cleaner Production, 2023)

Efficient nitrogen removal through coupling biochar with zero-valent iron by different packing modes in bioretention system - Jiajie Chen; Yu Xie; Shanshan Sun; Manping Zhang; Pan Yan; Feng Xu; Li Tang; Shengbing He (Environmental Research, 2023)

Adsorption of heavy metals on biodegradable and conventional microplastics in the Pearl River Estuary, China - Min Shi; Qun Xie; Zhen-Liang Li; Yun-Feng Pan; Zhen Yuan; Lang Lin; Xiang-Rong Xu; Heng-Xiang Li (Environmental Pollution, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

The Characterization of Arabidopsis Photorespiration D-glycerate 3-Kinase Mutants Generated by CRISPR/Cas9 and Identification of Its Interacting Proteins - Yingjie Li; Zhengshiyu Lai; Weijun Wang; Qi Zhong; Feng Wu; Shuhan Yang; Biying Xie; Yawen Li; Wenting Sun; Xinxiang Peng; Xuewen Hou (Journal of Plant Growth Regulation, 2023)

Plant regeneration via callus-mediated organogenesis in commercial variety of Chuanbeichai No. 1 in Bupleurum chinense DC - Yuchan Li; Jun Zhao; Hua Chen; Xia Yu; Hui Li; Yu Zhang; Liang Feng; Zhe Wu; Wenlin Xie; Dabin Hou; Ma Yu (Plant Biotechnology Reports, 2023)

Environmental controls on carbon fluxes in an urban forest in the Megalopolis of Beijing, 2012-2020 - Peng Liu; Tianshan Zha; Feng Zhang; Xin Jia; Charles P.-A. Bourque; Yun Tian; Yujie Bai; Ruizhi Yang; Xinhao Li; Haiqun Yu; Jing Xie; Jun Mao (Agricultural and Forest Meteorology, 2023)

Adipose mesenchymal stem cells-derived exosomes alleviate osteoarthritis by transporting microRNA -376c-3p and targeting the WNT-beta-catenin signaling axis - Feng Li; Zhiming Xu; Zheng Xie; Xing Sun; Chengxiang Li; Yangyang Chen; Jianzhong Xu; Guofu Pi (Apoptosis, 2023)

Effects of Starvation on the Physiology and Liver Transcriptome of Yellowcheek (Elopichthys bambusa) - Min Xie; Shaoming Li; Zhifeng Feng; Jin Xiang; Qi Deng; Pengpeng Wang; Hao Wu; Jingwei Gao; Guoqing Zeng; Guangqing Xiang (Fishes, 2023)
Anthropogenic and extreme climate disasters cause ecological changes in natural rivers and lakes, increasing the risk of starvation in yellowcheek (Elopichthys bambusa). Therefore, the impact of starvation on the metabolism and wild population of yellowcheek should be explored. In this study, we used transcriptome sequencing technology to analyze the effects of short (8 d) and long-term (28 d) starvation on the liver transcriptome, growth, and serum indicators of yellowcheek. Our results showed that short-term starvation significantly reduced the visceral weight and viscera index of yellowcheek. Long-term starvation significantly reduced the body weight and Fulton’s condition factor, and it maintained significant reductions in visceral weight and viscera index. These results indicate that glycogen is the preferred energy source, rather than muscle protein, under starvation. Short-term starvation limited N-glycan and fatty acid biosynthesis, fatty acid elongation in the endoplasmic reticulum in the liver, and upregulated fatty acid degradation. However, long-term starvation alleviated the reduction in N-glycan and fatty acid biosynthesis caused by early starvation, and it significantly reduced fatty acid elongation in the mitochondria, as well as fatty acid degradation. These results provide important experiment information for assessing the starvation levels and nutritional status of wild yellowcheek.

Effect of feeding level on growth, digestive and metabolic enzymes and antioxidant capacity in juvenile Yangtze sturgeon (Acipenser dabryanus) - Bin He; Bo Zhou; Hang Xie; Zeng-Tan Hu; Bin Wang; Jun-Lin Zhang; Qing-Zhi Li; Feng-Qi Zhao; Xing Liu; Qian-Dong Li; Tao Yan (Aquaculture, 2023)

Obeticholic acid protects against methamphetamine-induced anxiety-like behavior by ameliorating microbiota-mediated intestinal barrier impairment - Jian-Zheng Yang; Kai-Kai Zhang; Jie-Tao He; Li-Jian Chen; Jin-Feng Ding; Jia-Li Liu; Jia-Hao Li; Yi Liu; Xiu-Wen Li; Dong Zhao; Xiao-Li Xie; Qi Wang (Toxicology, 2023)

Genome mining-guided activation of two silenced tandem genes in Raoultella ornithinolytica XF201 for complete biodegradation of phthalate acid esters - Nai-Xian Feng; Fei Zhang; Yunchang Xie; Hui Bin; Lei Xiang; Yan-Wen Li; Fantao Zhang; Yunhong Huang; Hai-Ming Zhao; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Science of The Total Environment, 2023)

Cardamine violifolia as a potential Hg hyperaccumulator and the cellular responses - Liwei Cui; Xue Tian; Hongxin Xie; Xin Cong; Lihong Cui; Han Wu; Jianxu Wang; Bai Li; Jiating Zhao; Yanshan Cui; Xinbin Feng; Yu-Feng Li (Science of The Total Environment, 2023)

Pregnancy and lactation mixed exposure to lead, cadmium, and mercury alters maternal-offspring single heavy metal load: A factorial design - Guihua Du; Fankun Zhou; Lu Ouyang; Kai Wang; Shaoqi Rao; Rui Su; Yanhui Zhu; Kechu Guo; Jinmei Xiao; Jie Xie; Qi Li; Chang Feng; et al. (International Journal of Hygiene and Environmental Health, 2023)

Co-Pyrolyzed Rice Husk and Cow Bone In Situ Cd-Remediation for Corn Plant Growth. A Comprehensive Case Study - Caiying Liu; Yanyan Liu; Jiapeng Feng; Yaru Li; Jun Tao; Xiaoxiao Xie (Water, Air, & Soil Pollution, 2023)

Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.

Role of extracellular polymeric substance in flocculation of Chlorococcum sphacosum cultivated with different initial inoculum concentrations in municipal wastewater - Huifen Li; Jin Liu; Chunqi Jia; Jia Feng; Xudong Liu; Shulian Xie; Junping Lv (Algal Research, 2023)

Bidirectional reflectance factor measurement of conifer needles with microscopic spectroscopy imaging - Yongkang Lai; Xihan Mu; Yuequn Bian; Xiaohan Dong; Feng Qiu; Xinyu Bo; Zhixiang Zhang; Yi Li; Xinli Liu; Linyuan Li; Donghui Xie; Guangjian Yan (Agricultural and Forest Meteorology, 2023)

Evolution of woody plants to the land‐sea interface – The atypical genomic features of mangroves with atypical phenotypic adaptation - Wei Xie; Zixiao Guo; Jiayan Wang; Ziwen He; Yulong Li; Xiao Feng; Cairong Zhong; Suhua Shi (Molecular Ecology, 2023)
How plants adapt and diverge in extreme environments is a key question of plant evolution and ecology. Mangrove invasion of intertidal environments is facilitated by adaptive phenotypes such as aerial roots, salt‐secreting leaf, and viviparity, and genomic mechanisms including whole genome duplication and transposable element number reduction. However, a number of mangroves lack these typical phenotypes. The question we ask is whether these phenotypically atypical mangroves also have distinct genomic features? The sibling mangrove species Lumnitzera littorea and Lumnitzera racemosa provide a model to study this question. We sequenced and assembled their genomes to chromosome level, together with a closely related species Combretum micranthum . While most mangroves have small genomes, the genomes of both Lumnitzera species are large (1443 and 1317 Mb) and carry a high proportion of repeat sequences (~75%). Moreover, Lumnitzera species have not undergone post‐gamma whole‐genome duplications. Their genome size increased mainly due to the expansion of repeat sequences in their ancestors. However, Lumnitzera genomes have reduced transposable elements by constraining the proliferation of new LTR‐RTs. Meanwhile, the two species have more gene families contracted than expanded, and some gene families with reversed size change may underlie their differentiation in root morphology and local distribution. We identified 86 chromosomal inversions, five of which are measured between 6.5 and 12.8 megabases. A number of genes located in these inversions function in pigment biosynthesis, a process likely involved in flower colour differentiation between the Lumnitzera species. We conclude that the mangroves with atypical phenotypes also have atypical genomic evolution.

The galU gene is required for in vivo survival of pseudomonas plecoglossicida in large yellow croaker ( Larimichthys crocea ) - Feng‐Ling Shu; Li‐Yun Jin; Hao Liu; Zhen Tao; Fei Yin; Jia‐Song Xie; Su‐Ming Zhou (Journal of Fish Diseases, 2023)
Pseudomonas plecoglossicida is an important pathogenic bacterium in aquaculture that causes visceral granulomas in large yellow croaker ( Larimichthys crocea ). Uridine diphosphate glucose phosphorylase encoded by galU plays a key role in biosynthesis of the bacterial envelope, particularly lipopolysaccharide and the capsule. In this study, we inactivated the galU gene in the P. plecoglossicida isolate XSDHY‐P. The galU mutant strain showed impaired growth in the early exponential stage and lacked the O polysaccharide side chain in lipopolysaccharide, but almost no defect in biofilm formation was detected. The galU mutant strain also exhibited significantly more sensitivity to the bactericidal action of normal fish serum mediated by the complement system compared to the wild‐type strain. In a cell model originating from the head kidney of large yellow croaker, the galU mutant strain showed lower capacities of adhesion, invasion, and intracellular survival compared to the wild‐type strain. In addition, the deficiency of the galU mutant drastically decreased bacterial loads in tissues and attenuated P. plecoglossicida virulence in fish. These results suggest that the galU gene of P. plecoglossicida is required for in vivo survival in large yellow croaker.

Transcriptome, Proteome, Histology, and Biochemistry Analysis of Oriental River Prawn Macrobrachium nipponense under Long-term Salinity Exposure - Yaoran Fan; Xiao Wu; Feiyue Ling; Zefei Wang; Keyi Ma; Nan Xie; Juanying Li; Jianbin Feng; Jiale Li (Frontiers in Marine Science, 2023)
Salinity is an ecological factor affecting the physiology, survival, and distribution of crustaceans. Additionally, salinity fluctuation detrimentally affects the composition and biological process of crustaceans. As a significant commercial aquaculture species in China, Japan, and Southeast Asian countries, the oriental river prawn, Macrobrachium nipponense, can tolerate a wide range of salinity. The transcriptome, proteome, histology, and physiology analysis were utilized to explore the physiological responses and molecular mechanisms of salinity tolerance in M. nipponense . Through the three-month culture, the statistic of growth trait illustrated the relatively excellent performance of M. nipponense in low salinity, and the higher salinity exposure significantly affected the growth of M. nipponense . In terms of the histological analysis, the gills and hepatopancreas of M. nipponense suffered varying degrees of damage. Besides, the activities of the digestive, immune-related, and metabolic enzymes were calculated. These results indicated that salinity significantly influenced trypsin and amylase in hepatopancreas, especially in 14 ppt. The immune-related enzymes were activated in high salinity. Notably, the activity of metabolic enzymes was significantly low in 7 and 14 ppt, which testified that the 7 ppt to 14 ppt were near the isotonic point of M. nipponense . In gills, hepatopancreas, and muscle, high-throughput mRNA sequencing revealed 11356, 2227, and 1819 differentially expressed genes (DEGs) by comparing the 7, 14, and 21 ppt groups with the 0ppt group, respectively. The TMT-labeling proteome identified 439 and 230 differentially expressed proteins (DEPs) in gills and hepatopancreas through the comparison of the 7, 14, and 21 ppt groups to the 0 ppt group, respectively. Additionally, through the integration of transcriptome and proteome, several pathways related to salinity adaptation were enriched, including protein export, cGMP-PKG signaling pathway, Amino sugar and nucleotide sugar metabolism, and Glycine, serine and threonine metabolism. Besides, 16 up and down-regulated proteins and related DEGs were detected through KEGG enrichment analysis, including ETHE1, BIP, chitinase (E3.2.1.14), and SARDH. Notably, no significantly regulated proteins and related DEGs were recorded by the correlation of transcriptome and proteome of 0 ppt and 7 ppt in hepatopancreas. Thus, the optimum survival salinity of M. nipponense may range from 0 ppt to 7 ppt. Overall, these results may provide valuable insights into the mechanisms underlying the culture of M. nipponense in different salinity.

Improving the genome and proteome annotations of the marine model diatom Thalassiosira pseudonana using a proteogenomics strategy - Xiao-Huang Chen; Ming-Kun Yang; Yuan-Yuan Li; Zhang-Xian Xie; Shu-Feng Zhang; Mats Töpel; Shady A. Amin; Lin Lin; Feng Ge; Da-Zhi Wang (Marine Life Science & Technology, 2023)
Diatoms are unicellular eukaryotic phytoplankton that account for approximately 20% of global carbon fixation and 40% of marine primary productivity; thus, they are essential for global carbon biogeochemical cycling and climate. The availability of ten diatom genome sequences has facilitated evolutionary, biological and ecological research over the past decade; however, a complimentary map of the diatom proteome with direct measurements of proteins and peptides is still lacking. Here, we present a proteome map of the model marine diatom Thalassiosira pseudonana using high-resolution mass spectrometry combined with a proteogenomic strategy. In-depth proteomic profiling of three different growth phases and three nutrient-deficient samples identified 9526 proteins, accounting for ~ 81% of the predicted protein-coding genes. Proteogenomic analysis identified 1235 novel genes, 975 revised genes, 104 splice variants and 234 single amino acid variants. Furthermore, our quantitative proteomic analysis experimentally demonstrated that a considerable number of novel genes were differentially translated under different nutrient conditions. These findings substantially improve the genome annotation of T. pseudonana and provide insights into new biological functions of diatoms. This relatively comprehensive diatom proteome catalog will complement available diatom genome and transcriptome data to advance biological and ecological research of marine diatoms.

Resource utilization of hazardous solid waste blast furnace dust: Efficient wet desulfurization and metal recovery - Xuejin Yang; Binghua Xie; Fang Wang; Ping Ning; Kai Li; Lijuan Jia; Jiayu Feng; Futing Xia (Chemosphere, 2023)

How will warming affect the growth and body size of the largest extant amphibian? More than the temperature–size rule - Wei Zhu; Tian Zhao; Chunlin Zhao; Cheng Li; Feng Xie; Jiongyu Liu; Jianping Jiang (Science of The Total Environment, 2023)

Manganese-induced α-synuclein overexpression promotes the accumulation of dysfunctional synaptic vesicles and hippocampal synaptotoxicity by suppressing Rab26-dependent autophagy in presynaptic neurons - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Yu Deng; Xin Li; Bin Xu (Science of The Total Environment, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Citrobacter portucalensis Sb-2 contains a metalloid resistance determinant transmitted by Citrobacter phage Chris1 - Yanshuang Yu; Zhenchen Xie; Jigang Yang; Ruixiang Yang; Yuanping Li; Yongguan Zhu; Yanlin Zhao; Qiue Yang; Jichen Chen; Hend A. Alwathnani; Renwei Feng; Christopher Rensing; et al. (Journal of Hazardous Materials, 2023)

Efficient biodegradation of tris-(2-chloroisopropyl) phosphate by a novel strain Amycolatopsis sp. FT-1: Process optimization, mechanism studies and toxicity changes - Mi Feng; Yantian Xie; Wei Mao; Yanqin Lu; Yanwu Wang; Haixia Li; Chenhao Zhang (Journal of Hazardous Materials, 2023)

Catalytic pyrolysis of 5-Amino-1H-Tetrazole with copper and its oxide: A deep insight into the combustion mechanism for high nitrogen compound - Si-Yuan Zhou; Jiu Chen; Xuan Li; Fan Jia; Dan Zhang; Li-Feng Xie; Bin Li; Lin Jiang (Fuel, 2023)

The toxicity of nano polyethylene terephthalate to mice: Intestinal obstruction, growth retardant, gut microbiota dysbiosis and lipid metabolism disorders - Xiaoying Lin; Hongxin Xie; Yanfei Zhang; Xue Tian; Liwei Cui; Nianqiu Shi; Liming Wang; Jiating Zhao; Lihui An; Jing Wang; Bai Li; Yu-Feng Li (Food and Chemical Toxicology, 2023)

Effects of polystyrene nanoplastics on the physiological and biochemical characteristics of microalga Scenedesmus quadricauda - Ru-ru Li; Bin-liang Wang; Fang-ru Nan; Jun-ping Lv; Xu-dong Liu; Qi Liu; Jia Feng; Shu-lian Xie (Environmental Pollution, 2023)

Nano mercury selenide as a source of mercury for rice - Hongxin Xie; Lina He; Xue Tian; Wei Zhang; Liwei Cui; Lihai Shang; Jiating Zhao; Bai Li; Yu-Feng Li (Environmental Pollution, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

Water-borne, durable and multicolor silicon nanoparticles/sodium alginate inks for anticounterfeiting applications - Jing Xie; Xuening Sun; Xin Guo; Xiang Feng; Kailong Chen; Xin Shu; Chenhao Wang; Wei Sun; Yang Liu; Bin Shang; Xin Liu; Dongzhi Chen; et al. (Carbohydrate Polymers, 2023)

Overexpression of maize GOLDEN2 in rice and maize calli improves regeneration by activating chloroplast development - Wanni Luo; Jiantao Tan; Tie Li; Ziting Feng; Zhi Ding; Xianrong Xie; Yuanling Chen; Letian Chen; Yao-Guang Liu; Qinlong Zhu; Jinxing Guo (Science China Life Sciences, 2023)

Dexmedetomidine alleviates acute lung injury by promoting Tregs differentiation via activation of AMPK/SIRT1 pathway - Zheng-tao Zhang; Ke Xie; Ren-jie Luo; Dan-ying Zhang; Zhi-wei He; Ke-feng Li; Shi-hui Lin; Fang Xu (Inflammopharmacology, 2023)

Development and application of a multiplex qPCR assay for the detection of duck circovirus, duck Tembusu virus, Muscovy duck reovirus, and new duck reovirus - Yan Wen Yin; Chenyong Xiong; Kai Chuang Shi; Shou Yu Xie; Feng Long; Jun Li; Min Zheng; Xian Kai Wei; Shuping Feng; Sujie Qu; Wenjun Lu; Hongjin Zhou; et al. (Virus Genes, 2023)

Spatial distributions of intra-community tree species under topographically variable conditions - Ting Lv; Rong Zhao; Ning-jie Wang; Lei Xie; Yue-yao Feng; Yao Li; Hui Ding; Yan-ming Fang (Journal of Mountain Science, 2023)

Retention of organic matter on the surface of illite particle under the influence of different cations: A molecular dynamics simulation study - Yuhang Xing; Xiong Li; Zhaodi Wu; Haotian Feng; Xin Xue; Liangchen Xie; Taoying Zhang; Jianguo Zhang (Applied Clay Science, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

Establishment of the first cell line from the small yellow croaker (Larimichthys polyactis) and its application in unraveling the mechanism of ROS-induced apoptosis under hypoxia - Jingqian Wang; Xinming Gao; Li Wang; Chen Du; Congcong Hou; Feng Liu; Qingping Xie; Bao Lou; Shan Jin; Junquan Zhu (Aquaculture, 2023)

Estimating the contribution of environmental variables to water quality in the postrestoration littoral zones of Taihu Lake using the APCS-MLR model - Dong Xie; Xin Li; Tingting Zhou; Yuqing Feng (Science of The Total Environment, 2023)

Combined effect of polystyrene microplastics and bisphenol A on the human embryonic stem cells-derived liver organoids: The hepatotoxicity and lipid accumulation - Wei Cheng; Yue Zhou; Yichun Xie; Yan Li; Ren Zhou; Hui Wang; Yan Feng; Yan Wang (Science of The Total Environment, 2023)

Minor iridoid glycosides from the fruits of Cornus officinalis Sieb. et Zucc. and their anti-diabetic bioactivities - Zhi-You Hao; Xiao-Lan Wang; Meng Yang; Bing Cao; Meng-Nan Zeng; Shi-Qi Zhou; Meng Li; Yan-Gang Cao; Shuang-Shuang Xie; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

GWAS-assisted genomic prediction of cadmium accumulation in maize kernel with machine learning and linear statistical methods - Huili Yan; Hanyao Guo; Wenxiu Xu; Changhua Dai; Wilson Kimani; Jianyin Xie; Hezifan Zhang; Ting Li; Feng Wang; Yijun Yu; Mi Ma; Zhuanfang Hao; et al. (Journal of Hazardous Materials, 2023)

Enhancing flotation removal of unburned carbon from fly ash by coal tar-based collector: Experiment and simulation - Kanghao Zheng; Wenjun Zhang; Yijiang Li; An Ping; Feng Wu; Guangyuan Xie; Wencheng Xia (Fuel, 2023)

Effect of multi-type oxides on the catalytic pyrolysis behaviors of 5-amino-1H-tetrazole - Jiu Chen; Quan Liu; Xian-Zhao Song; Si-Yuan Zhou; Bin Li; Li-Feng Xie; Guang-Cheng Yang; Cheng-Yan Cao; Song Lu; Dan Zhang (Fuel, 2023)

Experimental investigation on the temperature characteristics and hydrogen elimination effect of non-premixed hydrogen-oxygen recombination reaction at ambient temperature - Xuan Li; Jing Zhang; Si-Yuan Zhou; Bin Li; Dan Zhang; Li-Feng Xie (Fuel, 2023)

Relationship of multiple metals mixture and osteoporosis in older Chinese women: An aging and longevity study - Xiuming Feng; Gaohui Zan; Yue Wei; Xiaoting Ge; Haiqing Cai; Tianzhu Long; Lianguang Xie; Lei Tong; Chaoqun Liu; Longman Li; Lulu Huang; Fei Wang; et al. (Environmental Pollution, 2023)

Characteristics of non-point source pollution based on monitoring experiment in the Yingwugou small watershed, China - Kai Peng; Jia-ke Li; Gai-rui Hao; Yi-wen Liu; Xiang Zhou; Wei-feng Xie (Ecohydrology & Hydrobiology, 2023)

Optimization and understanding of ZnO nanoarray supported Cu-ZnO-Al2O3 catalyst for enhanced CO2 -methanol conversion at low temperature and pressure - Jiyu Sun; Fangyuan Liu; Usman Salahuddin; Mudi Wu; Chunxiang Zhu; Xingxu Lu; Bo Zhang; Binchao Zhao; Zhiqiang Xie; Yunjiang Ding; Dongsheng Li; Chang-Yong Nam; et al. (Chemical Engineering Journal, 2023)

Formation mechanism and metabolic pathways of photogranule in batch and continuous-flow mode under high salinity stress - Jing Zhu; Hong You; Zhipeng Li; Binghan Xie; Weirun Li; Shaojie Qi; Rui Wang; Hongying Chen; Binyu Ma; Yi Ding; Haili Tan; Feng Liu; et al. (Chemical Engineering Journal, 2023)

Salt Bridge-intermediated three phase decoupling electrolytes for high voltage electrolytic aqueous Zinc-Manganese dioxides battery - Qi Xu; Qi-Xing Xie; Tong Xue; Gao Cheng; Jian-Dong Wu; Lan Ning; Xiang-Hui Yan; You-Jun Lu; Zhong-Li Zou; Bei-Ping Wang; Feng-Lan Han (Chemical Engineering Journal, 2023)

Confining CoTe2-ZnTe heterostructures on petal-like nitrogen-doped carbon for fast and robust sodium storage - Ying Jiang; Feng Wu; Zhengqing Ye; Yaozong Zhou; Yan Chen; Yixin Zhang; Zekai lv; Li Li; Man Xie; Renjie Chen (Chemical Engineering Journal, 2023)

Outer membrane protein of OmpF contributes to swimming motility, biofilm formation, osmotic response as well as the transcription of maltose metabolic genes in Citrobacter werkmanii - Gang Zhou; Ying-Si Wang; Hong Peng; Hui-Zhong Liu; Jin Feng; Su-Juan Li; Ting-Li Sun; Cai-Ling Li; Qing-Shan Shi; Xiao-bao Xie (World Journal of Microbiology and Biotechnology, 2023)

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Diagnostic accuracy of autoverification and guidance system for COVID-19 RT-PCR results - Yingmu Cai; Mengyu Liu; Zhiyuan Wu; Cuihong Tian; Song Qiu; Zhen Li; Feng Xu; Wei Li; Yan Zheng; Aijuan Xu; Longxu Xie; Xuerui Tan (EPMA Journal, 2022)
Background To date, most countries worldwide have declared that the pandemic of COVID-19 is over, while the WHO has not officially ended the COVID-19 pandemic, and China still insists on the personalized dynamic COVID-free policy. Large-scale nucleic acid testing in Chinese communities and the manual interpretation for SARS-CoV-2 nucleic acid detection results pose a huge challenge for labour, quality and turnaround time (TAT) requirements. To solve this specific issue while increase the efficiency and accuracy of interpretation, we created an autoverification and guidance system (AGS) that can automatically interpret and report the COVID-19 reverse transcriptase-polymerase chain reaction (RT-PCR) results relaying on computer-based autoverification procedure and then validated its performance in real-world environments. This would be conductive to transmission risk prediction, COVID-19 prevention and control and timely medical treatment for positive patients in the context of the predictive, preventive and personalized medicine (PPPM). Methods A diagnostic accuracy test was conducted with 380,693 participants from two COVID-19 test sites in China, the Hong Kong Hybribio Medical Laboratory ( n = 266,035) and the mobile medical shelter at a Shanghai airport ( n = 114,658). These participants underwent SARS-CoV-2 RT-PCR from March 28 to April 10, 2022. All RT-PCR results were interpreted by laboratorians and by using AGS simultaneously. Considering the manual interpretation as gold standard, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy were applied to evaluate the diagnostic value of the AGS on the interpretation of RT-PCR results. Results Among the 266,035 samples in Hong Kong, there were 16,356 (6.15%) positive, 231,073 (86.86%) negative, 18,606 (6.99%) indefinite, 231,073 (86.86%, negative) no retest required and 34,962 (13.14%, positive and indefinite) retest required; the 114,658 samples in Shanghai consisted of 76 (0.07%) positive, 109,956 (95.90%) negative, 4626 (4.03%) indefinite, 109,956 (95.90%, negative) no retest required and 4702 (4.10%, positive and indefinite) retest required. Compared to the fashioned manual interpretation, the AGS is a procedure of high accuracy [99.96% (95%CI, 99.95–99.97%) in Hong Kong and 100% (95%CI, 100–100%) in Shanghai] with perfect sensitivity [99.98% (95%CI, 99.97–99.98%) in Hong Kong and 100% (95%CI, 100–100%) in Shanghai], specificity [99.87% (95%CI, 99.82–99.90%) in Hong Kong and 100% (95%CI, 99.92–100%) in Shanghai], PPV [99.98% (95%CI, 99.97–99.99%) in Hong Kong and 100% (95%CI, 99.99–100%) in Shanghai] and NPV [99.85% (95%CI, 99.80–99.88%) in Hong Kong and 100% (95%CI, 99.90–100%) in Shanghai]. The need for manual interpretation of total samples was dramatically reduced from 100% to 13.1% and the interpretation time fell from 53 h to 26 min in Hong Kong; while the manual interpretation of total samples was decreased from 100% to 4.1% and the interpretation time dropped from 20 h to 16 min at Shanghai. Conclusions The AGS is a procedure of high accuracy and significantly relieves both labour and time from the challenge of large-scale screening of SARS-CoV-2 using RT-PCR. It should be recommended as a powerful screening, diagnostic and predictive system for SARS-CoV-2 to contribute timely the ending of the COVID-19 pandemic following the concept of PPPM.

Exploring the mechanism of a novel recirculating aquaculture system based on water quality parameters and bacterial communities - Gengfeng Xiao; Xiangju Cheng; Dantong Zhu; Zhifei Li; Lijuan Feng; Xiaoming Peng; Zhuoyin Lu; Jun Xie (Environmental Science and Pollution Research, 2022)

Seasonal variability of eddy kinetic energy in the East Australian current region - Jia Liu; Shaojun Zheng; Ming Feng; Lingling Xie; Baoxin Feng; Peng Liang; Lei Wang; Lina Yang; Li Yan (Frontiers in Marine Science, 2022)
The East Australian Current (EAC) is an important western boundary current of the South Pacific subtropical Circulation with high mesoscale eddy kinetic energy (EKE). Based on satellite altimeter observations and outputs from the eddy-resolving ocean general circulation model (OGCM) for the Earth Simulator (OFES), the seasonal variability of EKE and its associated dynamic mechanism in the EAC region are studied. High EKE is mainly concentrated in the shear-region between the poleward EAC southern extension and the equatorward EAC recirculation along Australia's east coast, which is confined within the upper ocean (0-300 m). EKE in this area exhibits obvious seasonal variation, strong in austral summer with maximum (465±89 cm² s-²) in February and weak in winter with minimum (334±48 cm² s-²) in August. Energetics analysis from OFES suggests that the seasonal variability of EKE is modulated by the mixed instabilities composed of barotropic and baroclinic instabilities confined within the upper ocean, and barotropic instability (baroclinic instability) is the main energy source of EKE in austral summer (winter). The barotropic process is mainly controlled by the zonal shear of meridional velocities of the EAC southern extension and the EAC recirculation. The poleward EAC southern extension and the equatorward EAC recirculation are synchronously strengthened (weakened) due to the local positive (negative) sea level anomalies (SLA) under geostrophic equilibrium, and the barotropic instability dominated by zonal shear is enhanced (slackened), which results in a high (low) level of EKE in the EAC region.

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Boosting visible light photocatalysis in BiOI/BaFe12O19 magnetic heterojunction - Shan Feng; Taiping Xie; Deshun Kong; Fuling Yang; Tao Li; Junwei Yang; Meixin Liu; Haigang Du; Zhimin Su (Environmental Science and Pollution Research, 2022)

Risk Assessment of Wave Over-Topping Based on Smoothed-Particle Hydrodynamics Method - Lei Wang; Li Zhang; Yanshuang Xie; Yaozhao Zhong; Yuan Sun; Zhiyuan Wang; Feng Zhang; Shaoping Shang (Journal of Marine Science and Engineering, 2022)
FETSWCM-SWAN and DualSPHysics models are used to study the storm flooding process of Dazuo Seawall in Quanzhou city, Fujian province, China. Firstly, a storm over-topping assessment method is proposed. Secondly, the water level and storm wave at the foot of Dazuo Seawall calculated by FETSWCM-SWAN during the process of Typhoon Usagi in 2013 and Typhoon Dujuan in 2015. Finally, the typical wave and storm run-up processes at Dazuo Seawall are modeled by DualSPHysics. The results show that the typical wave run-up of Dazuo Seawall is less than 2 m, but the storm wave run-up can reach 6.85 m under Usagi. The risk is high when high tide is encountered. The risk of storm flooding is classified into three grades. This risk assessment could provide decision-making support to government departments in warning against storm flooding threats.

Progressive Failure Characterization of Sandstone from Yingjinshan Area in Qinghai-Tibet Plateau - Xinzhong Wang; Heping Xie; Ru Zhang; Guangze Zhang; Zhengxuan Xu; Jianhui Deng; Dong Wang; Cunbao Li; Gan Feng; Zetian Zhang; Li Ren (Rock Mechanics and Rock Engineering, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Neural Stem Cells Therapy for Ischemic Stroke: Progress and Challenges - Tong Zhao; Tongming Zhu; Liqian Xie; Yao Li; Rong Xie; Feng Xu; Hailiang Tang; Jianhong Zhu (Translational Stroke Research, 2022)

Teosinte confers specific alleles and yield potential to maize improvement - Qingjun Wang; Zhengqiao Liao; Chuntao Zhu; Xiangjian Gou; Yaxi Liu; Wubing Xie; Fengkai Wu; Xuanjun Feng; Jie Xu; Jingwei Li; Yanli Lu (Theoretical and Applied Genetics, 2022)

Risk of thyroid cancer and benign nodules associated with exposure to parabens among Chinese adults in Wuhan, China - Nan-Xin Wu; Lang-Jing Deng; Feng Xiong; Jin-Ying Xie; Xiao-Jie Li; Qiang Zeng; Jia-Chen Sun; Da Chen; Pan Yang (Environmental Science and Pollution Research, 2022)

Association between ambient air pollution exposure during pregnancy and gestational diabetes mellitus: a meta-analysis of cohort studies - Xinyu Zhou; Changlian Li; Han Cheng; Junyi Xie; Feng Li; Lishan Wang; Rui Ding (Environmental Science and Pollution Research, 2022)

Identification and analysis of B cell epitopes of hemagglutinin of H1N1 influenza virus - Qing Feng; Xiao-Yan Huang; Yang-Meng Feng; Li-jun Sun; Jing-Ying Sun; Yan Li; Xin Xie; Jun Hu; Chun-Yan Guo (Archives of Microbiology, 2022)

Sugar Product Diversification and Its Opportunities in China - Qi Wang; Cai-Feng Xie; Chang-Rong Shi; Yuan Li; Yu-Hao Shang; Chu-Xuan Hou; Fang-Xue Hang; Jian-Bin Li; Kai Li (Sugar Tech, 2022)

RNA-seq Provides Novel Insights into Response to Acute Salinity Stress in Oriental River Prawn Macrobrachium nipponense - Yaoran Fan; Jianbin Feng; Nan Xie; Feiyue Ling; Zefei Wang; Keyi Ma; Xueming Hua; Jiale Li (Marine Biotechnology, 2022)

Lysobacter chinensis sp. nov., a cellulose-degrading strain isolated from cow dung compost - Yuyue Liu; Liuyan Zhou; Xinping Yang; Pengbin Li; Jinping Dai; Yuqing Xie; Xiaowu Wang; Zhifang Wang; Zhanqiang Su; Lei Feng (Antonie van Leeuwenhoek, 2022)

MdMYB88/124 modulates apple tree microRNA biogenesis through post-transcription processing and/or transcription pathway - Chun-dong Niu; Huan-ran Shi; Zi-tong Zhang; Tian-le Fan; Huan Dang; Peng-xiang Chen; Yin-peng Xie; Cha-na Bao; Feng-wang Ma; Qing-mei Guan; Xue-wei Li (Acta Physiologiae Plantarum, 2022)

Spatial-temporal distribution and tectonic setting of Mesozoic W-mineralized granitoids in the Xing-Meng Orogenic Belt, NE China - Wei Xie; Qing-Dong Zeng; Rui-Liang Wang; Jin-Jian Wu; Zhe-Ming Zhang; Feng-Chun Li; Zhuang Zhang (International Geology Review, 2022)

Prediction of the sea buckthorn AQP gene structure and its spatiotemporal expression pattern under drought stress - Dan Zhang; Nanxiang Yang; Jiawei Dong; Cheng Wang; Qiangfeng Li; Rong Wang; Zhipeng Feng; Dejuan Xie; Guisheng Ye; Yuhua Ma (Journal of Plant Biochemistry and Biotechnology, 2022)

Formation and reactivation mechanisms of large-scale ancient landslides in the Longwu River basin in the northeast Tibetan Plateau, China - Jing-jing Tian; Tian-tao Li; Xiang-jun Pei; Feng Ding; Hao Sun; Xian-gang Xie; Jian Guo (Journal of Mountain Science, 2022)

Two new compounds from a mangrove sediment-derived fungus Penicillium polonicum H175 - Shun-Zhi Liu; Xi-Xiang Tang; Feng-Ming He; Jian-Xin Jia; Hang Hu; Bao-Ying Xie; Ming-Yu Li; Ying-Kun Qiu (Natural Product Research, 2022)

Asymmetric deformation failure mechanism and support technology of roadways under non-uniform pressure from a mining disturbance - Maolin Tian; Lijun Han; Xuxu Yang; Qiang Feng; Qingbin Meng; Yunyue Xie; Wenshuai Li; Chao Ma (Bulletin of Engineering Geology and the Environment, 2022)

Effects of Shear Stress and Salinity Stratification on Floc Size Distribution During the Dry Season in the Modaomen Estuary of the Pearl River - Jie Huang; Simin Wang; Xinran Li; Rongyao Xie; Jianxiong Sun; Benwei Shi; Feng Liu; Huayang Cai; Qingshu Yang; Zhaoyong Zheng (Frontiers in Marine Science, 2022)
The floc size distribution of fine cohesive sediments in estuaries varies spatiotemporally within assorted physical, chemical, and biological factors. However, the distribution of different floc fractions that are affected by shear stress and salinity stratification has not yet been thoroughly investigated. This study intends to clarify the floc size distribution within the influences of turbulent shear rate and salinity stratification, and the implications for the flocculation process during the dry season in the Modaomen Estuary of the Pearl River. The decomposition of multimodal floc size distributions (FSDs) indicates that the floc fractions were composed of macroflocs (Macro), microflocs (Micro), Flocculi, and primary particles (Pp). Macro generally existed among the upper and middle layers, but smaller flocs, i.e., Micro, Flocculi, and Pp, were mostly concentrated in the bottom layer. The results agreed that the flocculation and deflocculation processes were dominant in the upper and bottom layers, respectively. In response to strong turbulent shear rates, FSDs in the bottom layer skewed toward small sizes and had a dual-peak tendency with frequent floc exchanges between Pp and Micro, then being Pp-dominant but converting to Micro when turbulent shear rates decreased. With impeded vertical mixing by salinity stratification, the FSDs in the upper or middle layers skewed toward a larger particle size with single peaks and lack of exchange among different floc fractions, leading to Macro dominance with a larger volume concentration and median size. In addition, turbulence mixing dramatically interfered with the good mixing of floc fractions amidst the vertical water column, with a low-salinity condition greatly affecting the formation of Macro in the bottom layer within proper turbulent shear rates. This study explores the effects of shear stress and salinity stratification on the flocculation process in the Modaomen Estuary, which contributes to a better understanding of sediment movement in a complex estuarine environment.

Identification and Optimization of the Algicidal Activity of a Novel Marine Bacterium Against Akashiwo sanguinea - Shuangfei Li; Shilin Wang; Linshen Xie; Yan Liu; Huirong Chen; Jie Feng; Liao Ouyang (Frontiers in Marine Science, 2022)
Akashiwo sanguinea is a marine algal species associated with harmful algal blooms (HABs). We found that Vibrio brasiliensis H115, isolated from the seawater of Dameisha Bay (Shenzhen), China, can lyse A. sanguinea . At bacteria-to-algae cell ratios of 7,000:1 and 8,000:1, 73.9 ± 1.8 and 81.4 ± 2.8%, respectively, of A. sanguinea were lysed in just 10 min. V. brasiliensis H115 attacks A. sanguinea by secreting extracellular active compounds. Single-factor experiments showed that the optimum growth conditions for strain H115 were medium 2216E with extra sorbitol (1.0%) and peptone (2.0%), pH 7.5, a shaking speed of 200 rpm, and incubated at 40°C for 54 h. Under these optimized conditions, the algicidal efficiency of strain H115 against A. sanguinea improved by 69.4%. Large biomasses were obtained when strain H115 was incubated in 5- and 100-L bioreactors, with algicidal efficiencies against A. sanguinea reaching 94.2 ± 0.5 and 97.1 ± 0.6%, respectively, in 4 h of co-incubation. These results suggest that strain H115 and its active algicidal compounds may be viable for controlling the outbreaks of A. sanguinea .

Pregnancy leads to changes in the brain functional network: a connectome analysis - Tongpeng Chu; Yuna Li; Kaili Che; Fanghui Dong; Heng Ma; Yinghong Shi; Peiyou Gong; Feng Zhao; Xicheng Song; Haizhu Xie; Ning Mao (Brain Imaging and Behavior, 2022)

Target residence of Cas9: challenges and opportunities in genome editing - Yi-Li Feng; Meng Wang; An-Yong Xie (Genome Instability & Disease, 2022)
CRISPR/Cas9 genome editing is a latest success in biotechnology that repurposes a natural biological system for a practical tool in genetic engineering. Site-specific DNA double strand breaks (DSB) induced by the CRISPR nuclease Cas9 allows endogenous cellular repair apparatus to generate desired repair products. Residence of Cas9 on cleaved DNA conceals the DNA ends from recognition by response and repair apparatus, delaying DNA damage response (DDR) and repair. Thus, tight-binding and long residence of Cas9 on DNA target are proposed as a new determinant of DSB repair pathway choice and may collaborate with other endogenous pathway choice regulators to control DSB repair. Accordingly, harnessing the binding and resident behavior of Cas9 not only broadens the application of CRISPR/dCas9 platform, which at least in part depends upon the tight binding and long residence of dCas9, but also minimizes the undesired outcomes of CRISPR/Cas9 genome editing.

Influence of the NAO on Wintertime Surface Air Temperature over East Asia: Multidecadal Variability and Decadal Prediction - Jianping Li; Tiejun Xie; Xinxin Tang; Hao Wang; Cheng Sun; Juan Feng; Fei Zheng; Ruiqiang Ding (Advances in Atmospheric Sciences, 2022)
In this paper, we investigate the influence of the winter NAO on the multidecadal variability of winter East Asian surface air temperature (EASAT) and EASAT decadal prediction. The observational analysis shows that the winter EASAT and East Asian minimum SAT (EAmSAT) display strong in-phase fluctuations and a significant 60–80-year multidecadal variability, apart from a long-term warming trend. The winter EASAT experienced a decreasing trend in the last two decades, which is consistent with the occurrence of extremely cold events in East Asia winters in recent years. The winter NAO leads the detrended winter EASAT by 12–18 years with the greatest significant positive correlation at the lead time of 15 years. Further analysis shows that ENSO may affect winter EASAT interannual variability, but does not affect the robust lead relationship between the winter NAO and EASAT. We present the coupled oceanic-atmospheric bridge (COAB) mechanism of the NAO influences on winter EASAT multidecadal variability through its accumulated delayed effect of ∼15 years on the Atlantic Multidecadal Oscillation (AMO) and Africa–Asia multidecadal teleconnection (AAMT) pattern. An NAO-based linear model for predicting winter decadal EASAT is constructed on the principle of the COAB mechanism, with good hindcast performance. The winter EASAT for 2020–34 is predicted to keep on fluctuating downward until ∼2025, implying a high probability of occurrence of extremely cold events in coming winters in East Asia, followed by a sudden turn towards sharp warming. The predicted 2020/21 winter EASAT is almost the same as the 2019/20 winter.

Preparation and In Vitro and In Vivo Evaluation of a Testosterone Film Forming Gel for the Treatment of Hypoactive Sexual Desire Disorder in Women - Jia Zeng; Tan-Fang Xie; Ting Huang; Fang Li; Zhi-Ping Wang; Ling-Lin Feng (AAPS PharmSciTech, 2022)

Risk and protection strategies of Amolops wuyiensis intestine against gastrointestinal nematode ( Cosmocercoides wuyiensis n. sp.) infection - Yilin Shu; Yunyun Xie; Shikun Li; Liming Cai; Ying Liu; Yalin Feng; Jun He; Huijuan Zhang; Menglong Ran; Qina Jia; Hailong Wu; Linming Lu (Environmental Microbiology, 2022)
Summary Anuran amphibians are susceptible to infection by intestinal nematodes, but the damage and response mechanisms that occur in their intestines after infection are only partially understood. In this study, the intestinal disruption and response mechanisms in Amolops wuyiensis frogs infected with Cosmocercoides wuyiensis n. sp. were revealed through analysis of the intestinal histopathology, digestive enzyme activity, transcriptome and intestinal microbiota. Tissue section analysis showed histological damage and inflammation in the infected intestine, and the digestive enzyme activity indicated a decrease in digestion and absorption of some nutrients. We found that infection led to differences in the intestinal microbiota composition, including lower diversity and symbiotic relationships. The greater relative abundance of the genera Burkholderia and Rhodococcus may enhance intestinal immunity to resist pathogenic infections. A comparison of the transcriptomes of infected and uninfected intestines revealed 1055 differentially expressed genes. GO enrichment and KEGG pathways analyses suggested that the guts of infected C . wuyiensis n. sp. show enhanced complement activation, cell adhesion molecule function, NOD‐like receptor signalling pathway activity and other innate immunity responses. Among the adaptive immune responses, the intestinal immune network for IgA production was significantly enriched, and the expression of IL‐17D and transforming growth factor beta‐1 genes were upregulated in the infected intestine. These results imply that C . wuyiens is n. sp. infection of A . wuyiensis intestine may trigger innate and adaptive immune responses, which reduce the post‐infection burden. Furthermore, the intestine of A . wuyiensis may also respond to C . wuyiensis n. sp. infection by increasing metallocarboxypeptidase activity and accelerating smooth muscle contraction.

Superiority of Adipose-derived CD34 + Cells over Adipose-derived Stem Cells in Promoting Ischemic Tissue Survival - Yan-Jun Liu; Tian-Yu Zhang; Poh-Ching Tan; Pei-Qi Zhang; Yun Xie; Qing-Feng Li; Shuang-Bai Zhou (Stem Cell Reviews and Reports, 2022)

Probiotic Therapy (BIO-THREE) Mitigates Intestinal Microbial Imbalance and Intestinal Damage Caused by Oxaliplatin - Wenzhen Yuan; Xingpeng Xiao; Xuan Yu; Fuquan Xie; Pengya Feng; Kamran Malik; Jingyuan Wu; Ze Ye; Peng Zhang; Xiangkai Li (Probiotics and Antimicrobial Proteins, 2022)

Inter-annual and intra-annual variations in water quality and its response to water-level fluctuations in a river-connected lake, Dongting Lake, China - Mingming Geng; Yandong Niu; Xiaohong Liao; Kelin Wang; Nan Yang; Zhan Qian; Feng Li; Yeai Zou; Xinsheng Chen; Zhengmiao Deng; Yonghong Xie (Environmental Science and Pollution Research, 2022)

Long-term observations of the chemical composition, fluxes and sources of atmospheric wet deposition at an urban site in Xi’an, Northwest China - Rui-feng Li; Xi-ying Dong; Cong Xie; Liang-ju Zhao (Environmental Monitoring and Assessment, 2022)

A Possible Dynamic Mechanism for Rapid Production of the Extreme Hourly Rainfall in Zhengzhou City on 20 July 2021 - Jinfang Yin; Haodong Gu; Xudong Liang; Miao Yu; Jisong Sun; Yanxin Xie; Feng Li; Chong Wu (Journal of Meteorological Research, 2022)

Comparative Study of Flood Coincidence Risk Estimation Methods in the Mainstream and its Tributaries - Na Li; Shenglian Guo; Feng Xiong; Jun Wang; Yuzuo Xie (Water Resources Management, 2022)

LncRNA NRON negatively regulates cisplatin-induced cell apoptosis via downregulating miR-31 in esophageal squamous cell carcinomas - Bo Liu; Xu Li; Jinbao Xie; Zhi Feng; Nanlong Lin; Minjie Yu (In Vitro Cellular & Developmental Biology - Animal, 2022)

Experimental mechanical strength and deformation characteristics of deep damaged–fractured rock - Qing-Bin Meng; Jiang-Feng Liu; Li-Xiang Xie; Hai Pu; Yu-Gui Yang; Bing-Xiang Huang; Wei Qian (Bulletin of Engineering Geology and the Environment, 2022)

Bioactive compounds derived from the marine-derived fungus MCCC3A00951 and their influenza neuraminidase inhibition activity in vitro and in silico - Shun-Zhi Liu; Feng-Ming He; Yan-lin Bin; Chu-Fang Li; Bao-Ying Xie; Xi-Xiang Tang; Ying-Kun Qiu (Natural Product Research, 2021)

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

MALDI–TOF-MS and XAS analysis of complexes formed by metallothionein with mercury and/or selenium - Lina He; Hongxin Xie; Xu Bai; Jiating Zhao; Liwei Cui; Junfang Zhang; Bai Li; Yu-Feng Li (BioMetals, 2021)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Geochemistry of the Lower Cretaceous limestones in the Eastern Tethys Gyabula Formation (Himalaya, southern Tibet): implications for the depositional environment and tectonic setting - Qing Li; Feng Ding; Micha Ruhl; Yongdong Wang; Ying Li; Lei Yang; Kunzhi Xu; Xiangang Xie (Arabian Journal of Geosciences, 2021)

A signal quality assessment–based ECG waveform delineation method used for wearable monitoring systems - Jialing Xie; Li Peng; Liang Wei; Yushun Gong; Feng Zuo; Juan Wang; Changlin Yin; Yongqin Li (Medical & Biological Engineering & Computing, 2021)

Research on a new cationic polyacrylamide (CPAM) with a cationic microblock structure and its enhanced effect on sludge condition and dewatering - Yuning Chen; Xuhao Li; Wang Zizeng; Li Feng; Jiehong Xie; Zeluan Lin; Zhihong Xu; Bingzhi Liu; Xiang Li; Huaili Zheng (Environmental Science and Pollution Research, 2021)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

A fungal sirtuin modulates development and virulence in the insect pathogen, Beauveria bassiana - Qing Cai; Li Tian; Jia‐Tao Xie; Qiu‐Ying Huang; Ming‐Guang Feng; Nemat O. Keyhani (Environmental Microbiology, 2021)
Summary Chromatin transitions are mediated in part by acetylation/deacetylation post‐translational modifications of histones. Histone deacetylases, e.g. sirtuins (Sir‐proteins), repress transcription via promotion of heterochromatin formation. Here, we characterize the Sir2 class III histone deacetylase ( BbSir2 ) in the environmentally and economically important fungal insect pathogen, Beauveria bassiana . BbSir2 is shown to contribute to the deacetylation of lysine residues on H3 and H4 histones. Targeted gene knockout of BbSir2 resulted in impaired asexual development, reduced abilities to utilize various carbon/nitrogen sources, reduced tolerance to oxidative, heat, and UV stress, and attenuated virulence. ΔBbSir2 cells showed disrupted cell cycle development and abnormal hyphal septation patterns. Proteomic protein acetylation analyses of wild type and ΔBbSir2 cells revealed the differential abundance of 462 proteins and altered (hyper‐ or hypo‐) acetylation of 436 lysine residues on 350 proteins. Bioinformatic analyses revealed enrichment in pathways involved in carbon/nitrogen metabolism, cell cycle control and cell rescue, defence and mitochondrial functioning. Critical targets involved in virulence included LysM effector proteins and a benzoquinone oxidoreductase implicated in detoxification of cuticular compounds. These data indicate broad effects of BbSir2 on fungal development and stress response, with identification of discrete targets that can account for the observed (decreased) virulence phenotype.

Fine mapping of a powdery mildew resistance gene MlIW39 derived from wild emmer wheat (Triticum turgidum ssp. dicoccoides) - Lina Qiu; Nannan Liu; Huifang Wang; Xiaohan Shi; Feng Li; Qiang Zhang; Weidong Wang; Weilong Guo; Zhaorong Hu; Hongjie Li; Jun Ma; Qixin Sun; et al. (Theoretical and Applied Genetics, 2021)

Evaluation of the CARDS toxin and its fragment for the serodiagnosis of Mycoplasma pneumoniae infections - Guanhua Xue; Hanqing Zhao; Chao Yan; Shaoli Li; Jinghua Cui; Yanling Feng; Xianghui Xie; Jing Yuan (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Periodontal health related–inflammatory and metabolic profiles of patients with end-stage renal disease: potential strategy for predictive, preventive, and personalized medicine - Xiaoxin Ma; Yongli Wang; Hongyu Wu; Fei Li; Xiping Feng; Yingxin Xie; Danshu Xie; Wenji Wang; Edward Chin Man Lo; Haixia Lu (EPMA Journal, 2021)
Objectives To compare the periodontal health related–inflammatory and metabolic differences between patients with end-stage renal disease (ESRD) and healthy controls (HC), and to identify potential biomarkers in gingival crevicular fluid (GCF) and serum of ESRD patients for predictive, preventive, and personalized medicine (PPPM). Methods Patients with ESRD (ESRD group; n = 52) and healthy controls (HC group; n = 44) were recruited. Clinical periodontal parameters were recorded. The differential metabolites in the GCF and serum were identified by liquid chromatography/mass spectrometry (LC/MS). Inflammatory markers including interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), and C-reactive protein (CRP) were also assessed. Results In the ESRD group, IL-8 and CRP were significantly higher in GCF, whereas IL-6 and CRP were significantly higher in serum, compared with HC group (all P < 0.05). In the case of GCF, taurine levels were positively correlated with IL-8 levels in both groups (all P < 0.05). In the case of serum, l -phenylalanine and p -hydroxyphenylacetic acid levels were positively correlated with CRP levels in both groups (all P < 0.05). Significant positive correlations were observed between metabolites (including pseudouridine, l -phenylalanine, and p -hydroxyphenylacetic acid) and IL-6 levels only in ESRD group. Conclusions IL-8 and CRP are potential inflammatory makers that reflect the periodontal health of ESRD individual, which may be considered the valuable predictive diagnostics in the agreement with PPPM philosophy. Besides, metabolites of taurine in GCF as well as l -phenylalanine and p -hydroxyphenylacetic acid in serum are possible biomarkers correlated with inflammatory markers. All these biomarkers may also be highly recommended as a novel predictive/diagnostic tool for the assessment of inflammatory status from the perspectives of PPPM in view of susceptible population and individual screening.

Establishment and characterization of 38 novel patient-derived primary cancer cell lines using multi-region sampling revealing intra-tumor heterogeneity of gallbladder carcinoma - Feiling Feng; Qingbao Cheng; Bin Li; Chen Liu; Huizhen Wang; Bin Li; Xiaoya Xu; Yong Yu; Zishuo Chen; Xiaobing Wu; Hua Dong; Kaijian Chu; et al. (Human Cell, 2021)
Gallbladder carcinoma (GBC) is a lethal biliary tract malignant neoplasm. Patient-derived primary cancer cell lines (PDPCs) are appropriate models to explore biological characteristics and potential therapeutics; however, there is a lack of PDPCs in GBC. In this study, we aimed to establish and characterize the GBC PDPCs, and further investigated the intra-tumor heterogeneity (ITH). Multi-region sampling (3–9 regions) of the operable tumor tissue samples was used to establish PDPCs. Short tandem repeat genotyping for cell authentication and karyotyping was performed, followed by whole-exome sequencing and RNA sequencing to assess the ITH at the genetic and transcriptional levels, respectively. Thirty-eight PDPCs were successfully established from seven GBC patients and characterized. ITH was observed with a median of 38.3% mutations being heterogeneous (range, 26.6–59.4%) across all patients. Similar with other tumor types, TP53 mutations were always truncal. In addition, there were three genes, KMT2C , CDKN2A , and ARID1A , with truncal mutations in at least two patients. A median of 370 differentially expressed genes (DEGs) was identified per patient. Distinct expression patterns were observed between major histocompatibility complex (MHC) class I and II genes. We found the expression of MHC class II genes in the PDPC samples was closely regulated by CIITA , while that of MHC class I genes were not correlated with CIITA expression. The PDPCs established from GBC patients can serve as novel in vitro models to identify the ITH, which may pave a crucial molecular foundation for enhanced understanding of tumorigenesis and progression.

Characteristics and Causes of Extreme Rainfall Induced by Binary Tropical Cyclones over China - Mingyang Wang; Fumin Ren; Yanjun Xie; Guoping Li; Ming-Jen Yang; Tian Feng (Asia-Pacific Journal of Atmospheric Sciences, 2021)
Binary tropical cyclones (BTC) often bring disastrous rainfall to China. From the viewpoint of the extreme of the BTC maximum daily rainfall, the characteristics of BTC extreme rainfall (BTCER) during 1960–2018 are analyzed, using daily rainfall data; and some representative large-scale mean flows, in which the associated BTCs are embedded, are analyzed. Results show that the frequency of BTCER shows a decreasing trend [−0.49 (10 yr) −1 ] and is mainly distributed within the BTC heavy rainstorm interval (100 mm ≤ BTCER

Appropriate Ammonium/Nitrate Mitigates Low Light Stress in Brassica pekinensis by Regulating the Nitrogen Metabolism and Expression Levels of Key Proteins - Linli Hu; Yue Wu; Mohammed Mujitaba Dawuda; Weibiao Liao; Jian Lv; Yutong Li; Jihua Yu; Jianming Xie; Zhi Feng; Guobin Zhang; Alejandro Calderón-Urrea (Journal of Plant Growth Regulation, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Simulation of the fragmentation and propagation of jointed rock masses in rockslides: DEM modeling and physical experimental verification - Qi-wen Lin; Qian-Gong Cheng; Yu Xie; Feng-shou Zhang; Kun Li; Yu-feng Wang; Yuan-yuan Zhou (Landslides, 2021)

MutagenPred-GCNNs: A Graph Convolutional Neural Network-Based Classification Model for Mutagenicity Prediction with Data-Driven Molecular Fingerprints - Shimeng Li; Li Zhang; Huawei Feng; Jinhui Meng; Di Xie; Liwei Yi; Isaiah T. Arkin; Hongsheng Liu (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Enhanced nitrous oxide emissions caused by atmospheric nitrogen deposition in agroecosystems over China - Yuyu Yang; Lei Liu; Feng Zhang; Xiuying Zhang; Wen Xu; Xuejun Liu; Yi Li; Zhen Wang; Yaowen Xie (Environmental Science and Pollution Research, 2021)

Fluoride Exposure and Blood Pressure: a Systematic Review and Meta-Analysis - Meng Li; Yannan Zhao; Xiaolin Tian; Penghui Liu; Jiaxin Xie; Nisha Dong; Jing Feng; Yi Gao; Ye Fan; Yulan Qiu; Fengjie Tian; Xiaoyan Yan (Biological Trace Element Research, 2021)

A single nucleotide polymorphism variant located in the cis ‐regulatory region of the ABCG2 gene is associated with mallard egg colour - Hehe Liu; Jian Hu; Zhanbao Guo; Wenlei Fan; Yaxi Xu; Suyun Liang; Dapeng Liu; Yunsheng Zhang; Ming Xie; Jing Tang; Wei Huang; Qi Zhang; et al. (Molecular Ecology, 2021)
Avian egg coloration is shaped by natural selection, but its genetic basis remains unclear. Here, we used genome‐wide association analysis and identity by descent to finely map green egg colour to a 179‐kb region of Chr4 based on the resequencing of 352 ducks ( Anas platyrhynchos ) from a segregating population resulting from the mating of Pekin ducks (white‐shelled eggs) and mallards (green‐shelled eggs). We further narrowed the candidate region to a 30‐kb interval by comparing genome divergence in seven indigenous duck populations. Among the genes located in the finely mapped region, only one transcript of the ABCG2 gene (XM_013093252.2) exhibited higher uterine expression in green‐shelled individuals than in white‐shelled individuals, as supported by transcriptome data from four populations. ABCG2 has been reported to encode a protein that functions as a membrane transporter for biliverdin. Sanger sequencing of the whole 30‐kb candidate region (Chr4: 47.41–47.44 Mb) and a plasmid reporter assay helped to identify a single nucleotide polymorphism (Chr4: 47,418,074 G>A) located in a conserved predicted promoter region whose variation may alter ABCG2 transcription activity. We provide a useful molecular marker for duck breeding and contribute data to the research on ecological evolution based on egg colour patterns among birds.

Correction to: Suppression of TLR4/NF-κB Signaling Pathway Improves Cerebral Ischemia–Reperfusion Injury in Rats - Hang Zhao; Zhuo Chen; Li-Juan Xie; Gui-Feng Liu (Molecular Neurobiology, 2021)

Field tests of micro screw anchor piles under different loading conditions at three soil sites - Shi-Jin Feng; Wen-Ding Fu; Hong-Xin Chen; Hong-Xing Li; Yan-Li Xie; Shao-Feng Lv; Jin Li (Bulletin of Engineering Geology and the Environment, 2021)

Effects of Clipping on Bud Bank and Population Regeneration of Triarrhena lutarioriparia in Dongting Lake Wetland, China - Xiaorong Chen; Lianlian Zhu; Zhengmiao Deng; Yonghong Xie; Xinsheng Chen; Feng Li; Ye-ai Zou (Wetlands, 2020)

Unveiling of active diazotrophs in a flooded rice soil by combination of NanoSIMS and 15N2-DNA-stable isotope probing - Xiaojie Wang; Qicheng Bei; Wei Yang; Heng Zhang; Jialong Hao; Li Qian; Yucheng Feng; Zubin Xie (Biology and Fertility of Soils, 2020)

Enhanced Stability of the Pharmacologically Active Lactone Form of 10-Hydroxycamptothecin by Self-Microemulsifying Drug Delivery Systems - Ruiming Li; Yong Wang; Qiang Yang; Baolong Lai; Xie Zhou; Min Feng (AAPS PharmSciTech, 2020)

Effects of Drying-Rewetting Frequency on Vertical and Lateral Loss of Soil Organic Carbon in a Tidal Salt Marsh - Juanyong Li; Wendi Qu; Guangxuan Han; Feng Lu; Yingfeng Zhou; Weimin Song; Baohua Xie; Franziska Eller (Wetlands, 2020)

Comparative analysis of the transcriptome, methylome, and metabolome during pollen abortion of a seedless citrus mutant - Li-Xia Ye; Zhi-Meng Gan; Wen-Feng Wang; Xiao-Yan Ai; Zong-Zhou Xie; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology, 2020)

Co-exposure to Arsenic-Fluoride Results in Endoplasmic Reticulum Stress-Induced Apoptosis Through the PERK Signaling Pathway in the Liver of Offspring Rats - Nisha Dong; Jing Feng; Jiaxin Xie; Xiaolin Tian; Meng Li; Penghui Liu; Yannan Zhao; Cailing Wei; Yi Gao; Ben Li; Yulan Qiu; Xiaoyan Yan (Biological Trace Element Research, 2020)

Examining environmental regulation efficiency of haze control and driving mechanism: evidence from China - Feng Dong; Shengnan Zhang; Yangfan Li; Jingyun Li; Shouxiang Xie; Jixiong Zhang (Environmental Science and Pollution Research, 2020)

Spatio-temporal variation and risk assessment of hydrochemical indices in a large diversion project of the Yellow River, northern China, from 2008 to 2017 - Yuan Li; Fei Wang; Jia Feng; Junping Lv; Qi Liu; Fangru Nan; Xudong Liu; Lan Xu; Shulian Xie (Environmental Science and Pollution Research, 2020)

Cytochrome P450 1A mRNA in the Gambusia affinis and Response to Several PAHs - Shaolin Xie; Aiguo Zhou; Yongyong Feng; Yue Zhang; Junyi Li; Zhuolin Sun; Lanfen Fan; Jixing Zou (Biochemical Genetics, 2020)

Microbial and metabolomic analysis of gingival crevicular fluid in general chronic periodontitis patients: lessons for a predictive, preventive, and personalized medical approach - Jun Pei; Fei Li; Youhua Xie; Jing Liu; Tian Yu; Xiping Feng (EPMA Journal, 2020)
Objectives General chronic periodontitis (GCP) is a bacterial inflammatory disease with complex pathology. Despite extensive studies published on the variation in the oral microbiota and metabolic profiles of GCP patients, information is lacking regarding the correlation between host-bacterial interactions and biochemical metabolism. This study aimed to analyze the oral microbiome, the oral metabolome, and the link between them and to identify potential molecules as useful biomarkers for predictive, preventive, and personalized medicine (PPPM) in GCP. Methods In this study, gingival crevicular fluid (GCF) samples were collected from patients with GCP ( n = 30) and healthy controls ( n = 28). The abundance of oral microbiota constituents was obtained by Illumina sequencing, and the relative level of metabolites was measured by gas chromatography-mass spectrometry. Full-mouth probing depth, clinical attachment loss, and bleeding on probing were recorded as indices of periodontal disease. Results The relative abundances of 7 phyla and 82 genera differed significantly between the GCP and healthy groups. Seventeen differential metabolites involved in different metabolism pathways were selected based on variable influence on projection values (VIP > 1) and P values ( P < 0.05). Through Spearman’s correlation analysis, microorganisms, metabolites in GCF, and clinical data together showed a clear trend, and clinical data regarding periodontitis can be reflected in the shift of the oral microbial community and the change in metabolites in GCF. A combination of citramalic acid and N-carbamylglutamate yielded satisfactory accuracy (AUC = 0.876) for the predictive diagnosis of GCP. Conclusions Dysbiosis in the polymicrobial community structure and changes in metabolism could be mechanisms underlying periodontitis. The differential microorganisms and metabolites in GCF between periodontitis patients and healthy individuals are possibly biomarkers, pointing to a potential strategy for the prediction, diagnosis, prognosis, and management of personalized periodontal therapy.

Chemical constituents from the deep sea-derived Streptomyces xiamenensis MCCC 1A01570 and their effects on RXRα transcriptional regulation - Wei-Xiang Lin; Chun-Lan Xie; Mi Zhou; Man-Li Xia; Ting-Ting Zhou; Hai-Feng Chen; Xian-Wen Yang; Quan Yang (Natural Product Research, 2020)

Chloroplast genomic comparison of two sister species Allium macranthum and A. fasciculatum provides valuable insights into adaptive evolution - Hao Li; Deng-Feng Xie; Jun-Pei Chen; Song-Dong Zhou; Xing-Jin He (Genes & Genomics, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

The phase and code biases of Galileo and BDS-3 BOC signals: effect on ambiguity resolution and precise positioning - Xingxing Li; Xin Li; Gege Liu; Weiliang Xie; Fei Guo; Yongqiang Yuan; Keke Zhang; Guolong Feng (Journal of Geodesy, 2020)

GNAS-AS1/miR-4319/NECAB3 axis promotes migration and invasion of non-small cell lung cancer cells by altering macrophage polarization - Zhixin Li; Changjiang Feng; Junhong Guo; Xuefei Hu; Dong Xie (Functional & Integrative Genomics, 2020)

An inter-basin teleconnection from the North Atlantic to the subarctic North Pacific at multidecadal time scales - Zhanqiu Gong; Cheng Sun; Jianping Li; Juan Feng; Fei Xie; Ruiqiang Ding; Yun Yang; Jiaqing Xue (Climate Dynamics, 2020)

Geochemical characteristics and geological significance of basalts in the Sangxiu formation, Rongbu area, southern Tibet - Ying Li; Feng Ding; Lei Yang; Xiangang Xie; Kunzhi Xu; Qing Li; Wenlong Yu; Yao Sun (Arabian Journal of Geosciences, 2019)

Proteomics combined with BSMV-VIGS methods identified some N deficiency-responsive protein species and ABA role in wheat seedling - Guozhang Kang; Yufang Wu; Gezi Li; Pengfei Wang; Qiaoxia Han; Yonghua Wang; Yingxin Xie; Wei Feng; Dongyun Ma; Chenyang Wang; Tiancai Guo (Plant and Soil, 2019)

Petrology and geochemistry of Upper Jurassic Weimei Formation sandstones in southern Tibet: implications for provenance and tectonic setting - Kunzhi Xu; Feng Ding; Qing Li; Xiangang Xie; Lei Yang; Ying Li; Binbin Dong (Geosciences Journal, 2019)

Genome-wide association analysis of salt tolerance QTLs with SNP markers in maize (Zea mays L.) - Yonghong Xie; Yan Feng; Qi Chen; Feike Zhao; Shuijuan Zhou; Ying Ding; Xianliang Song; Ping Li; Baohua Wang (Genes & Genomics, 2019)

The prevalence and genetic diversity of porcine circovirus types 2 and 3 in Northeast China from 2015 to 2018 - Deli Xia; Liping Huang; Yongxing Xie; Xiaoqian Zhang; Yanwu Wei; Dan Liu; Hongzhen Zhu; Haiqiao Bian; Li Feng; Changming Liu (Archives of Virology, 2019)

Exploring the Potential of Mesoporous Silica as a Carrier for Puerarin: Characterization, Physical Stability, and In Vivo Pharmacokinetics - Zhi Wang; Bei-Ni Ye; Yong-Tai Zhang; Jian-Xu Xie; Wan-Si Li; Hong-Tao Zhang; Ying Liu; Nian-Ping Feng (AAPS PharmSciTech, 2019)

Synergistic deletion of RGS1 and COS1 may reduce the pathogenicity of Magnaporthe oryzae - He Na; An Bang; Xie Qing-biao; Yan Xia; Feng Hui-min; Luo Hong-li; He Chao-zu (Archives of Microbiology, 2019)

Rheological characteristics and one-dimensional isotache modelling of marine soft clays - Sheng-Feng Zou; Xin-Yu Xie; Jin-Zhu Li; Zhong-Jin Wang; Heng-Yu Wang (Marine Georesources & Geotechnology, 2019)

NAO implicated as a predictor of the surface air temperature multidecadal variability over East Asia - Tiejun Xie; Jianping Li; Cheng Sun; Ruiqiang Ding; Kaicun Wang; Chuanfeng Zhao; Juan Feng (Climate Dynamics, 2019)

Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2019)

The dominant role of the atmospheric component of coupled models in ENSO amplitude simulations - Yanli Tang; Lijuan Li; Bin Wang; Pengfei Lin; Lin Chen; Feng Xie; Wenjie Dong; Kun Xia (Climate Dynamics, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Genetic polymorphism analysis of mitochondrial DNA from Chinese Xinjiang Kazak ethnic group by a novel mitochondrial DNA genotyping panel - Tong Xie; Li Hu; Yu-Xin Guo; Yu-Chun Li; Feng Chen; Bo-Feng Zhu (Molecular Biology Reports, 2019)

Does dual reduction in chemical fertilizer and pesticides improve nutrient loss and tea yield and quality? A pilot study in a green tea garden in Shaoxing, Zhejiang Province, China - Shaowen Xie; Hanxiao Feng; Fen Yang; Zhide Zhao; Xuedi Hu; Chaoyang Wei; Tao Liang; Haitao Li; Yuanbo Geng (Environmental Science and Pollution Research, 2019)

MiR-92a inhibits fibroblast-like synoviocyte proliferation and migration in rheumatoid arthritis by targeting AKT2 - Fang-Yuan Yu; Cong-Qin Xie; Chang-liang Jiang; Ji-Tong Sun; Hui-Cheng Feng; Chao Li; Xun-Wu Huang (Journal of Biosciences, 2018)

An advanced impact of Arctic stratospheric ozone changes on spring precipitation in China - Fei Xie; Xuan Ma; Jianping Li; Jinlong Huang; Wenshou Tian; Jiankai Zhang; Yongyun Hu; Cheng Sun; Xin Zhou; Juan Feng; Yun Yang (Climate Dynamics, 2018)

Effects of cadmium stress on the antioxidant system and chlorophyll fluorescence characteristics of two Taxodium clones - Ying-Li Ma; Hui-Fang Wang; Ping Wang; Chao-Guang Yu; Si-Qian Luo; Yu-Feng Zhang; Yin-Feng Xie (Plant Cell Reports, 2018)

Analysis of Sedimentary Components in Post-haze Concentrated Sugarcane Juice - Rui-Jing Qu; Kai Li; Fang-Xue Hang; Wen Li; Cai-Feng Xie (Sugar Tech, 2018)

Paenibacillus maysiensis sp. nov., a Nitrogen-Fixing Species Isolated from the Rhizosphere Soil of Maize - Tian-shu Wang; Jiu-yan Xie; Li-ying Wang; San-feng Chen (Current Microbiology, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Deriving Optimal Operating Rules of a Multi-Reservoir System Considering Incremental Multi-Agent Benefit Allocation - Zhuowei Shen; Pan Liu; Bo Ming; Maoyuan Feng; Xiaoqi Zhang; He Li; Aili Xie (Water Resources Management, 2018)

The complete chloroplast genome sequence of an endangered Orchidaceae species Dendrobium monilforme and its phylogenetic implications - Yan-xia Gao; Yu-yan Zhou; Ying Xie; Li Feng; Shi-gang Shen (Conservation Genetics Resources, 2018)

Assessing the efficacy of a live vaccine against avian encephalomyelitis virus - Wencheng Lin; Piaopiao Lu; Aijun Li; Yu Wu; Hongxin Li; Feng Chen; Jingyun Ma; Qingmei Xie (Archives of Virology, 2018)

Finger or Light: Stimulation Sensitivity of Visual Startle in the Coma Recovery Scale-Revised for Disorders of Consciousness - Feng Zhou; Hui Li; Kai Wang; Yanbin He; Yan Chen; Xiaoxiao Ni; Yechun Guo; Wei Lv; Jiechun Zhang; Qiuyou Xie; Ronghao Yu (Neuroscience Bulletin, 2018)

Application of Phragmites australis to remove phenol from aqueous solutions by chemical activation in batch and fixed-bed columns - Sheng-Li Shi; Jun-Ping Lv; Qi Liu; Fang-Ru Nan; Xiao-Yan Jiao; Jia Feng; Shu-Lian Xie (Environmental Science and Pollution Research, 2018)

An improved Mahalanobis distance-based colour segmentation method for rural building recognition - Jia-li Xie; Yong-shu Li; Guo-lin Cai; Feng Wang; He-chao Li (Journal of Mountain Science, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Expression plasticity and evolutionary changes extensively shape the sugar‐mimic alkaloid adaptation of nondigestive glucosidase in lepidopteran mulberry‐specialist insects - Xiaotong Li; Liangen Shi; Xiangping Dai; Yajie Chen; Hongqing Xie; Min Feng; Yuyin Chen; Huabing Wang (Molecular Ecology, 2018)
During the co‐evolutionary arms race between plants and herbivores, insects evolved systematic adaptive plasticity to minimize the chemical defence effects of their host plants. Previous studies mainly focused on the expressional plasticity of enzymes in detoxification and digestion. However, the expressional response and adaptive evolution of other fundamental regulators against host phytochemicals are largely unknown. Glucosidase II ( GII ), which is composed of a catalytic GII α subunit and a regulatory GII β subunit, is an evolutionarily conserved enzyme that regulates glycoprotein folding. In this study, we found that GII α expression of the mulberry‐specialist insect was significantly induced by mulberry leaf extract, 1‐deoxynojirimycin (1‐ DNJ ), whereas GII β transcripts were not significantly changed. Moreover, positive selection was detected in GII α when the mulberry‐specialist insects diverged from the lepidopteran order, whereas GII β was mainly subjected to purifying selection, thus indicating an asymmetrically selective pressure of GII subunits. In addition, positively selected sites were enriched in the GII α of mulberry‐specialist insects and located around the 1‐ DNJ ‐binding sites and in the C‐terminal region, which could result in conformational changes that affect catalytic activity and substrate‐binding efficiency. These results show that expression plasticity and evolutionary changes extensively shape sugar‐mimic alkaloids adaptation of nondigestive glucosidase in lepidopteran mulberry‐specialist insects. Our study provides novel insights into a deep understanding of the sequestration and adaptation of phytophagous specialists to host defensive compounds.

Chloroplast genome sequence of the endangered Orchidaceae species Dendrobium hancockii - Yan-xia Gao; Yu-yan Zhou; Ying Xie; Li Feng; Shi-gang Shen (Conservation Genetics Resources, 2018)

Suppression of TLR4/NF-κB Signaling Pathway Improves Cerebral Ischemia–Reperfusion Injury in Rats - Hang Zhao; Zhuo Chen; Li-Juan Xie; Gui-Feng Liu (Molecular Neurobiology, 2018)

Enhancement of nitrogen and phosphorus removal in landscape water using polymeric ferric sulfate as well as the synergistic effect of four kinds of natural rocks as promoter - Xuejiao Huang; Mi Feng; Chengsheng Ni; Deti Xie; Zhenlun Li (Environmental Science and Pollution Research, 2018)

Expression of three reporter genes in four cell lines developed from Papilio demoleus Linnaeus (Lepidoptera: Papilionidae) - Wei-Feng Ding; Xin Zhang; Xian Li; Zhi-Gang Liu; Shi-Cong Xie; Ying Feng (In Vitro Cellular & Developmental Biology - Animal, 2018)

Safety, pharmacokinetics, and pharmacodynamics of S-(−)-pantoprazole sodium injections after single and multiple intravenous doses in healthy Chinese subjects - Hui-Wen Jiao; Lu-Ning Sun; Yue-Qi Li; Lei Yu; Hong-Wen Zhang; Mei-Feng Wang; Li-Yuan Yu; Zi-Qing-Yun Yuan; Li-Jun Xie; Juan Chen; Ling Meng; Xue-Hui Zhang; et al. (European Journal of Clinical Pharmacology, 2018)

Alternative oxidase functions in the excess excitation energy-induced resistance to pathogen infection - Qin-zheng Hou; Kun Sun; Ling-yun Jia; Jun-yu Liang; Jia-jia Xie; Li-na Lu; Han-qing Feng; Jing Wen (Biologia, 2018)

Establishment of an embryonic cell line from the American cockroach Periplaneta americana (Blattaria: Blattidae) and a preliminary study of telomerase activity changes during the culturing process - Xin Zhang; Ying Feng; Wei-Feng Ding; Xian Li; Si-Cong Xie (In Vitro Cellular & Developmental Biology - Animal, 2018)

Temporal patterns and processes of genetic differentiation of the Brachionus calyciflorus (Rotifera) complex in a subtropical shallow lake - Ye Zhang; Ao Zhou; Yi-Long Xi; Qiang Sun; Le-Feng Ning; Ping Xie; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2018)

Metaproteomics reveals major microbial players and their metabolic activities during the blooming period of a marine dinoflagellate Prorocentrum donghaiense - Dong‐Xu Li; Hao Zhang; Xiao‐Huang Chen; Zhang‐Xian Xie; Yong Zhang; Shu‐Feng Zhang; Lin Lin; Feng Chen; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Interactions between bacteria and phytoplankton during bloom events are essential for both partners, which impacts their physiology, alters ambient chemistry and shapes ecosystem diversity. Here, we investigated the community structure and metabolic activities of free‐living bacterioplankton in different blooming phases of a dinoflagellate Prorocentrum donghaiense using a metaproteomic approach. The Fibrobacteres ‐ Chlorobi ‐ Bacteroidetes group, Rhodobacteraceae , SAR11 and SAR86 clades contributed largely to the bacterial community in the middle‐blooming phase while the Pseudoalteromonadaceae exclusively dominated in the late‐blooming phase. Transporters and membrane proteins, especially TonB‐dependent receptors were highly abundant in both blooming phases. Proteins involved in carbon metabolism, energy metabolism and stress response were frequently detected in the middle‐blooming phase while proteins participating in proteolysis and central carbon metabolism were abundant in the late‐blooming phase. Beta‐glucosidase with putative algicidal capability was identified from the Pseudoalteromonadaceae only in the late‐blooming phase, suggesting an active role of this group in lysing P . donghaiense cells. Our results indicated that diverse substrate utilization strategies and different capabilities for environmental adaptation among bacteria shaped their distinct niches in different bloom phases, and certain bacterial species from the Pseudoalteromonadaceae might be crucial for the termination of a dinoflagellate bloom.

Controls on Litter Decomposition of Emergent Macrophyte in Dongting Lake Wetlands - Yajun Xie; Yonghong Xie; Huayun Xiao; Xinsheng Chen; Feng Li (Ecosystems, 2017)

Decadal Indian Ocean dipolar variability and its relationship with the tropical Pacific - Yun Yang; Jianping Li; Lixin Wu; Yu Kosaka; Yan Du; Cheng Sun; Fei Xie; Juan Feng (Advances in Atmospheric Sciences, 2017)

RETRACTED ARTICLE: Structure revision of aspergicin by the crystal structure of aspergicine, a co-occurring isomer produced by co-culture of two mangrove epiphytic fungi - Feng Zhu; Jie-sen Li; Wu-cheng Xie; Jun-jun Shi; Feng Xu; Zhao-feng Song; Yi-lu Liu (Natural Product Research, 2017)

Hsa_circ_0045714 regulates chondrocyte proliferation, apoptosis and extracellular matrix synthesis by promoting the expression of miR-193b target gene IGF1R - Bao-feng Li; Ying Zhang; Jin Xiao; Fei Wang; Mei Li; Xiao-ze Guo; Hui-bin Xie; Hong Xia; Bei Chen (Human Cell, 2017)

Evaluation of NTCM-BC and a proposed modification for single-frequency positioning - Xiaohong Zhang; Fujian Ma; Xiaodong Ren; Weiliang Xie; Feng Zhu; Xin Li (GPS Solutions, 2017)

Occurrence and incidence of 18 per- and polyfluoroalkyl compounds in edible oils commonly consumed in Guiyang, China - Hongbo Yang; Guihong Li; Zhu Rao; Feng Guo; Zhanbin Li; Feng Xie; Hong Tan (Food Additives & Contaminants: Part A, 2017)

Agrobacterium deltaense sp. nov., an endophytic bacteria isolated from nodule of Sesbania cannabina - Jun Yan; Yan Li; Xiao Zeng Han; Wen Feng Chen; Wen Xiu Zou; Zhihong Xie; Meng Li (Archives of Microbiology, 2017)

Genome-wide identification, characterization, and expression analysis of SnRK2 family in Hevea brasiliensis - Dong Guo; Hui-Liang Li; Jia-Hong Zhu; Ying Wang; Feng An; Gui-Shui Xie; Shi-Qing Peng (Tree Genetics & Genomes, 2017)

Gene Polymorphisms for Both Auto-antigen and Immune-Modulating Proteins Are Associated with the Susceptibility of Autoimmune Myasthenia Gravis - Hai-Feng Li; Yu Hong; Xu Zhang; Yanchen Xie; Geir Olve Skeie; Hong-Jun Hao; Nils Erik Gilhus; Bing Liang; Yao-Xian Yue; Xian-Jun Zhang; Xiang Gao; Qi Wang; et al. (Molecular Neurobiology, 2017)

Green Synthesis of Sucrose Laurate Under Different Ultrasonic Frequencies - Fang-xue Hang; Chang-rong Shi; Yong-shi Xu; Hai-qin Lu; Cai-feng Xie; Kai Li (Sugar Tech, 2017)

Dyslexic Children Show Atypical Cerebellar Activation and Cerebro-Cerebellar Functional Connectivity in Orthographic and Phonological Processing - Xiaoxia Feng; Le Li; Manli Zhang; Xiujie Yang; Mengyu Tian; Weiyi Xie; Yao Lu; Li Liu; Nathalie N. Bélanger; Xiangzhi Meng; Guosheng Ding (The Cerebellum, 2017)

Retraction Note to: CXCR4 Signaling Induced Epithelial-Mesenchymal Transition by PI3K/AKT and ERK Pathways in Glioblastoma - Baoyu Lv; Xiangshan Yang; Shunzeng Lv; Lei Wang; Kaixi Fan; Ranran Shi; Fengling Wang; Huishu Song; Xiaochen Ma; Xuefen Tan; Kun Xu; Jingjing Xie; et al. (Molecular Neurobiology, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

Interaction mechanism of pepsin with a natural inhibitor gastrodin studied by spectroscopic methods and molecular docking - Jie Wang; Calvin Chan; Feng-wen Huang; Jiang-feng Xie; Hong Xu; Ka-wai Ho; Sheng-gang Zheng; Zhang-li Hu; Jun Lu; Zhen-dan He (Medicinal Chemistry Research, 2017)

Gene expression signatures for phlegm-dampness constitution of Chinese medicine - Lingru Li; Juan Feng; Haiqiang Yao; Lan Xie; Yu Chen; Lingling Yang; Shujuan Hou; Shipeng Zhao; Ranran Sun; Yanling Wu; Tongtong Bai; Yingshuai Li; et al. (Science China Life Sciences, 2017)

Fragment growth performance of the invasive submerged macrophyte Myriophyllum spicatum under conditions of different water depths and sediment types - Feng Li; Lianlian Zhu; Yonghong Xie; Shichu Liang; Cong Hu; Xinsheng Chen; Zhengmiao Deng (Aquatic Ecology, 2016)

Molecular epidemiology of J-subgroup avian leukosis virus isolated from meat-type chickens in southern China between 2013 and 2014 - Wencheng Lin; Xinjian Li; Zhenkai Dai; Xinheng Zhang; Shuang Chang; Peng Zhao; Huanmin Zhang; Feng Chen; Qingmei Xie (Archives of Virology, 2016)

Genetic and phylogenetic analysis of a novel parvovirus isolated from chickens in Guangxi, China - Bin Feng; Zhixun Xie; Xianwen Deng; Liji Xie; Zhiqin Xie; Li Huang; Qin Fan; Sisi Luo; Jiaoling Huang; Yanfang Zhang; Tingting Zeng; Sheng Wang; et al. (Archives of Virology, 2016)

Polymorphisms in complement genes and risk of preeclampsia in Taiyuan, China - Weiwei Wu; Hailan Yang; Yongliang Feng; Ping Zhang; Shuzhen Li; Xin Wang; Tingting Peng; Fang Wang; Bingjie Xie; Pengge Guo; Mei Li; Ying Wang; et al. (Inflammation Research, 2016)

Isolation, identification and evolution analysis of a novel subgroup of avian leukosis virus isolated from a local Chinese yellow broiler in South China - Xinjian Li; Wencheng Lin; Shuang Chang; Peng Zhao; Xinheng Zhang; Yang Liu; Weiguo Chen; Baohong Li; Dingming Shu; Huanmin Zhang; Feng Chen; Qingmei Xie (Archives of Virology, 2016)

Neuropeptide S ameliorates olfactory spatial memory impairment induced by scopolamine and MK801 through activation of cognate receptor-expressing neurons in the subiculum complex - Yu-Feng Shao; Can Wang; Jun-Fan Xie; Xiang-Pan Kong; Le Xin; Chao-Yu Dong; Jing Li; Wen-Ting Ren; Yi-Ping Hou (Brain Structure and Function, 2016)

Molecular cloning and characterization of a stress responsive peroxidase gene HbPRX42 from rubber tree - Li-Feng Wang; Ji-Kun Wang; Feng An; Gui-Shui Xie (Brazilian Journal of Botany, 2016)

Changes in the activities of starch metabolism enzymes in rice grains in response to elevated CO2 concentration - Li-Yong Xie; Er-Da Lin; Hong-Liang Zhao; Yong-Xiang Feng (International Journal of Biometeorology, 2016)

Abnormal Functional Connectivity Density in Post-traumatic Stress Disorder - Youxue Zhang; Bing Xie; Heng Chen; Meiling Li; Feng Liu; Huafu Chen (Brain Topography, 2016)

Expression of HIV-encoded microRNA-TAR and its inhibitory effect on viral replication in human primary macrophages - Li Li; Haimin Feng; Qin Da; Honglin Jiang; Lang Chen; Linlin Xie; Qiuling Huang; Hairong Xiong; Fan Luo; Lei Kang; Yan Zeng; Haitao Hu; et al. (Archives of Virology, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Interleukin-12 inhibits the hepatocellular carcinoma growth by inducing macrophage polarization to the M1-like phenotype through downregulation of Stat-3 - Qin Wang; Feng Cheng; Ting-ting Ma; Hai-Yu Xiong; Zi-Wei Li; Chang-Li Xie; Cui-Ying Liu; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2016)

Enhanced autophagy reveals vulnerability of P-gp mediated epirubicin resistance in triple negative breast cancer cells - Li-han Zhang; Ai-jun Yang; Min Wang; Wei Liu; Chen-yu Wang; Xiao-feng Xie; Xu Chen; Jing-fei Dong; Min Li (Apoptosis, 2016)

Feasibility of an enhanced washing process to extract PBDEs/heavy metals/antibiotics from antibiotic resistance gene-affected soil with aqueous DNA followed by microbial augmentation - Mao Ye; Mingming Sun; Jinzhong Wan; Yu Zhao; Shanni Xie; Da Tian; Feng Hu; Huixin Li; Lianggang Zong; Fredrick Orori Kengara; Jiang Xin (Journal of Soils and Sediments, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Differential distribution patterns of ammonia-oxidizing archaea and bacteria in acidic soils of Nanling National Nature Reserve forests in subtropical China - Xian-Hua Gan; Fang-Qiu Zhang; Ji-Dong Gu; Yue-Dong Guo; Zhao-Qing Li; Wei-Qiang Zhang; Xiu-Yu Xu; Yi Zhou; Xiao-Ying Wen; Guo-Guang Xie; Yong-Feng Wang (Antonie van Leeuwenhoek, 2016)

Different roles of three emergent macrophytes in promoting sedimentation in Dongting Lake, China - Feng Li; Ying Pan; Yonghong Xie; Xinsheng Chen; Zhengmiao Deng; Xu Li; Zhiyong Hou; Yue Tang (Aquatic Sciences, 2016)

RETRACTED ARTICLE: CXCR4 Signaling Induced Epithelial-Mesenchymal Transition by PI3K/AKT and ERK Pathways in Glioblastoma - Baoyu Lv; Xiangshan Yang; Shunzeng Lv; Lei Wang; Kaixi Fan; Ranran Shi; Fengling Wang; Huishu Song; Xiaochen Ma; Xuefen Tan; Kun Xu; Jingjing Xie; et al. (Molecular Neurobiology, 2015)

National serosurvey of encephalomyocarditis virus in healthy people and pigs in China - Ruofei Feng; Jia Wei; Haixia Zhang; Jingjing Fan; Xiangrong Li; Dan Wang; Jingying Xie; Zilin Qiao; Mingsheng Li; Jialin Bai; Zhongren Ma (Archives of Virology, 2015)

Association between Val66Met polymorphisms in brain-derived neurotrophic factor gene and asthma risk: a meta-analysis - Xinming Xie; Yanting Zhu; Jiaojiao Zhang; Cui Zhai; Wei Feng; Yilin Pan; Lu Liu; Xiaofan Su; Lan Yang; Manxiang Li (Inflammation Research, 2015)

p55γ functional mimetic peptide N24 blocks vascular proliferative disorders - Jiaojiao Guo; Ning Xie; Geng Li; Yan Zhang; Fengxiang Lv; Sile Guo; Yuanqing Feng; Chun-Mei Cao; Rui-Ping Xiao (Journal of Molecular Medicine, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Relationships among the monsoon-like southwest Australian circulation, the Southern Annular Mode, and winter rainfall over southwest Western Australia - Juan Feng; Jianping Li; Yun Li; Jianlei Zhu; Fei Xie (Advances in Atmospheric Sciences, 2015)

Analysis of the sucrose synthase gene family in tobacco: structure, phylogeny, and expression patterns - Zhong Wang; Pan Wei; Mingzhu Wu; Yalong Xu; Feng Li; Zhaopeng Luo; Jianfeng Zhang; Ang Chen; Xiaodong Xie; Peijian Cao; Fucheng Lin; Jun Yang (Planta, 2015)

Combined influence of hydrological gradient and edaphic factors on the distribution of macrophyte communities in Dongting Lake wetlands, China - Xinsheng Chen; Xu Li; Yonghong Xie; Feng Li; Zhiyong Hou; Jing Zeng (Wetlands Ecology and Management, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Characterization of Post-traumatic Stress Disorder Using Resting-State fMRI with a Multi-level Parametric Classification Approach - Feng Liu; Bing Xie; Yifeng Wang; Wenbin Guo; Jean-Paul Fouche; Zhiliang Long; Wenqin Wang; Heng Chen; Meiling Li; Xujun Duan; Jiang Zhang; Mingguo Qiu; et al. (Brain Topography, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

TRAF4 mediates activation of TGF-β signaling and is a biomarker for oncogenesis in breast cancer - FangFang Zhou; Fang Li; Feng Xie; ZhengKui Zhang; HuiZhe Huang; Long Zhang (Science China Life Sciences, 2014)

Effects of Apelin-13 on Rat Bone Marrow-Derived Mesenchymal Stem Cell Proliferation Through the AKT/GSK3β/Cyclin D1 Pathway - Lanfang Li; Lifang Li; Lu He; Zidong Zhang; Feng Xie; Yu Guo; Jianhua Xiao; Linxi Chen; Jian Li (International Journal of Peptide Research and Therapeutics, 2014)

Modulation, Bioinformatic Screening, and Assessment of Small Molecular Peptides Targeting the Vascular Endothelial Growth Factor Receptor - Shibin Feng; Lingyun Zou; Qingshan Ni; Xiang Zhang; Qianwei Li; Lei Zheng; Laiping Xie; Hongmin Li; Dingde Huang (Cell Biochemistry and Biophysics, 2014)

Effects of sediment burial disturbance on the vegetative propagation of Phalaris arundinacea with different shoot statuses - Xinsheng Chen; Zhengmiao Deng; Yonghong Xie; Feng Li; Zhiyong Hou; Xu Li; Y. F. Li (Aquatic Ecology, 2014)

Deep-Red Phosphorescent Iridium(III) Complexes Containing 1-(Benzo[b] Thiophen-2-yl) Isoquinoline Ligand: Synthesis, Photophysical and Electrochemical Properties and DFT Calculations - Gao-Nan Li; Ying Zou; Yi-Ding Yang; Jiao Liang; Feng Cui; Tao Zheng; Hui Xie; Zhi-Gang Niu (Journal of Fluorescence, 2014)

Platelet-derived growth factor mediates interleukin-13-induced collagen I production in mouse airway fibroblasts - Jiamei Lu; Yanting Zhu; Wei Feng; Yilin Pan; Shaojun Li; Dong Han; Lu Liu; Xinming Xie; Guizuo Wang; Manxiang Li (Journal of Biosciences, 2014)

Evidence for natural Borna disease virus infection in healthy domestic animals in three areas of western China - Liang Zhang; Xiao Wang; Qunling Zhan; Zhenhai Wang; Mingming Xu; Dan Zhu; Feng He; Xia Liu; Rongzhong Huang; Dan Li; Yang Lei; Peng Xie (Archives of Virology, 2014)

Sequence and phylogenetic analysis of surface protein genes of emerging H9N2 influenza viruses isolated from poultry in two geographical regions of China - Yu Xue; Jing-Lan Wang; Zhuan-Qiang Yan; Guang-Wei Li; Shun-Yan Chen; Xiang-Bin Zhang; Jian-Ping Qin; Hai-Yan Li; Shuang Chang; Feng Chen; Ying-Zuo Bee; Qing-Mei Xie (Virus Genes, 2014)

Protection of MES23.5 dopaminergic cells by obestatin is mediated by proliferative rather than anti-apoptotic action - Xiao-Li Shen; Feng-Ju Jia; Ning Song; Jun-Xia Xie; Hong Jiang (Neuroscience Bulletin, 2014)

Relationship between the algal partners and the growth of lichen-forming fungus Porpidia crustulata - Bo Li; Jia Feng; Shu-lian Xie (Symbiosis, 2014)

Cell cycle perturbations induced by human herpesvirus 6 infection and their effect on virus replication - Lingyun Li; Bin Gu; Feng Zhou; Jing Chi; Dongju Feng; Fangyi Xie; Fang Wang; Changyan Ma; Meng Li; Jinfeng Wang; Kun Yao (Archives of Virology, 2014)

Effects of intercropping with Atractylodes lancea and application of bio-organic fertiliser on soil invertebrates, disease control and peanut productivity in continuous peanut cropping field in subtropical China - Xiao-gang Li; Xing-xiang Wang; Chuan-chao Dai; Tao-lin Zhang; Xing-guang Xie; Chang-feng Ding; Hong-wei Wang (Agroforestry Systems, 2014)

Fine mapping of the Ph-3 gene conferring resistance to late blight (Phytophthora infestans) in tomato - Chunzhi Zhang; Lei Liu; Zheng Zheng; Yuyan Sun; Longxi Zhou; Yuhong Yang; Feng Cheng; Zhonghua Zhang; Xiaowu Wang; Sanwen Huang; Bingyan Xie; Yongchen Du; et al. (Theoretical and Applied Genetics, 2013)

qLTG-9, a stable quantitative trait locus for low-temperature germination in rice (Oryza sativa L.) - Linfang Li; Xi Liu; Kun Xie; Yihua Wang; Feng Liu; Qiuyun Lin; Wenyan Wang; Chunyan Yang; Bingyue Lu; Shijia Liu; Liangming Chen; Ling Jiang; et al. (Theoretical and Applied Genetics, 2013)

Autophagy, a new target for disease treatment - Feng Xie; LanFang Li; LinXi Chen (Science China Life Sciences, 2013)

Morphological and phylogenetic study of algal partners associated with the lichen-forming fungus Porpidia crustulata from the Guancen Mountains, northern China - Bo Li; Jia Feng; Shu-lian Xie (Symbiosis, 2013)

Growth responses and non-structural carbohydrates in three wetland macrophyte species following submergence and de-submergence - Xianyan Qin; Feng Li; Xinsheng Chen; Yonghong Xie (Acta Physiologiae Plantarum, 2013)

Succession of aquatic macrophytes in the Modern Yellow River Delta after 150 years of alluviation - Feng Li; Yonghong Xie; Xinsheng Chen; Zhiyong Hou; Xu Li; Zhengmiao Deng; Yinyin Liu; Jiayu Hu; Na Liu (Wetlands Ecology and Management, 2013)

Molecular characterization and phylogenetic analysis of infectious bursal disease viruses isolated from chicken in South China in 2011 - Di Liu; Xiang-Bin Zhang; Zhuan-Qiang Yan; Feng Chen; Jun Ji; Jian-Ping Qin; Hai-Yan Li; Jun-Peng Lu; Yu Xue; Jia-Jia Liu; Qing-Mei Xie; Jing-Yun Ma; et al. (Tropical Animal Health and Production, 2013)

Sequence and phylogenetic analysis of nucleocapsid genes of porcine epidemic diarrhea virus (PEDV) strains in China - Zhili Li; Feng Chen; Yao Yuan; Xiduo Zeng; Zhongyan Wei; Ling Zhu; Baoli Sun; Qingmei Xie; Yongchang Cao; Chunyi Xue; Jingyun Ma; Yingzuo Bee (Archives of Virology, 2013)

Tanshinone IIA and astragaloside IV promote the migration of mesenchymal stem cells by up-regulation of CXCR4 - Juan Xie; Huan Wang; Tiebing Song; Zongren Wang; Feng Li; Jing Ma; Jun Chen; Yayun Nan; Hui Yi; Wen Wang (Protoplasma, 2013)

Phylogeographic Patterns of mtDNA Variation Revealed Multiple Glacial Refugia for the Frog Species Feirana taihangnica Endemic to the Qinling Mountains - Bin Wang; Jianping Jiang; Feng Xie; Cheng Li (Journal of Molecular Evolution, 2013)

Physiological mechanisms for plant distribution pattern: responses to flooding and drought in three wetland plants from Dongting Lake, China - Feng Li; Xianyan Qin; Yonghong Xie; Xinsheng Chen; Jiayu Hu; Yinyin Liu; Zhiyong Hou (Limnology, 2013)

Binding properties of Ru(II) polypyridyl complexes with poly(U)·poly(A)*poly(U) triplex: the ancillary ligand effect on third-strand stabilization - Li-Feng Tan; Ling-Jun Xie; Xiao-Nan Sun (JBIC Journal of Biological Inorganic Chemistry, 2013)

Paenibacillus taohuashanense sp. nov., a nitrogen-fixing species isolated from rhizosphere soil of the root of Caragana kansuensis Pojark - Jian-Bo Xie; Li-Hong Zhang; Yu-Guang Zhou; Hong-Can Liu; San-Feng Chen (Antonie van Leeuwenhoek, 2012)

Association study of ACE polymorphisms and systemic lupus erythematosus in Northern Chinese Han population - Ai-min Gong; Xin-yuan Li; Yi-qin Wang; Hai-xia Yan; Zhao-xia Xu; Zhao Feng; Yi-qiang Xie; De-hui Yin; Shi-zhong Yang (Molecular Biology Reports, 2012)

Association of STAT4 rs7574865 polymorphism with autoimmune diseases: a meta-analysis - Ya-ling Liang; Hua Wu; Xi Shen; Pei-qiang Li; Xiao-qing Yang; Li Liang; Wei-hua Tian; Li-feng Zhang; Xiao-dong Xie (Molecular Biology Reports, 2012)

Heavy metal uptake capacities by the common freshwater green alga Cladophora fracta - Li Ji; Shulian Xie; Jia Feng; Yanhui Li; Le Chen (Journal of Applied Phycology, 2012)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) field strains in south China - Zhi-Li Li; Ling Zhu; Jing-Yun Ma; Qing-Feng Zhou; Yan-Hua Song; Bao-Li Sun; Rui-Ai Chen; Qing-Mei Xie; Ying-Zuo Bee (Virus Genes, 2012)

3-Nitro-naphthalimide and nitrogen mustard conjugate NNM-25 induces hepatocellular carcinoma apoptosis via PARP-1/p53 pathway - Song-qiang Xie; Ya-hong Zhang; Qian Li; Feng-hua Xu; Jiu-wang Miao; Jin Zhao; Chao-jie Wang (Apoptosis, 2012)

Human anti-EGFL7 recombinant full-length antibodies selected from a mammalian cell-based antibody display library - Feng Li; Yan-Hong Liu; Yan-Wen Li; Qian Ju; Lin Chen; Ping-Li Xie; Yue-Hui Li; Guan-Cheng Li (Molecular and Cellular Biochemistry, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Molecular cloning, characterization and differential expression of Cdc42 in Fonsecaea monophora - Zhi Xie; Peiying Feng; Junming Zhang; Xiqing Li; Jiufeng Sun; Changming Lu; Huaiqiu Huang; Liyan Xi (Molecular Biology Reports, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Local structure of Se nanotube investigated by X-ray absorption fine structure spectroscopy - Yajuan Feng; Zhi Xie; Zhihu Sun; Jing Zhang; Tao Yao; Yuanyuan Li; Ziyu Wu; Lirong Zheng; Zhiyun Pan; Shiqiang Wei (Rendiconti Lincei. Scienze Fisiche e Naturali, 2011)

Highly enriched CD133+CD44+ stem-like cells with CD133+CD44high metastatic subset in HCT116 colon cancer cells - Ke-li Chen; Feng Pan; Heng Jiang; Jian-fang Chen; Li Pei; Fang-wei Xie; Hou-jie Liang (Clinical & Experimental Metastasis, 2011)

Effect of Copper on the Expression of TGF-β in Incubated Chondrocytes of Newborn Pigs - Xiaoyan Zhu; Jianguo Wang; Guanghong Xie; Haihua Feng; Xiaobing Li; Lei Liu; Xiaoxu Wang; Dongna Li; Zhaoxi Liu; Jian Qian; Zhe Wang; Guowen Liu (Biological Trace Element Research, 2011)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

Genomic Differences Between Actinobacillus pleuropneumoniae Serotypes 5b and 3 and their Distribution and Transcription Among 15 Serotypes - Feng Yang; Fang Xie; Yuwen Jiang; Suqing Li; Yanping Xing; Yu Wang; Xin Feng; Wenyu Han; Liancheng Lei (Current Microbiology, 2011)

Magma mixing of granites at Lianghe: In-situ zircon analysis for trace elements, U-Pb ages and Hf isotopes - Feng Cong; ShiLiang Lin; GuangFu Zou; ZaiHui Li; Tao Xie; ZhiMin Peng; Ting Liang (Science China Earth Sciences, 2011)

Potential for forest vegetation carbon storage in Fujian Province, China, determined from forest inventories - Yin Ren; Xiaohua Wei; Li Zhang; Shenghui Cui; Feng Chen; Yongzhu Xiong; Pingping Xie (Plant and Soil, 2011)

Tetraethylammonium enhances the rectal and colonic motility in rats and human in vitro - Zhe Li; Zhi-Lin Xu; Jing Liang; Ji-Chao Wu; Chao-Wei Hu; Hui Xie; Wen-Chao Ma; Hong-Chi Jiang; Bao-Feng Yang; De-Li Dong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Identification and mapping of quantitative resistance to late blight (Phytophthora infestans) in Solanum habrochaites LA1777 - Junming Li; Lei Liu; Yuling Bai; Richard Finkers; Feng Wang; Yongchen Du; Yuhong Yang; Bingyan Xie; Richard G. F. Visser; Adriaan W. van Heusden (Euphytica, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Blood cells of a sisorid catfish Glyptosternum maculatum (Siluriformes: Sisoridae), in Tibetan Plateau - Hui Juan Zhang; Cong Xin Xie; Da Peng Li; Hai Ping Liu; Xue Feng Yang (Fish Physiology and Biochemistry, 2011)

Plant distribution can be reflected by the different growth and morphological responses to water level and shade in two emergent macrophyte seedlings in the Sanjiang Plain - Feng Li; Youzhi Li; Hongyan Qin; Yonghong Xie (Aquatic Ecology, 2011)

Water quality of a tributary of the Pearl River, the Beijiang, Southern China: implications from multivariate statistical analyses - Ming W. Song; Ping Huang; Feng Li; Hui Zhang; Kai Z. Xie; Xi H. Wang; Guo X. He (Environmental Monitoring and Assessment, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Molecular cloning, characterization and expression of PmRsr1, a Ras-related gene from yeast form of Penicillium marneffei - Peiying Feng; Zhi Xie; Jiufeng Sun; Junmin Zhang; Xiqing Li; Changming Lu; Liyan Xi (Molecular Biology Reports, 2010)

Exposure to lanthanum compound diminishes LPS-induced inflammation-associated gene expression: involvements of PKC and NF-κB signaling pathways - Fei Guo; Yuanlei Lou; Nianhua Feng; Guohui Li; An Xie; Xueming Huang; Yang Wang (BioMetals, 2010)

Competition and Facilitation in Three Marsh Plants in Response to a Water-Level Gradient - Wenbo Luo; Yonghong Xie; Xinsheng Chen; Feng Li; Xianyan Qin (Wetlands, 2010)

Trap Induction and Trapping in Eight Nematode-trapping Fungi (Orbiliaceae) as Affected by Juvenile Stage of Caenorhabditis elegans - Hongyan Xie; F. M. Aminuzzaman; Lingling Xu; Yiling Lai; Feng Li; Xingzhong Liu (Mycopathologia, 2010)

Protein sumoylation sites prediction based on two-stage feature selection - Lin Lu; Xiao-He Shi; Su-Jun Li; Zhi-Qun Xie; Yong-Li Feng; Wen-Cong Lu; Yi-Xue Li; Haipeng Li; Yu-Dong Cai (Molecular Diversity, 2010)

Calcineurin Plays an Important Role in the Shell Formation of Pearl Oyster (Pinctada fucata) - Changzhong Li; Yilin Hu; Jian Liang; Yawei Kong; Jing Huang; Qiaoli Feng; Shuo Li; Guiyou Zhang; Liping Xie; Rongqing Zhang (Marine Biotechnology, 2010)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

A novel method for promoting conidial production by a nematophagous fungus, Pochonia chlamydosporia AS6.8 - Ling-Ling Xu; Feng Li; Hong-Yan Xie; Xing-Zhong Liu (World Journal of Microbiology and Biotechnology, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Molecular Cloning and Expression of cDNA Encoding the Cysteine Proteinase Inhibitor from Upland Cotton - Ming-feng Jiang; Sheng-wei Li; Min Chen; Ying-fan Cai; Yong-fang Xie; Biao Li; Quan Sun; Huai-zhong Jiang; Zheng Pan; Yun-ling Gao; You-Lu Yuan; Yu-zheng Shi (Journal of Plant Biology, 2009)

Using remote sensing to estimate sea ice thickness in the Bohai Sea, China based on ice type - Li Ning; Feng Xie; Wei Gu; Yingjun Xu; Shuqing Huang; Shuai Yuan; Weijia Cui; Jason Levy (International Journal of Remote Sensing, 2009)

Erythroid differentiation-related factor expression driven by effective promoter to ameliorate the anemia syndrome - Pingyu Wang; Shuyang Xie; Yongliang Chi; Fei Jiao; Zunling Li; Ying Ma; Feng Liu (Biologia, 2009)

Isolation and characterization of twelve novel microsatellites in yellow catfish, Pelteobagrus fulvidraco - Xiao-Yu Feng; Zhong-Quan Li; Nan Xie; Jia-Le Li (Conservation Genetics, 2009)

Shoot regeneration of dwarf dogwood (Cornus canadensis L.) and morphological characterization of the regenerated plants - Chun-Miao Feng; Rongda Qu; Li-Li Zhou; De-Yu Xie; Qiu-Yun (Jenny) Xiang (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Investigation of Phosphorylation Site Responsible for CaLP (P. fucata) Nucleo-cytoplasmic Shuttling Triggered by Overexpression of p21Cip1 - Z. Fang; Q. Wang; W. Cao; Q. Feng; C. Li; L. Xie; R. Zhang (Marine Biotechnology, 2009)

Proposed Conservation Landscape for Giant Pandas in the Minshan Mountains, China - GUOZHEN SHEN; CHAOYANG FENG; ZONGQIANG XIE; ZHIYUN OUYANG; JUNQING LI; MARTY PASCAL (Conservation Biology, 2008)
The giant panda ( Ailuropoda melanoleuca ), is one of the world's most endangered species. Habitat loss and fragmentation have reduced its numbers, shrunk its distribution, and separated the population into isolated subpopulations. Such isolated, small populations are in danger of extinction due to random demographic factors and inbreeding. We used least‐cost modeling as a systematic approach to incorporate satellite imagery and data on ecological and behavioral parameters of the giant panda collected during more than 10 years of field research to design a conservation landscape for giant pandas in the Minshan Mountains. We identified 8 core habitats and 4 potential linkages that would link core habitats CH3, CH4, and CH5 with core habitats CH6, CH7, and CH8. Establishing and integrating the identified habitats with existing reserves would create an efficient reserve network for giant panda conservation. The core habitats had an average density of 4.9 pandas/100 km 2 and contained approximately 76.6% of the giant panda population. About 45% of the core habitat (3245.4 km 2 ) existed outside the current nature reserves network. Total estimated core habitat decreased between 30.4 and 44.5% with the addition of residential areas and road networks factored into the model. A conservation area for giant panda in the Minshan Mountains should aim to ensure habitat retention and connectivity, improve dispersal potential of corridors, and maintain the evolutionary potential of giant pandas in the face of future environmental changes.

Cloning and characterization of chicken SPATA4 gene and analysis of its specific expression - Ming-Chao Xie; Chao Ai; Xiu-Mei Jin; Shang-Feng Liu; Shi-Xin Tao; Zan-Dong Li; Zhao Wang (Molecular and Cellular Biochemistry, 2007)

The origin of the temperature-induced fluorescence fluctuation in Spirulina platensis: temperature-sensitive mobility of PQ molecules - Heng Li; Shuzhen Yang; Jie Xie; Juanjuan Feng; Yandao Gong; Jingquan Zhao (Photosynthesis Research, 2007)

Relationships between O isotope equilibrium, mineral alteration and Rb–Sr chronometric validity in granitoids: implications for determination of cooling rate - Jiang Feng Chen; Yong-Fei Zheng; Zi-Fu Zhao; Bo Li; Zhi Xie; Bing Gong; Hui Qian (Contributions to Mineralogy and Petrology, 2007)

Expression of a bacterial aroA mutant, aroA-M1 , encoding 5-enolpyruvylshikimate-3-phosphate synthase for the production of glyphosate-resistant tobacco plants - He-Yong Wang; Yun-Feng Li; Long-Xu Xie; Peilin Xu (Journal of Plant Research, 2003)

NDVI changes in China between 1989 and 1999 using change vector analysis based on time series data - Chen Yun-hao; Li Xiao-bing; Xie Feng (Journal of Geographical Sciences, 2001)